Silicone hydrogel lenses with water-rich surfaces

JP2025029005AActive Publication Date: 2025-03-05ALCON INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024207150
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2011-03-02
Filing Date
2024-11-28
Publication Date
2025-03-05
Estimated Expiration
2031-07-29

Smart Images

  • Figure 2025029005000001_ABST
    Figure 2025029005000001_ABST
Patent Text Reader

Abstract

To provide SiHy contact lenses with hydrophilic surfaces which exhibit persistent hydrophilicity, wettability, and lubricity that can be maintained in the eye throughout the entire day.SOLUTION: The present invention relates to a hydrated silicone hydrogel contact lens having a layered structural configuration, and a low-water-content silicone hydrogel core (or bulk material) completely covered with a layer of a water-rich (e.g., a water content greater than 80%) hydrogel totally or substantially free of silicone. The hydrated silicone hydrogel contact lens of the present invention has a high oxygen permeability to maintain corneal health, and a soft, water-rich, lubricious surface for wearing comfort.SELECTED DRAWING: Figure 4C
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates generally to an ophthalmic device, and in particular to a lens having a structure that creates a water content gradient, and a water content (WC) of about 10% to about 70% (by weight). SiHy and a hydrogel material having a thickness of about 0.1 to about 20 μm, completely covering the silicone hydrogel bulk material and completely or substantially free of silicone, and when a cross section of the silicone hydrogel contact lens in a fully hydrated state is measured by AFM, the cross section has a WC SiHy ≦45%, characterized by a water swelling rate of at least about 100%, or WC SiHy >45%, at least approximately [120·WC SiHy / (1-WC SiHy and an outer surface layer having a higher water content characterized by a water swelling rate of 3.0% (water swelling rate of 3.0%).

[0002] background Silicone hydrogel (SiHy) contact lenses are widely used to correct various types of vision defects. They consist of hydrated cross-linked polymeric materials that contain silicone and a certain amount of water in equilibrium within the lens polymer matrix. According to the FDA contact lens classification, hydrogel contact lenses are generally classified into two main categories: low water content contact lenses (containing less than 50% water) and high water content contact lenses (containing more than 50% water). For SiHy contact lenses, the high oxygen permeability required to minimize the adverse effects of contact lenses on corneal health is achieved by incorporating silicone into the cross-linked polymeric material rather than increasing the water content. As a result, unlike conventional hydrogel contact lenses, SiHy contact lenses can have a low water content while still having a relatively high oxygen permeability (Dk). For example, CIBA Vision Corporation's Focus® Night&Day® (approximately 23.5% H2O and Dk~140 Barrer; CIBA Vision Corporation's Air Optix® (approximately 33% H2O and Dk~110 Barrer); Bausch & Lomb's PureVision® (approximately 36% H2O and Dk~100 Barrer); Johnson & Johnson's Acuvue® Oasys® (approximately 38% H2O, Dk~105 Barrer); Johnson & Johnson's Acuvue® Advance® (approximately 47% H2O, Dk~65 Barrer) rer); Johnson & Johnson's Acuvue® TruEye® (approximately 46% H2O, Dk~100 Barrer); CooperVision's Biofinity® (approximately 48% H2O, Dk~128 Barrer); CooperVision's Avaira® (approximately 46% H2O, Dk~100 Barrer); and Menicon's PremiO® (approximately 40% H2O, Dk~129 Barrer).

[0003] The water content in the SiHy contact lenses can provide the desired flexibility that allows the SiHy lenses to be worn for a sufficiently long period of time and provides the patient with benefits such as adequate initial comfort (i.e., immediately after lens insertion), a relatively short adaptation time required for the patient to adapt to them, and / or a proper fit. A higher water content would be desirable to provide SiHy contact lenses with biocompatibility and comfort. However, there is a limit to the amount of water that SiHy contact lenses can contain (believed to be 80%) while still having sufficient mechanical strength and stiffness required for contact lenses as in conventional hydrogel contact lenses. Furthermore, a high water content can also have undesirable effects. For example, the oxygen permeability of SiHy contact lenses can be reduced by increasing the water content. Furthermore, because SiHy contact lenses with a high water content can lose the eye's limited supply of tears (water), a high water content of the SiHy lenses can lead to greater intraocular dehydration and, as a result, wearing discomfort caused by dehydration. It is believed that intraocular dehydration can result from evaporation (i.e., loss of water) at the anterior surface of a contact lens, that such water loss is controlled primarily by diffusion of water from the posterior to the anterior surface of the lens, and that the rate of diffusion is closely proportional to the water content of the lens bulk material at equilibrium (L. Jones et al., Contact Lens & Anterior Eye 25 (2002) 147-156, incorporated herein by reference in its entirety).

[0004] The incorporation of silicone into contact lens materials also has an undesirable effect on the biocompatibility of contact lenses, since silicone is hydrophobic and has a strong tendency to migrate to lens surfaces exposed to air. As a result, SiHy contact lenses will generally require surface modification processes, such as various plasma treatments (e.g., Focus® Night&Day® and Air Optix® from CIBA Vision Corporation; PureVision® from Bausch&Lomb; and PremiO™ from Menicon); internal wetting agents physically and / or chemically embedded in the SiHy polymer matrix (e.g., Acuvue® Oasys®, Acuvue® Advance®, and Acuvue® TruEye™ from Johnson&Johnson; Biofinity® and Avira™ from CooperVision) to eliminate or minimize the exposure of silicone to the contact lens and to maintain a hydrophilic surface. Although the surface modification techniques used in the manufacture of commercially available SiHy lenses can provide new (unused) SiHy lenses with a reasonably hydrophilic surface, SiHy lenses worn in the eye can have dry spots and / or hydrophobic surface areas resulting from partial lack of protection from air exposure, eyelid shearing forces, silicone migration and / or silicone exposure. These dry spots and / or hydrophobic surface areas are non-wettable and prone to adsorb lipids or proteins from the intraocular environment and can adhere to the eye causing discomfort to the patient.

[0005] Therefore, there is a need for SiHy contact lenses with hydrophilic surfaces that have sustained hydrophilicity, wettability and lubricity that can be maintained throughout the day in the eye.

[0006] Summary of the Invention The present invention can meet the need for SiHy contact lenses with hydrophilic surfaces that have sustained surface hydrophilicity, surface wettability, and surface lubricity throughout the day in the eye.

[0007] In one aspect, the invention is a hydrated silicone hydrogel contact lens comprising an anterior (convex) surface and an opposite posterior (concave) surface; and a layered configuration from the anterior to posterior surface, the layered configuration comprising an anterior outer hydrogel layer, an inner layer of silicone hydrogel material, and a posterior outer hydrogel layer, the silicone hydrogel material having an oxygen permeability (Dk) of at least about 50, preferably at least about 60, more preferably at least about 70, even more preferably at least about 90 barrers, and most preferably at least about 110 barrers, and a first water content (WC) of about 10% to about 70%, preferably about 10% to about 65%, more preferably about 10% to about 60%, even more preferably about 15% to about 55%, and most preferably about 15% to about 50% by weight. SiHy wherein the anterior and posterior outer hydrogel layers are of substantially uniform thickness and are fused at the peripheral edges of the contact lens to completely encapsulate the inner layer of silicone hydrogel material, and wherein the anterior and posterior outer hydrogel layers, independently of one another, have a thickness of at least about 100% by mass, preferably at least about 100% by mass, more preferably at least about 15 ... SiHy having a water swelling ratio (expressed as WSR) of at least about 100% (preferably at least about 150%, more preferably at least about 200%, even more preferably at least about 250%, and most preferably at least about 300%) if WC>45%, or at least about [120·WC SiHy / (1-WC SiHy )]% (preferably, [130·WC SiHy / (1-WC SiHy )]%, more preferably, [140·WC SiHy / (1-WC SiHy )]%, and even more preferably, [150·WC SiHy / (1-WC SiHy )%) in water expansion coefficient, SiHyA hydrated silicone hydrogel contact lens is provided having a higher second water content, with the anterior and posterior outer hydrogel layers each having a thickness of from about 0.1 μm to about 20 μm, preferably from about 0.25 μm to about 15 μm, more preferably from about 0.5 μm to about 12.5 μm, and even more preferably from about 1 μm to about 10 μm (as measured by atomic force microscopy across a cross section from the posterior to the anterior surface of the silicone hydrogel contact lens in a fully hydrated state).

[0008] In another aspect, the present invention provides a hydrated silicone hydrogel contact lens. The hydrated silicone hydrogel contact lens of the present invention comprises a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface; the contact lens has an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrer / mm, and a cross-sectional surface modulus profile (along the shortest line between the anterior and posterior surfaces of the cross-sectional surface of the contact lens, the anterior surface outer region including and adjacent the anterior surface; an inner region including and surrounding the center of the shortest line; and a posterior surface outer region including and adjacent the posterior surface, the anterior surface outer region having an average anterior surface modulus profile of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrer / mm).

number

number

number

number

[0009] In a further aspect, the present invention provides a hydrated silicone hydrogel contact lens. The hydrated silicone hydrogel contact lens of the present invention comprises a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface; the contact lens has (1) an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, even more preferably at least about 110 barrer / mm, and (2) a surface lubricity characterized by a critical coefficient of friction (referred to as CCOF) of about 0.046 or less, preferably about 0.043 or less, more preferably about 0.040 or less, the anterior and posterior surfaces having a low surface concentration of negatively charged groups, such as carboxylic acid groups, characterized by attracting a maximum of about 200, preferably a maximum of about 160, more preferably a maximum of about 120, even more preferably a maximum of about 90, most preferably a maximum of about 60 positively charged particles in a positively charged particle adhesion test.

[0010] These and other aspects of the present invention, including various preferred embodiments in any combination, will become apparent from the following description of preferred embodiments of the invention. The detailed description is merely illustrative of the invention and is not intended to limit the scope of the invention, which is defined by the appended claims and equivalents thereof. As would be apparent to one skilled in the art, many variations and modifications of the present invention can be made without departing from the spirit and scope of the novel concepts of the disclosure. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 shows a schematic cross-sectional view of the structural geometry of a SiHy contact lens according to a preferred embodiment of the present invention. [Diagram 2]FIG. 2 shows a schematic cross-sectional view of the structural shape of a SiHy contact lens according to another preferred embodiment of the present invention. [Figure 3A] FIG. 3A shows the fluorescence intensity profile across the cross section of a SiHy contact lens by confocal laser fluorescence microscopy. [Figure 3B] FIG. 3B shows the fluorescence intensity profile across the cross section of a SiHy contact lens by confocal laser fluorescence microscopy. [Figure 4A] FIG. 4A shows an SEM (scanning electron microscope) image of a SiHy contact lens of the present invention in a freeze-dried state. [Figure 4B] FIG. 4B shows an SEM (scanning electron microscope) image of a SiHy contact lens of the present invention in a freeze-dried state. [Figure 4C] FIG. 4C shows an SEM (scanning electron microscope) image of a SiHy contact lens of the present invention in a freeze-dried state. [Diagram 5] FIG. 5 illustrates a schematic of a tilted plate setup according to a preferred embodiment. [Figure 6A] FIG. 6A shows optical microscope images of contact lenses having various coatings thereon after immersion in a dispersion of positively charged particles (DOWEX™ 1×4 20-50 mesh resin). [Figure 6B] FIG. 6B shows optical microscope images of contact lenses having various coatings thereon after immersion in a dispersion of positively charged particles (DOWEX™ 1×4 20-50 mesh resin). [Figure 6C] FIG. 6C shows optical microscope images of contact lenses having various coatings thereon after immersion in a dispersion of positively charged particles (DOWEX™ 1×4 20-50 mesh resin). [Figure 7] FIG. 7 illustrates generally how a cross-section of a SiHy contact lens of the present invention was mounted vertically in a metal clamp for AFM testing. [Figure 8]FIG. 8 shows an AFM (atomic force microscopy) image of a portion of a cross section of a SiHy contact lens in a fully hydrated state (in phosphate buffered saline, pH 7.3) according to a preferred embodiment of the present invention. [Figure 9] FIG. 9 shows the cross-sectional surface modulus profile of a SiHy contact lens of the present invention in a fully hydrated state (in phosphate buffered saline, pH ∼7.3) along the two shortest lines between the front and back surfaces of the cross-sectional surface of the SiHy contact lens according to a preferred embodiment of the present invention, approximately represented by a plot of cantilever deflection as a function of distance.

[0012] DETAILED DESCRIPTION OF EMBODIMENTS OF THEINVENTION Reference will now be made in detail to the embodiments of the present invention. It will be apparent to those skilled in the art that various modifications, variations, and combinations can be made in the present invention without departing from the scope or spirit of the present invention. For example, features illustrated or described as part of one embodiment can be used in another embodiment to obtain still further embodiments. It is therefore intended that the present invention encompass such modifications, variations, and combinations as fall within the scope of the appended claims and their equivalents. Other objects, features, and aspects of the present invention will be disclosed in or will be apparent from the following detailed description. It will be appreciated by those skilled in the art that the discussion of the present invention merely describes exemplary embodiments, and is not intended to limit the broader aspects of the present invention.

[0013] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention belongs. In general, the nomenclature and laboratory procedures used herein are well known and commonly used in the art. Conventional methods are used for these procedures as given in the art and various general references. Where a term is given in the singular, the inventors also contemplate the plural of that term. The nomenclature used herein and the laboratory procedures described below are well known and commonly used in the art.

[0014] As used herein, the term "silicone hydrogel contact lenses" refers to contact lenses that include a silicone hydrogel material.

[0015] As used herein, the term "hydrogel" or "hydrogel material" refers to a crosslinked polymeric material that is water insoluble and can contain at least 10% water (by weight) in its polymer matrix when fully hydrated.

[0016] As used herein, the term "non-silicone hydrogel" refers to a hydrogel that does not theoretically contain silicone.

[0017] As used herein, the term "silicone hydrogel" refers to a hydrogel containing silicone.Silicone hydrogels are typically obtained by copolymerization of a polymerizable composition comprising at least one silicone-containing vinyl monomer or at least one silicone-containing vinyl macromer or at least one silicone-containing prepolymer having ethylenically unsaturated groups.

[0018] As used herein, the term "vinyl monomer" refers to a compound that has one single ethylenically unsaturated group and that can be polymerized actinically or thermally.

[0019] As used herein, the terms "olefinically unsaturated group" or "ethylenically unsaturated group" are used broadly herein and are intended to encompass any group that contains at least one >C=C< group. Exemplary ethylenically unsaturated groups include: [ka] Includes, but is not limited to, styrenyl or other C=C containing groups.

[0020] As used herein, the term "(meth)acrylamide" refers to methacrylamide and / or acrylamide.

[0021] As used herein, the term "(meth)acrylate" refers to methacrylate and / or acrylate.

[0022] As used herein, the term "hydrophilic vinyl monomer" refers to a vinyl monomer which, as a homopolymer, typically produces a polymer that is water soluble or can absorb at least 10% (by weight) water.

[0023] As used herein, the term "hydrophobic vinyl monomer" refers to a vinyl monomer which, as a homopolymer, typically yields a polymer that is insoluble in water and can absorb less than 10% (by weight) water.

[0024] As used herein, the term "macromer" or "prepolymer" refers to a medium to high molecular weight compound or polymer that contains two or more ethylenically unsaturated groups. Medium to high molecular weight typically means an average molecular weight greater than 700 Daltons.

[0025] As used herein, the term "crosslinker" refers to a compound having at least two ethylenically unsaturated groups. "Crosslinker" refers to a crosslinker having a molecular weight of about 700 Daltons or less.

[0026] As used herein, the term "polymer" refers to a material formed by polymerizing / crosslinking one or more monomers or macromers or prepolymers.

[0027] As used herein, the term "molecular weight" of a polymeric material (including monomeric or macromeric materials) refers to the weight average molecular weight, unless specifically indicated otherwise or the test conditions indicate otherwise.

[0028] As used herein, unless specifically indicated otherwise, the term "amino group" refers to a group of the formula -NHR', where R' is hydrogen or C1-C 20 The term "amino group" refers to a primary or secondary amino group represented by the formula:

[0029] As used herein, the term "epichlorohydrin-functionalized polyamine" or "epichlorohydrin-functionalized polyamidoamine" refers to a polymer obtained by reacting a polyamine or polyamidoamine with epichlorohydrin to convert all or a significant percentage of the amine groups of the polyamine or polyamidoamine to azetidinium groups.

[0030] As used herein, the term "azetidinium group" means [ka] It refers to a positively charged group represented by the formula:

[0031] As used herein, the term "thermally crosslinkable" means, with respect to a polymeric material or functional group, that a crosslinking (or coupling) reaction of the polymeric material or functional group with another material or functional group can be carried out at relatively high temperatures (about 40°C to about 140°C), whereas the same crosslinking (or coupling) reaction of the polymeric material or functional group with another material or functional group cannot be carried out (to a detectable extent (i.e., greater than about 5%) over about an hour) at room temperature (i.e., about 22°C to about 28°C, preferably about 24°C to about 26°C, in particular about 25°C).

[0032] As used herein, the term "phosphorylcholine" refers to [ka] (wherein n is an integer from 1 to 5, and R1, R2 and R3 are each independently C1-C8 alkyl or C1-C8 hydroxyalkyl). It refers to a zwitterionic group represented by the formula:

[0033] As used herein, the term "reactive vinyl monomer" refers to a vinyl monomer that has a carboxyl group or an amino group (ie, a primary or secondary amino group).

[0034] As used herein, the term "non-reactive hydrophilic vinyl monomer" refers to a hydrophilic vinyl monomer that does not contain any carboxyl or amino groups (i.e., primary or secondary amino groups). The non-reactive vinyl monomer may contain tertiary or quaternary amino groups.

[0035] As used herein, the term "water soluble," with respect to a polymer, means that the polymer can be dissolved in water at room temperature (as defined above) to a sufficient extent to produce an aqueous solution of the polymer having a concentration of up to about 30% (by weight).

[0036] As used herein, the term "water contact angle" refers to an average water contact angle (ie, a contact angle measured by the sessile drop method), obtained by averaging contact angle measurements.

[0037] As used herein, the term "intact" is intended to refer to the extent to which a contact lens can be stained by Sudan Black in the Sudan Black staining test described in Example 1, with respect to a coating on a SiHy contact lens. Good integrity of a coating on a SiHy contact lens means that the contact lens is not substantially stained by Sudan Black.

[0038] As used herein, the term "durable," with respect to a coating on a SiHy contact lens, is intended to refer to the ability of the coating on the SiHy contact lens to survive a digital rub test.

[0039] As used herein, the term "survives a digital rub test" or "survives a durability test" means, with respect to a coating on a contact lens, that after rubbing the lens with a finger according to the procedure described in Example 1, the water contact angle of the finger-rubbed lens remains about 100 degrees or less, preferably about 90 degrees or less, more preferably about 80 degrees or less, and most preferably about 70 degrees or less.

[0040] The intrinsic "oxygen permeability" Dk of a material is the rate at which oxygen permeates the material. As used herein, the term "oxygen permeability (Dk)" refers to the measured oxygen permeability (Dk) of a hydrogel (silicone or non-silicone) or contact lens, corrected for the surface resistance to oxygen flux caused by boundary layer effects according to the procedure set forth in the Examples hereinafter. Oxygen permeability is conventionally expressed in units of barrers, where a "barrer" is [(oxygen cm 3 )(mm) / (cm 2 )(sec)(mmHg)]×10 -10 It is defined as:

[0041] The "oxygen transmissibility" of a lens or material, Dk / t, is the rate at which oxygen permeates a particular lens or material having an average thickness t [in mm] over the area being measured. Oxygen transmissibility is conventionally expressed in barrer / mm, where "barrer / mm" is the unit of [(oxygen cm 3 ) / (cm 2 )(sec)(mmHg)]×10 -9 It is defined as:

[0042] The "ion permeability" through the lens correlates with the ionoflux diffusion coefficient. The ionoflux diffusion coefficient D ([mm 2 The time (in [min]) is determined by applying Fick's law as follows: D = -n' / (A × dc / dx) (where n' = rate of ion transport [mol / min]; A = exposed lens area [mm 2 ];dc=concentration difference [mol / L];dx=lens thickness [mm])

[0043] As used herein, the term "ophthalmologically compatible" refers to a material or surface of a material that can be in intimate contact with the intraocular environment for extended periods of time without causing significant damage to the intraocular environment and without causing severe discomfort to the user.

[0044] As used herein, the term "ophthalmically safe" is intended to mean, with respect to a packaging solution for sterilizing and storing contact lenses, that a contact lens stored in the solution is safe when placed directly on the eye without rinsing after autoclaving, and that the solution is safe and sufficiently comfortable for daily contact with the eye through a contact lens. An ophthalmically safe packaging solution after autoclaving has an osmolality and pH that is compatible with the eye, and is substantially free of materials that are irritating or cytotoxic to the eye according to international ISO standards and U.S. FDA regulations.

[0045] As used herein, the term "cross section" of a SiHy contact lens refers to a lens cross section obtained by cutting the lens with a knife or cutting tool at an angle substantially perpendicular to the anterior or posterior surface of the lens. Those skilled in the art are familiar with cutting contact lenses manually (i.e., by hand) or with a Cryosta Microtome or lath to obtain a cross section of a contact lens. The resulting cross section of the contact lens can be polished using ion etching or similar techniques.

[0046] The terms "surface modulus", "surface flexibility", "surface elastic modulus", "surface Young's modulus" or "surface compressibility modulus" are used interchangeably herein and refer to nanomechanical (elastic) properties measured by atomic force microscopy (AFM) using contact mode, nanoindentation, Peakforce QNM or Harmonic Force techniques on the surface of a material or cross-section of a contact lens in a fully hydrated state (in phosphate buffer, pH ~ 7.3 ± 0.2). Jan Domke and Manfred Radmacher reported that the elastic properties of thin layers can be measured by AFM (Langmuir 1998, 14, 3320-3325, incorporated herein by reference in its entirety). AFM nanoindentation can be performed according to the experimental procedure described by Gonzalez-Meijome JM, Almeida JB and Parafita MA in Microscopy: Science, Technology, Applications and Education, "Analysis of Surface Mechanical Properties of Unworn and Worn Silicone Hydrogel Contact Lenses Using Nanoindentation with AFM", pp554-559, A. Mendez-Vilas and J. Diaz (Eds.), Formatex Research Center, Badajoz, Spain (2010), which is incorporated herein by reference in its entirety. It should be noted that the cross-sectional surface of the contact lens (performed by Gonzalez-Meijome JM, Almeida JB and Parafita MA in these papers) is analyzed using nanoindentation with AFM, rather than the front or back surface of the contact lens.Nanoindentation, Peakforce QNM and Harmonic Force methods are described in an article by Kim Sweers, et al. in Nanoscale Research Letters 2011, 6:270, entitled "Nanomechanical properties of a-synuclein amyloid fibrils: a comparative study by nanoindentation, harmonic force microscopy, and Peakforce QNM", which is incorporated herein by reference in its entirety. It should also be understood that when surface modulus measurements are performed using AFM from the anterior to the bulk or from the bulk to the posterior surface (or vice versa) of a cross-section of a fully hydrated SiHy contact lens, the surface modulus profile across the cross-section of the contact lens can be determined along the shortest line between the anterior and posterior surfaces of the cross-section of the contact lens. It should also be understood that, as a good approximation, any experimentally and directly measured quantity can be used to represent the surface modulus to the extent that the measured quantity is proportional to the surface modulus.

[0047] As used herein, the term "anterior outer hydrogel layer" refers to a hydrogel layer that includes the anterior surface of the contact lens, is of substantially uniform thickness (i.e., the thickness varies by no more than about 10% of the average thickness of the layer), and has an average thickness of at least about 0.1 μm. The "average thickness" of the anterior outer hydrogel layer is also referred to herein simply as the "thickness of the anterior outer hydrogel layer."

[0048] As used herein, the term "posterior outer hydrogel layer" refers to a hydrogel layer that includes the posterior surface of a SiHy contact lens of the present invention, is of substantially uniform thickness (i.e., the thickness varies by no more than about 10% of the average thickness of the layer), and has an average thickness of at least about 0.1 μm. The "average thickness" of the posterior outer hydrogel layer is also referred to herein simply as the "thickness of the posterior outer hydrogel layer."

[0049] As used herein, the term "inner layer," in reference to the SiHy contact lenses of the present invention, means a layer that includes the central curved surface (which divides the contact lens into two portions, one containing the anterior surface and the other containing the posterior surface) and that has a variable thickness.

[0050] As used herein, the terms "crosslinked coating" or "hydrogel coating" are used interchangeably to refer to a crosslinked polymeric material having a three-dimensional network structure that can contain water when fully hydrated. The three-dimensional network structure of the crosslinked polymeric material can be formed through crosslinking links by crosslinking two or more linear or branched polymers.

[0051] As used herein, the term "water swelling ratio" refers to the anterior or posterior outer hydrogel layer of the hydrogel material of the SiHy contact lens of the present invention, where WSR=L Wet / L Dry × 100%, where WSR is the water swelling ratio of one of the front and rear outer hydrogel layers, and L Wet is the average thickness of the outer hydrogel layer of a SiHy contact lens in a fully hydrated state (i.e., in phosphate buffer, pH 7.3 ± 0.2) as measured by AFM on a cross-section of the SiHy contact lens, and L Dry is the average thickness of the outer hydrogel layer of the SiHy contact lens in a dry state (dried without preserving the porosity of the hydrogel material, e.g., vacuum dried) when a cross section of the SiHy contact lens in a substantially dry atmosphere is measured by AFM). The water swelling rate of each outer hydrogel layer (of the SiHy contact lens of the present invention) is proportional to the water content of each outer hydrogel layer, and is at least about 100% or

number

[0052] As used herein, the term "reduced surface modulus" refers to either or both of the anterior and posterior outer hydrogel layers of the present SiHy contact lenses, as defined by the following formula:

number

number

number

number

[0053] "Critical coefficient of friction" is the tangent of the critical angle, which is the maximum inclination angle of the inclined surface at which the lens begins to slide on the inclined surface after being pressed, but takes more than 10 seconds before stopping or reaching the edge. The procedure for determining the critical coefficient of friction (CCOF) is described in Example 29. It is believed that the critical coefficient of friction (CCOF) of a contact lens correlates with the surface lubricity of the contact lens and can be used to quantify the surface lubricity of the contact lens.

[0054] As used herein, the "positively charged particle adhesion test" refers to a test for characterizing the surface concentration of negatively charged groups (e.g., carboxylic acid groups) on a hydrated SiHy contact lens. The positively charged particle adhesion test is performed as follows: DOWEX™ 1×4 20-50 mesh resin (spherical type I strong basic resin (N + (CH3)3Cl -An aqueous dispersion of DOWEX™ 1×4 20-50 mesh resin (a styrene / divinylbenzene copolymer containing functional groups and 4% divinylbenzene) is prepared by dispersing a predetermined amount of DOWEX™ 1×4 20-50 mesh resin in phosphate buffered saline (pH-7.3) to have a resin concentration of 5% (by weight) and then thoroughly mixing by shaking or stirring or vortexing at about 1000 rpm for 10 seconds. A hydrated silicone hydrogel contact lens is immersed in the aqueous dispersion of DOWEX™ 1×4 20-50 mesh resin prepared above, vortexed at about 1000-1100 rpm for about 1 minute, then rinsed with DI water and vortexed in DI water for about 1 minute. The lens is then placed in water in a glass Petri dish and an image of the lens is taken using bottom illumination with a Nikon optical microscope. The number of positively charged particles attached to each lens surface can be counted. The number of positively charged particles attached to the lens surface is proportional to the surface concentration of negatively charged groups on the contact lens.

[0055] As used herein, the term "carboxylic acid content," with respect to the crosslinked coating or outer hydrogel layer of the present SiHy contact lenses, means the weight (%) of carboxylic acid groups (COOH) based on the weight of the crosslinked coating or outer hydrogel layer of the SiHy contact lens. The carboxylic acid content of the crosslinked coating or outer hydrogel layer can be theoretically estimated based on the composition of the starting materials for making the crosslinked coating or outer hydrogel layer and the carboxylic acid content of each starting material.

[0056] The present invention relates to a SiHy contact lens having a layered structure shape and a unique water gradient from the inside to the outside of the SiHy contact lens: a silicone hydrogel core (or bulk material) with a lower water content, which has a higher water content and a moderate thickness (at least about 0.1 μm) and is completely covered with an outer (surface) hydrogel layer that is substantially silicone-free (preferably completely silicone-free); and an outer hydrogel layer with a water content that is at least about 1.2 times (or 120%), preferably at least about 1.3 times (or 130%), more preferably at least about 1.4 times (or 140%), even more preferably at least about 1.5 times (150%), and most preferably at least about 2 times (or 200%) the water content of the bulk material. Figure 1 illustrates a SiHy contact lens with a layered structure shape according to a preferred embodiment. According to this preferred embodiment of the invention, the SiHy contact lens 100 has a front surface (or front curve or convex surface) 101 and an opposing back surface (or base curve or concave surface) 102 that rests on the cornea of ​​the eye when worn by a user. The SiHy contact lens 100 includes an inner (or middle) layer 110 and two outer layers 120. The inner layer 110 is the bulk material of the SiHy contact lens 100 and has a three-dimensional shape that is in close proximity to the SiHy contact lens 100. The inner layer 110 is preferably made of a silicone hydrogel with a lower water content. The two outer layers 120, which are substantially identical, are of substantially uniform thickness and made of a substantially silicone-free (preferably completely silicone-free) hydrogel material with a higher water content relative to that of the inner layer 110. The two outer layers 120 are fused at the peripheral edge 103 of the contact lens 100 and completely cover the inner layer 110.

[0057] The SiHy contact lenses having the layered structure shape of the present invention can provide several advantages over conventional contact lenses. First, such SiHy contact lenses can still have high oxygen permeability necessary to maintain the health of the cornea of ​​the eye. Second, since the inner layer (bulk material) provides the bulk mechanical strength and rigidity required for the contact lens, the outer hydrogel layer can contain as much water as possible without being limited in terms of water content. Therefore, the outer hydrogel layer can provide a water-rich film or contact lens with a water content gradient (highest water content in the area near and including the lens surface and lowest water content in the lens nucleus) in the lens structure shape. Third, the SiHy contact lenses having the layered structure shape of the present invention can have low intraocular dehydration, resulting in a less dry feeling to the eye, and as a result, improved all-day wearing comfort. It is believed that the inner layer (i.e., the bulk material of the lens) having a low water content controls (limits) the diffusion rate of water from the posterior surface of the lens through to the anterior surface, and evaporation (water loss) at the anterior surface of the lens. Also, the layered structure shape of the present invention may create an internal water concentration gradient (i.e., water content decreases moving inward from the anterior surface to the lens nucleus), which is believed to be unfavorable to water diffusion from the posterior surface to the anterior surface of the lens according to Fick's law of diffusion. Fourth, the SiHy contact lens having the layered structure shape of the present invention can provide high biocompatibility because water is highly biocompatible with tears, and because the high water content (e.g., preferably >75% H2O) in the outer hydrogel layer is located in and near the anterior and posterior surfaces where the eye comes into direct contact and biocompatibility is maximized. Fifth, the high water content in the outer hydrogel layer with a moderate thickness can provide the SiHy contact lens with a highly flexible surface, i.e., a "water cushion". Sixth, the SiHy contact lens having the layered structure shape of the present invention can have a highly lubricating surface. It is believed that the outer hydrogel layer with a very high water content and moderate thickness will provide a "water-loving" surface that can attract tears that spread over the lens surface.The outer hydrogel layer, which has a much higher flexibility than the bulk lens material (inner layer), is highly deformable under pressure (i.e., shear force of the eyelid), and it is believed that such SiHy contact lenses can provide elastohydrodynamic lubrication when worn in the eye. Seventh, the layered structure shape in the SiHy contact lenses of the present invention can prevent exposure of silicone. It is believed that the three-dimensional mesh network structure (i.e., polymer matrix) of the outer hydrogel layer with a moderate thickness can cover the silicone and prevent the silicone from migrating to the lens surface. Eighth, the SiHy contact lenses of the present invention can have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups), making them less susceptible to severe debris adhesion during patient handling and severe protein adhesion during wear (it is believed that most proteins in tears are positively charged).

[0058] In one aspect, the invention is a hydrated silicone hydrogel contact lens comprising an anterior (convex) surface and an opposite posterior (concave) surface; and a layered configuration from the anterior to posterior surfaces, the layered configuration comprising an anterior outer hydrogel layer, an inner layer of silicone hydrogel material, and a posterior outer hydrogel layer, the silicone hydrogel material having an oxygen permeability (Dk) of at least about 50, preferably at least about 60, more preferably at least about 70, even more preferably at least about 90, and most preferably at least about 110 barrer, and a first water content (WC) of about 10% to about 70%, preferably about 10% to about 65%, more preferably about 10% to about 60%, even more preferably about 15% to about 55%, and most preferably about 15% to about 50% by weight. SiHy and wherein the anterior and posterior outer hydrogel layers are of substantially uniform thickness and are fused at the peripheral edges of the contact lens to completely encapsulate the inner layer of silicone hydrogel material, and wherein the anterior and posterior outer hydrogel layers, independently of one another, have a thickness of at least about 100 nm, preferably at least about 150 nm, more preferably at least about 150 nm, most preferably at least about 150 nm. SiHyIf ≦45%, then it has a water swelling rate of at least about 100% (preferably at least about 150%, more preferably at least about 200%, even more preferably at least about 250%, and most preferably at least about 300%), or SiHy If >45%, then at least approximately

number

[0059] According to the present invention, the inner layer of the SiHy contact lens is essentially the bulk material of the lens. It can be derived directly from a preformed SiHy contact lens by a surface modification process in which two outer hydrogel layers are directly and / or indirectly applied and bonded onto the preformed SiHy contact lens. The preformed SiHy contact lens can be any commercially available SiHy lens, such as one of the lenses described above. Alternatively, the preformed SiHy can be manufactured according to any method well known to those skilled in the art. For example, the preformed contact lens can be manufactured by conventional "spin cast molding" as described, for example, in U.S. Pat. No. 3,408,429, or by a static full cast molding process as described in U.S. Pat. Nos. 4,347,198; 5,508,317; 5,583,463; 5,789,464; and 5,849,810, or by lathe cutting of the silicone hydrogel bottom used in the manufacture of customized contact lenses. In cast molding, the lens formulation is typically dispensed into a mold for producing a contact lens and cured (i.e., polymerized and / or crosslinked) in the mold. SiHy lens formulations for producing preformed SiHy contact lenses, for cast molding or spin casting, or for producing SiHy rods used in lathe cutting of contact lenses, generally contain at least one component selected from the group consisting of silicone-containing vinyl monomers, silicone-containing vinyl macromers, silicone-containing prepolymers, hydrophilic vinyl monomers, hydrophobic vinyl monomers, crosslinkers (compounds having a molecular weight of about 700 Daltons or less and containing at least two ethylenically unsaturated groups), free radical initiators (photoinitiators or thermal initiators), hydrophilic vinyl macromers / prepolymers, and combinations thereof, as is well known to those skilled in the art.The SiHy contact lens formulation may also include other necessary ingredients known to those skilled in the art, such as UV absorbers, visibility colorants (e.g., dyes, pigments, or mixtures thereof), antimicrobial agents (e.g., preferably silver nanoparticles), bioactive agents, leachable lubricants, leachable tear-stabilizing agents, and mixtures thereof. The resulting preformed SiHy contact lens may then be subjected to an extraction and hydration process using an extraction solvent to remove non-polymerized components from the resulting lens, as known to those skilled in the art. The preformed SiHy contact lens may also be a tinted contact lens (i.e., a SiHy contact lens having at least one color pattern printed thereon, as is well known to those skilled in the art).

[0060] Any suitable silicone-containing vinyl monomer can be used in the present invention.Examples of preferred silicone-containing vinyl monomers include N-[tris(trimethylsiloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylpropylsiloxy)-silylpropyl]-(meth)acrylamide, N-[tris(dimethylphenylsiloxy)silylpropyl]-(meth)acrylamide, N-[tris(dimethylethylsiloxy)silylpropyl]-(meth)acrylamide, N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy) N-(2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl)acrylamide;N,N-Bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl]-2-methylacrylamide;N,N-Bis[2-hydroxy-3-(3-(bis(trimethylsilyloxy)methylsilyl)propyloxy)propyl]acrylamide;N-(2-hydroxy-3-(3-( N-(2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl)acrylamide;N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl]-2-methylacrylamide;N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl]acrylamide;N,N-bis[2-hydroxy-3-(3-(tris(trimethylsilyloxy)silyl)propyloxy)propyl]acrylamide N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide;N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide;N,N-bis[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide;N,N-bis[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide;N,N-bis[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide;3-Methacryloxypropyl pentamethyldisiloxane, tris(trimethylsilyloxy)silylpropyl methacrylate (TRIS), (3-methacryloxy-2-hydroxypropyloxy)propyl bis(trimethylsiloxy)methylsilane), (3-methacryloxy-2-hydroxypropyloxy)propyl tris(trimethylsiloxy)silane, 3-methacryloxy-2-(2-hydroxyethoxy)propyloxy)propyl bis(trimethylsiloxy)methylsilane, N-2-methacryloxyethyl-O-(methyl-bis-trimethylsiloxy-3-propyl)silane The most preferred siloxane-containing (meth)acrylamide monomers of formula (1) include, but are not limited to, N-[tris(trimethylsiloxy)silylpropyl]acrylamide, TRIS, N-[2-hydroxy-3-(3-(t-butyldimethylsilyl)propyloxy)propyl]acrylamide or combinations thereof;

[0061] A preferred class of silicone-containing vinyl monomers or macromers are polysiloxane-containing vinyl monomers or macromers. Examples of such polysiloxane-containing vinyl monomers or macromers include monomethacrylate or monoacrylate polydimethylsiloxanes of various molecular weights (e.g., mono-3-methacryloxypropyl terminated, mono-butyl terminated polydimethylsiloxanes or mono-(3-methacryloxy-2-hydroxypropyloxy)propyl terminated, mono-butyl terminated polydimethylsiloxanes); dimethacrylate or diacrylate polydimethylsiloxanes of various molecular weights; vinyl carbonate terminated polydimethylsiloxanes; vinyl carbamate terminated polydimethylsiloxanes; vinyl terminated polydimethylsiloxanes of various molecular weights; methacrylamide terminated polydimethylsiloxanes; acrylamide terminated polydimethylsiloxanes; acrylate terminated polydimethylsiloxanes; methacryl ... dimethylsiloxane; methacrylate terminated polydimethylsiloxane; bis-3-methacryloxy-2-hydroxypropyloxypropyl polydimethylsiloxane; N,N,N',N'-tetrakis(3-methacryloxy-2-hydroxypropyl)-α,ω-bis-3-aminopropyl-polydimethylsiloxane; polysiloxanylalkyl(meth)acrylic monomers; siloxane-containing macromers selected from the group consisting of Macromer A, Macromer B, Macromer C, and Macromer D described in U.S. Pat. No. 5,760,100, which is incorporated herein by reference in its entirety; reaction products of glycidyl methacrylate and amino-functionalized polydimethylsiloxane; hydroxyl-functionalized siloxane-containing vinyl monomers or macromers;U.S. Patent Nos. 4,136,250, 4,153,641, 4,182,822, 4,189,546, 4,343,927, 4,254,248, 4,355,147, 4,276,402, 4,327,203, 4,341,889, 4,486,577, No. 4,543,398, No. 4,605,712, No. 4,661,575, No. 4,684,538, No. 4,703,097, No. 4,833,218 No. 4,837,289, No. 4,954,586, No. 4,954,587, No. 5,010,141, No. 5,034,461, No. 5,070, 170, 5,079,319, 5,039,761, 5,346,946, 5,358,995, 5,387,632, 5,416,132, 5,451,617, 5,486,579, 5,962,548, 5,981,675, 6,039,913 and 6,762,264, each of which is incorporated by reference in its entirety; and polysiloxane-containing macromers disclosed in U.S. Pat. Nos. 4,259,467, 4,260,725 and 4,261,875, each of which is incorporated by reference in its entirety. Di- and tri-block macromers of polydimethylsiloxane and polyalkylene oxide may also be used. For example, polyethylene oxide-block-polydimethylsiloxane-block-polyethylene oxide end-capped with methacrylate may be used to improve oxygen permeability. Suitable mono-functionalized hydroxyl-functionalized siloxane-containing vinyl monomers / macromers and suitable multi-functionalized hydroxyl-functionalized siloxane-containing vinyl monomers / macromers are commercially available from Gelest, Inc, Morrisville, PA;

[0062] Another class of preferred silicone-containing macromers are silicon-containing prepolymers that contain hydrophilic and hydrophobic segments. Any suitable silicone-containing prepolymer having hydrophilic and hydrophobic segments can be used in the present invention. Examples of such silicone-containing prepolymers include those described in commonly owned U.S. Patent Nos. 6,039,913, 7,091,283, 7,268,189, and 7,238,750, 7,521,519; commonly owned U.S. Patent Application Publication Nos. US 2008-0015315 A1, US 2008-0143958 A1, US 2008-0143003 A1, US 2008-0234457 A1, US 2008-0231798 A1, and commonly owned U.S. Patent Application Nos. 61 / 180,449 and 61 / 180,453, all of which are incorporated herein by reference in their entirety.

[0063] Examples of preferred hydrophilic vinyl monomers are N,N-dimethylacrylamide (DMA), N,N-dimethylmethacrylamide (DMMA), 2-acrylamidoglycolic acid, 3-acryloylamino-1-propanol, N-hydroxyethylacrylamide, N-[tris(hydroxymethyl)methyl]-acrylamide, N-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methyl ... -methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 1-n-propyl-3-methylene-2-pyrrolidone, 1-n-propyl-5-methylene-2-pyrrolidone, 1-isopropyl-3-methylene-2-pyrrolidone, 1-isopropyl-5-methylene-2-pyrrolidone, 1-n-butyl-3-methylene-2-pyrrolidone, 1-tert-butyl-3-methylene-2-pyrrolidone, 2-hydroxyethyl methacrylate (HEMA), 2-hydroxyethyl acrylate (HEA), hydroxypropyl acrylate, hydroxypropyl methacrylate (HPMA), 2-hydroxypropyl methacrylate trimethylammonium hydrochloride, aminopropyl methacrylate hydrochloride, dimethylaminoethyl methacrylate (DMAEMA), glycerol methacrylate (GMA), N-vinyl-2-pyrrolidone (NVP), allyl alcohol, vinylpyridine, C1-C4-alkoxy polyethylene glycol (meth)acrylates having a weight average molecular weight of up to 1500, methacrylic acid, N-vinyl formamide, N-vinyl acetamide, N-vinyl isopropylamide, N-vinyl-N-methyl acetamide, allyl alcohol, N-vinyl caprolactam and mixtures thereof.

[0064] Examples of preferred hydrophobic vinyl monomers include methyl acrylate, ethyl acrylate, propyl acrylate, isopropyl acrylate, cyclohexyl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, propyl methacrylate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl valerate, styrene, chloroprene, vinyl chloride, vinylidene chloride, acrylonitrile, 1-butene, butadiene, methacrylonitrile, vinyl toluene, vinyl ethyl ether, perfluorohexylethyl-thio-carbonyl-aminoethyl-methacrylate, isobornyl methacrylate, trifluoroethyl methacrylate, hexafluoro-isopropyl methacrylate, hexafluorobutyl methacrylate.

[0065] Examples of preferred crosslinking agents include tetraethylene glycol diacrylate, triethylene glycol diacrylate, ethylene glycol diacrylate, diethylene glycol diacrylate, tetraethylene glycol dimethacrylate, triethylene glycol dimethacrylate, ethylene glycol dimethacrylate, diethylene glycol dimethacrylate, trimethylopropane trimethacrylate, pentaerythritol tetramethacrylate, bisphenol A dimethacrylate, vinyl methacrylate, ethylenediamine dimethylacrylamide, ethylenediamine diacrylamide, glycerol dimethacrylate, triallyl isocyanurate, triallyl cyanurate, allyl methacrylate, allyl methacrylate, 1,3-bis(methacrylamidopropyl)- These include, but are not limited to, 1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, N,N'-methylenebisacrylamide, N,N'-methylenebismethacrylamide, N,N'-ethylenebisacrylamide, N,N'-ethylenebismethacrylamide, 1,3-bis(N-methacrylamidopropyl)-1,1,3,3-tetrakis-(trimethylsiloxy)disiloxane, 1,3-bis(methacrylamidobutyl)-1,1,3,3-tetrakis(trimethylsiloxy)-disiloxane, 1,3-bis(acrylamidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, 1,3-bis(methacryloxyethylureidopropyl)-1,1,3,3-tetrakis(trimethylsiloxy)disiloxane, and combinations thereof. Preferred crosslinking agents are tetra(ethylene glycol) diacrylate, tri(ethylene glycol) diacrylate, ethylene glycol diacrylate, di(ethylene glycol) diacrylate, methylene bisacrylamide, triallyl isocyanurate, or triallyl cyanurate. The amount of crosslinking agent used is expressed as a weight content based on the total polymer, and is preferably in the range of about 0.05% to about 4%, more preferably in the range of about 0.1% to about 2%.

[0066] Examples of suitable thermal initiators include, but are not limited to, 2,2'-azobis(2,4-dimethylpentanenitrile), 2,2'-azobis(2-methylpropanenitrile), 2,2'-azobis(2-methylbutanenitrile), peroxides such as benzoyl peroxide, etc. Preferably, the thermal initiator is 2,2'-azobis(isobutyronitrile) (AIBN).

[0067] Suitable photoinitiators are benzoin methyl ether, diethoxyacetophenone, benzoylphosphine oxide, 1-hydroxycyclohexylphenyl ketone and Darocur and Irgacur types, preferably Darocur 1173® and Darocur 2959®. Examples of benzoylphosphine oxide initiators include 2,4,6-trimethylbenzoyldiphenylphosphine oxide; bis-(2,6-dichlorobenzoyl)-4-N-propylphenylphosphine oxide; and bis-(2,6-dichlorobenzoyl)-4-N-butylphenylphosphine oxide. Reactive photoinitiators are also suitable, which can be incorporated into macromers or used as special monomers, for example. Examples of reactive photoinitiators are those disclosed in European Patent Application No. 632 329, which is incorporated herein by reference in its entirety. Polymerization can then be initiated by actinic radiation, for example light, in particular UV light of a suitable wavelength. If appropriate, the spectral requirements can be controlled by adding a suitable photosensitizer.

[0068] Any suitable polymerizable UV absorber can be used in the present invention. Preferably, the polymerizable UV absorber comprises a benzotriazole moiety or a benzophenone moiety. Examples of preferred polymerizable UV absorbers include 2-(2-hydroxy-5-vinylphenyl)-2H-benzotriazole, 2-(2-hydroxy-5-acrylyloxyphenyl)-2H-benzotriazole, 2-(2-hydroxy-3-methacrylamidomethyl-5-tertoctylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacrylamidophenyl)-5-methoxybenzotriazole, 2-(2'-hydroxy-5'-methyl ... These include, but are not limited to, 2-(2'-hydroxy-5'-methacryloxypropyl-3'-t-butyl-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-5'-methacryloxyethylphenyl)benzotriazole, 2-(2'-hydroxy-5'-methacryloxypropylphenyl)benzotriazole, 2-hydroxy-4-acryloxyalkoxybenzophenone, 2-hydroxy-4-methacryloxyalkoxybenzophenone, allyl-2-hydroxybenzophenone, 2-hydroxy-4-methacryloxybenzophenone.

[0069] A bioactive agent is any compound that can prevent eye disease and reduce the symptoms of eye disease. A bioactive agent can be a drug, an amino acid (e.g., taurine, glycine, etc.), a polypeptide, a protein, a nucleic acid, or a combination thereof. Examples of drugs useful herein include, but are not limited to, rebamipide, ketotifen, olaptidine, cromoglycolate, cyclosporine, nedocromil, levocabastine, lodoxamide, ketotifen, or a pharma- ceutically acceptable salt or ester thereof. Other examples of bioactive agents include 2-pyrrolidone-5-carboxylic acid (PCA), alpha-hydroxyl acids (e.g., glycolic acid, lactic acid, malic acid, tartaric acid, mandelic acid, and citric acid and salts thereof), linoleic acid and gamma-linoleic acid, and vitamins (e.g., B5, A, B6, etc.).

[0070] Examples of leachable lubricants include, but are not limited to, mucin-like materials (e.g., polyglycolic acid) and non-crosslinkable hydrophilic polymers (i.e., not containing ethylenically unsaturated groups). Any hydrophilic polymer or copolymer that does not contain any ethylenically unsaturated groups can be used as a leachable lubricant. Preferred examples of non-crosslinkable hydrophilic polymers include, but are not limited to, polyvinyl alcohol (PVA), polyamides, polyimides, polylactones, homopolymers of vinyl lactams, copolymers of at least one vinyl lactam with or without one or more hydrophilic vinyl comonomers, homopolymers of acrylamide or methacrylamide, copolymers of acrylamide or methacrylamide with one or more hydrophilic vinyl monomers, polyethylene oxide (i.e., polyethylene glycol (PEG)), polyoxyethylene derivatives, poly-NN-dimethylacrylamide, polyacrylic acid, poly-2-ethyloxazoline, heparin polysaccharides, polysaccharides, and mixtures thereof. The weight average molecular weight M of the non-crosslinkable hydrophilic polymers is preferably 0.1 to 0.5% by weight. w is preferably 5,000 to 1,00,000.

[0071] Examples of the leaky tear stabilizer include, but are not limited to, phospholipids, monoglycerides, diglycerides, triglycerides, glycolipids, glyceroglycolipids, sphingolipids, sphingoglycolipids, fatty alcohols, fatty acids, mineral oils, and mixtures thereof. Preferably, the tear stabilizer is a phospholipid, monoglyceride, diglyceride, triglyceride, glycolipid, glyceroglycolipid, sphingolipid, sphingoglycolipid, fatty acid having 8 to 36 carbon atoms, fatty alcohol having 8 to 36 carbon atoms, or mixtures thereof.

[0072] In accordance with the present invention, the SiHy lens formulation may be a solution or melt at a temperature of about 20° C. to about 85° C. Preferably, the polymerizable composition is a solution of all the desired components in a suitable solvent or mixture of suitable solvents.

[0073] SiHy lens formulations, as known to those skilled in the art, can be prepared by dissolving all of the desired components in any suitable solvent, such as water, a mixture of water and one or more organic solvents that are miscible with water, an organic solvent, or a mixture of one or more organic solvents.

[0074] Examples of preferred organic solvents include tetrahydrofuran, tripropylene glycol methyl ether, dipropylene glycol methyl ether, ethylene glycol n-butyl ether, ketones (e.g., acetone, methyl ethyl ketone, etc.), diethylene glycol n-butyl ether, diethylene glycol methyl ether, ethylene glycol phenyl ether, propylene glycol methyl ether, propylene glycol methyl ether acetate, dipropylene glycol methyl ether acetate, propylene glycol n-propyl ether, dipropylene glycol n-propyl ether, tripropylene glycol n-butyl ether, propylene glycol n-butyl ether, dipropylene glycol n-butyl ether, tripropylene glycol n-butyl ether, propylene glycol phenyl ether, and the like. ether, dipropylene glycol dimethyl ether, polyethylene glycol, polypropylene glycol, ethyl acetate, butyl acetate, amyl acetate, methyl lactate, ethyl lactate, i-propyl lactate, methylene chloride, 2-butanol, 1-propanol, 2-propanol, menthol, cyclohexanol, cyclopentanol and exonorborneol, 2-pentanol, 3-pentanol, 2-hexanol, 3-hexanol, 3-methyl-2-butanol, 2-heptanol, 2-octanol, 2-nonanol, 2-decanol, 3-octanol, norborneol, tert-butanol, tert-amyl alcohol, 2-methyl-2-pentanol, 2,3-dimethyl-2-butanol, 3-methyl-3-pentanol, 1-methylcyclohexanol, 2-methyl-2-hexanol, 3,7-Dimethyl-3-octanol, 1-chloro-2-methyl-2-propanol, 2-methyl-2-heptanol, 2-methyl-2-octanol, 2-2-methyl-2-nonanol, 2-methyl-2-decanol, 3-methyl-3-hexanol, 3-methyl-3-heptanol, 4-methyl-4-heptanol, 3-methyl-3-octanol, 4-methyl-4-octanol, 3-methyl-3-nonanol, 4-methyl-4-nonanol, 3-methyl-3-octanol, 3-ethyl-3-hexanol, 3-methyl-3-heptanol, 4-ethyl-4-heptanol, 4-propyl-4-heptanol, 4-isopropyl-4-heptanol, 2,4-dimethyl-2-pentanol, 1-methylcyclopentanol, 1-ethylcyclopentanol, 1- These include, but are not limited to, ethylcyclopentanol, 3-hydroxy-3-methyl-1-butene, 4-hydroxy-4-methyl-1-cyclopentanol, 2-phenyl-2-propanol, 2-methoxy-2-methyl-2-propanol, 2,3,4-trimethyl-3-pentanol, 3,7-dimethyl-3-octanol, 2-phenyl-2-butanol, 2-methyl-1-phenyl-2-propanol and 3-ethyl-3-pentanol, 1-ethoxy-2-propanol, 1-methyl-2-propanol, t-amyl alcohol, isopropanol, 1-methyl-2-pyrrolidone, N,N-dimethylpropionamide, dimethylformamide, dimethylacetamide, dimethylpropionamide, N-methylpyrrolidinone and mixtures thereof.

[0075] Many SiHy lens formulations have been described in numerous patents and patent applications published up to the filing date of this application. All of these can be used to the extent that they produce a SiHy material having the Dk and water content specified above in obtaining a preformed SiHy lens that will become the inner layer of the SiHy contact lens of the present invention. SiHy lens formulations for producing commercially available SiHy lenses, such as lotrafilcon A, lotrafilcon B, balafilcon A, galyfilcon A, senofilcon A, narafilcon A, narafilcon B, comfilcon A, enfilcon A, asmofilcon A, filcon II 3, etc., can also be used to produce a preformed SiHy contact lens (the inner layer of the SiHy contact lens of the present invention).

[0076] Lens molds for producing contact lenses are well known to those skilled in the art and are used, for example, in cast molding or spin casting. For example, a mold (in the case of cast molding) generally comprises at least two mold sections (or parts) or mold halves, namely, a first and a second mold half. The first mold half defines a first molding (or optical) surface, and the second mold half defines a second molding (or optical) surface. The first and second mold halves are configured to mate with each other such that a lens-forming cavity is formed between the first and second molding surfaces. The molding surface of the mold half is the cavity-forming surface of the mold and is in direct contact with the lens-forming material.

[0077] Methods of manufacturing mold parts for cast molding contact lenses are generally well known to those skilled in the art. The process of the present invention is not limited to any particular mold forming method. In fact, any method of forming a mold can be used in the present invention. The first and second mold halves can be formed by a variety of techniques, such as injection molding or lathing. Examples of suitable processes for forming mold halves are disclosed in U.S. Patent Nos. 4,444,711 (Schad); 4,460,534 (Boehm et al.); 5,843,346 (Morrill); and 5,894,002 (Boneberger et al.), which are also incorporated herein by reference.

[0078] Virtually all materials known in the art for making molds can be used to make molds for making contact lenses.For example, polymeric materials such as polyethylene, polypropylene, polystyrene, PMMA, Topas® COC grade 8007-S10 (transparent amorphous copolymer of ethylene and norbornene, Ticona GmbH of Frankfurt, Germany and Summit, New Jersey) can be used.Other materials that are UV light transparent, such as quartz glass and sapphire, can also be used.

[0079] In a preferred embodiment, a reusable mold is used to actinically cure a silicone hydrogel lens-forming composition under spatially confined actinic radiation to form a SiHy contact lens. Examples of preferred reusable molds are those disclosed in U.S. patent application Ser. Nos. 08 / 274,942 (filed Jul. 14, 1994), 10 / 732,566 (filed Oct. 10, 2003), 10 / 721,913 (filed Nov. 25, 2003) and U.S. Patent No. 6,627,124 (incorporated by reference in their entireties). Reusable molds can be made from quartz, glass, sapphire, CaF2, cyclic olefin copolymers (e.g., Topas® COC grade 8007-S10 (a transparent amorphous copolymer of ethylene and norbornene) (Ticona GmbH of Frankfurt, Germany and Summit, New Jersey), Zeonex® and Zeonor® (Zeon Chemicals LP, Louisville, KY)), polymethyl methacrylate (PMMA), polyoxymethylene (Delrin) from DuPont, Ultem® (polyetherimide) from GE Plastics, PrimoSpire®, and the like.

[0080] According to the present invention, the silicone hydrogel (bulk material) of the inner layer has an oxygen permeability of at least about 50, preferably at least about 60, more preferably at least about 70, even more preferably at least about 90 barrers, and most preferably at least about 110 barrers. The silicone hydrogel material also has a (first) water content WC of about 10% to about 70%, preferably about 10% to about 65%, more preferably about 10% to about 60%; even more preferably about 15% to about 55%, and most preferably about 15% to about 50% (by weight). SiHyThe silicone hydrogel material may further have a bulk modulus or bulk Young's modulus (hereinafter the terms "flexibility", "elastic modulus" and "Young's modulus" are used interchangeably in this application to mean bulk modulus, unless the term is modified by the word "surface") of about 0.3 MPa to about 1.8 MPa, preferably 0.4 MPa to about 1.5 MPa, more preferably about 0.5 MPa to about 1.2 MPa. The oxygen permeability, elastic modulus and water content of the inner layer of the silicone hydrogel material of the SiHy contact lens of the present invention can be determined by measuring the oxygen permeability, elastic modulus and water content of the pre-formed SiHy lens from which the inner layer is derived. It should be understood that since the outer hydrogel layer is very thin, as a reasonable approximation, the elastic modulus of the SiHy contact lens of the present invention can be considered to be the elastic modulus of the silicone hydrogel material of the inner layer. Those skilled in the art will be familiar with how to determine the elastic modulus and water content of the silicone hydrogel material of the SiHy contact lens. For example, the values ​​of elastic modulus and water content of all commercially available SiHy contact lenses are reported.

[0081] The two outer hydrogel layers of the SiHy contact lenses of the present invention are preferably crosslinked coatings applied onto a preformed SiHy contact lens that are substantially identical to one another and have the desired Dk, water content and bulk modulus.

[0082] The layered structure shape of the SiHy contact lens of the present invention can be determined by analyzing the cross-section of the SiHy contact lens in a fully hydrated state (i.e., directly in water or buffered saline) using atomic force microscopy (AFM), as described above, and is shown in the Examples. The cross-sectional surface modulus can be characterized (imaged) using AFM (e.g., force-volume mode) to visualize any change in surface modulus from the posterior side to the anterior side of the cross-section. A significant change (e.g., about 20% or more, preferably about 30% or more) observed in the surface modulus (by examining the AFM image) over a thickness of about 0.04 μm, preferably about 0.03 μm, more preferably about 0.02 μm, and even more preferably about 0.01 μm along the shortest line between the anterior and posterior surfaces over the cross-section of the SiHy contact lens in a fully hydrated state indicates a transition from one layer to a different layer. The average thickness of each outer hydrogel layer can be determined from the AFM image, as is well known to those skilled in the art.

[0083] The two outer hydrogel layers of the SiHy contact lens of the present invention are of substantially uniform thickness. They are fused at the peripheral edge of the contact lens to completely incorporate the inner layer of silicone hydrogel material. The thickness of each outer hydrogel layer is about 0.1 μm to about 20 μm, preferably about 0.25 μm to about 15 μm, even more preferably about 0.5 μm to about 12.5 μm, and most preferably about 1 μm to about 10 μm. The thickness of the outer hydrogel layer (or crosslinked coating) of the SiHy contact lens of the present invention is determined by AFM analysis of a cross section of the SiHy contact lens in a fully hydrated state, as described above. In a more preferred embodiment, the thickness of each outer hydrogel layer is preferably up to about 30% (i.e., 30% or less), preferably up to about 20% (20% or less), and more preferably up to about 10% (10% or less) of the central thickness of the SiHy contact lens in a fully hydrated state.

[0084] It should be understood that the layered structure shape of the SiHy contact lens of the present invention can also be qualitatively determined by analysis of a cross-section of a freeze-dried SiHy contact lens using a scanning electron microscope (SEM), as shown in the examples. SEM can show the different composition and / or structure of each layer of the cross-section of a freeze-dried SiHy contact lens. A significant change observed in composition (e.g., about 20% or more, preferably about 30% or more) and / or a significant (visually noticeable) change in structure (by examining the SEM image) over a thickness of about 0.04 μm, preferably about 0.03 μm, more preferably about 0.02 μm, even more preferably about 0.01 μm across the cross-section of a freeze-dried SiHy contact lens indicates a transition from one layer to a different layer. However, thickness values ​​based on SEM analysis of a cross-section of a freeze-dried SiHy lens are typically lower than the actual values ​​due to the collapse of the outer hydrogel layer, the transition layer, if any, and the inner layer after freeze-drying.

[0085] According to this aspect of the invention, the two outer hydrogel layers (anterior and posterior outer hydrogel layers) of the SiHy contact lenses of the present invention are made of a silicone hydrogel material having a (first) water content (WC SiHy ), more specifically, the (first) water content (WC SiHy ) (i.e., 120%). It is believed that the water swelling rate of each outer hydrogel layer correlates with its water content and, as a good approximation, can adequately represent the water content of the outer hydrogel layer. In another preferred embodiment, the water content (WC) of the inner layer of the silicone hydrogel material is 1.2 times (i.e., 120%). SiHy ) is about 55% or less, the water swelling ratio of each outer hydrogel layer is at least about 150%; and the water content (WC SiHy ) about 60% or less, the water swelling ratio of each outer hydrogel layer is at least about 200%; and the water content (WC SiHy) is about 65% or less, the water swelling rate of each outer hydrogel layer is at least about 250%; and the water content (WC SiHy ) is about 70% or less, each outer hydrogel layer has a water swelling rate of at least about 300%.

[0086] It should be appreciated that the water content of the anterior and posterior outer hydrogel layers (crosslinked coatings) can be determined more accurately by following the procedure described in Example 23. Alternatively, the water content of the two outer hydrogel layers (crosslinked coatings) can be determined using an article that includes a non-water-absorbent thin substrate and a crosslinked coating thereon, the crosslinked coating being applied on the non-water-absorbent thin substrate according to the same coating process and under substantially the same conditions as the SiHy contact lenses. The water content of each outer hydrogel layer can then be determined based on the difference between the dry weight and hydrated weight of the article with the crosslinked coating.

[0087] According to the present invention, each of the two outer hydrogel layers is substantially free of silicone, and preferably completely free of silicone.However, it is well known that when X-ray photoelectron spectroscopy (XPS) is used to determine the presence or absence of silicon in the outer hydrogel layer (typically with a 1.5-6 nm probe), the sample will inevitably be contaminated with environmental silicon, as shown by the silicon detection by XPS on the sample surface that theoretically does not contain any silicon atoms, such as polyethylene sheet, DAILIES® AquaComfortPlus® contact lens of CIBA Vision Corporation, or ACUVUE® Moist of Johnson & Johnson (see Example 21 below). Thus, the term "substantially free of silicon" is used herein to mean that the surface atomic percent silicon as measured by XPS on a SiHy contact lens is less than about 200%, preferably less than about 175%, more preferably less than about 150%, and even more preferably less than about 125% of the atomic percent silicon of a control sample known to be inherently (theoretically) free of silicon (e.g., polyethylene sheet, DAILIES® AquaComfortPlus™ contact lens from CIBA Vision Corporation, or ACUVUE® Moist from Johnson & Johnson). Alternatively, each outer hydrogel layer of the SiHy contact lenses of the present invention is substantially free of silicon as characterized by having an atomic percent silicon of about 5% or less, preferably about 4% or less, and even more preferably about 3% or less of the total elemental percent as measured by XPS analysis of the contact lens in its dry state. It should be understood that a small percentage of silicone can optionally (but preferably not) be incorporated into the polymer network of the outer hydrogel layer so long as it does not significantly degrade the surface properties (hydrophilicity, wettability and / or lubricity) of the SiHy contact lens.

[0088] In a preferred embodiment, the anterior and posterior outer hydrogel layers (crosslinked coatings) have a sufficiently low crosslink density to provide a crosslinked coating or outer hydrogel layer (i.e., SiHy contact lens) with high digital rub resistance, characterized by no visible surface crack lines under dark field after rubbing the SiHy contact lens between fingers. It is believed that surface cracking resulting from digital rubs may reduce surface lubricity and / or may not prevent silicone migration (exposure) to the surface. Surface cracking may also indicate excessive crosslink density in the surface layer, which may affect the surface modulus. Preferably, the non-silicone hydrogel material in the outer hydrogel layer (crosslinked coating) contains crosslinks derived from azetidinium groups in a heat-induced coupling reaction.

[0089] In another preferred embodiment, the anterior and posterior surfaces have a low surface concentration of negatively charged groups, such as carboxylic acid groups, characterized by attracting up to about 200, preferably up to about 160, more preferably up to about 120, even more preferably up to about 90, and most preferably up to about 60 positively charged particles in the positively charged particle adhesion test. It is desirable to have a minimum surface concentration of negatively charged groups (e.g., carboxylic acid groups) on the SiHy contact lenses of the present invention, since contact lenses with a high surface concentration of negatively charged groups (e.g., carboxylic acid groups) are prone to severe debris adhesion during patient handling, severe protein adhesion during wear (the majority of proteins in tears are believed to be positively charged), and severe deposition and accumulation of antibacterial agents such as polyhexamethylene biguanide (PHMB) present in contact lens care solutions. In order to have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups), the anterior and posterior outer hydrogel layers must have a relatively low carboxylic acid content. Preferably, the front and back outer hydrogel layers have a carboxylic acid content of about 20% (by weight) or less, preferably about 15% (by weight) or less, even more preferably about 10% (by weight) or less, and most preferably about 5% (by weight) or less.

[0090] In another preferred embodiment, the SiHy contact lenses of the present invention have good surface lubricity, characterized by a critical coefficient of friction (expressed as CCOF) of about 0.046 or less, preferably about 0.043 or less, more preferably about 0.040 or less. Alternatively, the SiHy contact lenses of the present invention preferably have better lubricity than ACUVUE OASYS or ACUVUE TruEye, as measured in a blind test according to the lubricity evaluation procedure described in Example 1.

[0091] In another preferred embodiment, the SiHy contact lens of the present invention further comprises two transition layers of polymeric material in its layered structure configuration, as illustrated diagrammatically in FIG. 2. Each of the two transition layers 115 is located between the inner layer 110 and one of the two outer hydrogel layers 120. Each transition layer is of substantially uniform thickness. The thickness of each transition layer is at least about 0.05 μm, preferably about 0.05 μm to about 10 μm, more preferably about 0.1 μm to about 7.5 μm, and even more preferably about 0.15 μm to about 5 μm. The transition layers are fused at the peripheral edge of the contact lens to completely encapsulate the inner layer of silicone hydrogel material. The presence and thickness of the transition layers can preferably be determined by AFM analysis of a cross section of the SiHy contact lens in a fully hydrated state, as described above for the outer hydrogel layer and the inner layer.

[0092] The two transition layers of the SiHy contact lenses of the present invention are essentially base (or prime) coatings that are applied over a pre-formed SiHy contact lens with the desired Dk, water content and bulk modulus before the crosslinked coating (outer hydrogel layer) is applied. The transition layer (base coating) functions to anchor / connect the outer hydrogel layer. Preferably, the transition layer is a carboxyl (COOH) containing polymer, preferably acrylic or methacrylic acid or C2-C 12The transition layer may include a homo- or copolymer of alkylacrylic acid. It should be understood that the carboxyl-containing polymer may penetrate into the bulk material and extend into the outer hydrogel layer. If such penetration into the inner layer of the silicone hydrogel material occurs, each transition layer will include a carboxyl-containing polymer and a silicone hydrogel bound together. It is also believed that the presence of the transition layer, especially when including a carboxyl-containing polymer, may provide the outer hydrogel layer with a thicker layer and / or a relatively higher water content than the water reservoir due to the high water binding properties of the carboxyl groups. Furthermore, even if the transition layer may contain many carboxylic acid groups, it will have minimal adverse effect on the surface concentration of carboxylic acid groups of the SiHy contact lens, since the surface concentration of carboxylic acid groups is determined primarily by the outer hydrogel layer, which completely covers the transition layer. The outer hydrogel layer with a low surface concentration of carboxylic acid groups may prevent deposition of positively charged proteins from the tear fluid of the patient wearing the lens.

[0093] In another preferred embodiment, the front and back outer hydrogel layers, independently of each other, have a surface modulus that is reduced relative to the inner layer by at least about 20%, preferably at least about 25%, more preferably at least about 30%, even more preferably at least about 35%, and most preferably at least about 40%.

[0094] The anterior and posterior outer hydrogel layers are preferably comprised of the same or substantially the same material (preferably completely silicone free) which may be formed by applying and crosslinking a water soluble and crosslinkable hydrophilic polymeric material onto a preformed SiHy contact lens that includes amino and / or carboxyl groups at and / or near the surface of the contact lens, or a base coating that includes amino and / or carboxyl groups, which becomes the inner layer after crosslinking.

[0095] In accordance with the present invention, preformed SiHy contact lenses naturally contain, or can be modified to contain, amino and / or carboxyl groups on and / or near their surfaces.

[0096] Where the preformed SiHy contact lenses inherently contain amino and / or carboxyl groups on and / or near their surface, this may be achieved by polymerizing a silicone hydrogel lens formulation that includes reactive vinyl monomers.

[0097] Examples of preferred reactive vinyl monomers include amino-C2-C6 alkyl(meth)acrylates, C1-C6 alkylamino-C2-C6 alkyl(meth)acrylates, allylamines, vinylamines, amino-C2-C6 alkyl(meth)acrylamides, C1-C6 alkylamino-C2-C6 alkyl(meth)acrylamides, acrylic acid, C1-C 12 Examples of suitable acrylic acids include, but are not limited to, alkyl acrylic acids (e.g., methacrylic acid, ethyl acrylic acid, propyl acrylic acid, butyl acrylic acid, pentyl acrylic acid, etc.), N,N-2-acrylamidoglycolic acid, β-methyl-acrylic acid (crotonic acid), α-phenyl acrylic acid, β-acryloyloxypropionic acid, sorbic acid, angelic acid, cinnamic acid, 1-carboxy-4-phenylbutadiene-1,3, itaconic acid, citraconic acid, mesaconic acid, glutaconic acid, aconitic acid, maleic acid, fumaric acid, tricarboxyethylene, and combinations thereof. Preferably, the SiHy contact lens is selected from the group consisting of amino-C2-C6 alkyl (meth)acrylates, C1-C6 alkylamino-C2-C6 alkyl (meth)acrylates, allylamines, vinylamines, amino-C1-C6 alkyl (meth)acrylamides, C1-C6 alkylamino-C2-C6 alkyl (meth)acrylamides, acrylic acids, C1-C6 alkylamino-C2-C6 alkyl (meth)acrylamides ... 12 The lens is prepared from a lens formulation that includes at least one reactive vinyl monomer selected from the group consisting of alkylacrylic acid, N,N-2-acrylamidoglycolic acid, and combinations thereof.

[0098] The lens formulation preferably contains from about 0.1% to about 10%, more preferably from about 0.25% to about 7%, even more preferably from about 0.5% to about 5%, and most preferably from about 0.75% to about 3% (by weight) of the reactive vinyl monomers described above.

[0099] The preformed SiHy contact lens can also be subjected to a surface treatment to form a reactive base coating having amino and / or carboxyl groups on the surface of the contact lens. Examples of surface treatment include, but are not limited to, surface treatment with energy (e.g., plasma, electrostatic, radiation or other energy sources), chemical treatment, chemical vapor deposition, grafting of hydrophilic vinyl monomers or macromers onto the surface of the article, layer-by-layer coatings ("LbL coatings") obtained according to the methods described in U.S. Patent Nos. 6,451,871, 6,719,929, 6,793,973, 6,811,805 and 6,896,926 series and U.S. Patent Application Publication Nos. 2007 / 0229758A1, 2008 / 0152800A1 and 2008 / 0226922A1, which are incorporated herein by reference in their entirety. As used herein, "LbL coating" refers to a coating that is not covalently bonded to the polymer matrix of a contact lens and is obtained via layer-by-layer ("LbL") deposition of charged or chargeable (by protonation or deprotonation) and / or uncharged materials onto the lens. LbL coatings can be composed of one or more layers.

[0100] Preferably, the surface treatment is an LbL coating process. In this preferred embodiment (i.e., reactive LbL-based coating embodiment), the resulting silicone hydrogel contact lens comprises a reactive LbL-based coating (i.e., two transition layers) that includes at least one layer of reactive polymer (i.e., a polymer with pendant amino and / or carboxyl groups), and the reactive LbL-based coating is obtained by contacting the contact lens with a solution of reactive polymer. Contacting the contact lens with the coating solution of reactive polymer can be performed by immersing the contact lens in the coating solution or spraying the coating solution onto the contact lens. One contacting process simply involves immersing the contact lens in a coating solution bath for a certain period of time, or successively immersing the contact lens in a series of coating solution baths for a shorter period of time in each bath. Another contacting process simply involves spraying the coating solution. However, a person skilled in the art can design many alternative methods that include various combinations of spraying and immersion steps. The contact time between the contact lens and the reactive polymer coating solution may be up to about 10 minutes, preferably about 5 to about 360 seconds, more preferably about 5 to about 250 seconds, and even more preferably about 5 to about 200 seconds.

[0101] According to this embodiment of reactive LbL base coating, the reactive polymer can be a linear or branched polymer with pendant amino and / or carboxyl groups. Any polymer with pendant amino and / or carboxyl groups can be used as the reactive polymer for forming the base coating on the silicone hydrogel contact lens. Examples of such reactive polymers include, but are not limited to, homopolymers of reactive vinyl monomers; copolymers of two or more reactive vinyl monomers; copolymers of reactive vinyl monomers and one or more non-reactive hydrophilic vinyl monomers (i.e., hydrophilic vinyl monomers that do not contain any carboxyl or (primary or secondary) amino groups); polyethyleneimine (PEI); polyvinyl alcohol with pendant amino groups; carboxyl-containing celluloses (e.g., carboxymethylcellulose, carboxyethylcellulose, carboxypropylcellulose); hyaluronate; chondroitin sulfate; poly(glutamic acid); poly(aspartic acid); and combinations thereof.

[0102] Any of the preferred reactive vinyl monomers described above can be used in this embodiment to form the reactive polymer for forming the reactive LbL base coating.

[0103] Preferred examples of non-reactive hydrophilic vinyl monomers that do not contain carboxyl or amino groups include acrylamide (AAm), methacrylamide, N,N-dimethylacrylamide (DMA), N,N-dimethylmethacrylamide (DMMA), N-vinylpyrrolidone (NVP), N,N-dimethylaminoethyl methacrylate (DMAEM), N,N-dimethylaminoethyl acrylate (DMAEA), N,N-dimethylaminopropyl methacrylamide (DMAPMAm), N,N-dimethylaminopropyl acrylamide (DMAPAAm), glycerol methacrylate, 3-acryloylamino-1-propanol, N-hydroxyethyl acrylamide, N-[tris(hydroxymethyl)methyl]-acrylamide, N-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5 ... pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, C1-C4-alkoxy polyethylene glycol (meth)acrylates having a weight average molecular weight of up to 1500 Daltons, N-vinyl formamide, N-vinyl acetamide, N-vinyl isopropylamide, N-vinyl-N-methyl acetamide, allyl alcohol, vinyl alcohol (hydrolyzed form of vinyl acetate in copolymers), phosphorylcholine-containing vinyl monomers (including (meth)acryloyloxyethyl phosphorylcholine and those described in U.S. Pat. No. 5,461,433, which is incorporated herein by reference in its entirety), and combinations thereof.

[0104] Preferably, the reactive polymer for forming the reactive LbL based coating is polyacrylic acid, polymethacrylic acid, poly(C2-C 12 alkylacrylic acid), poly(acrylic acid-co-methacrylic acid), poly[C2-C 12alkylacrylic acid-co-(meth)acrylic acid], poly(N,N-2-acrylamidoglycolic acid), poly[(meth)acrylic acid-co-acrylamide], poly[(meth)acrylic acid-co-vinylpyrrolidone], poly[C2-C 12 alkylacrylic acid-co-acrylamide], poly[C2-C 12 alkylacrylic acid-co-vinylpyrrolidone], hydrolyzed poly[(meth)acrylic acid-co-vinyl acetate], hydrolyzed poly[C2-C 12 alkylacrylic acid-co-vinyl acetate], polyethyleneimine (PEI), polyallylamine hydrochloride (PAH) homo- or copolymer, polyvinylamine homo- or copolymer, or combinations thereof.

[0105] The weight average molecular weight M of the reactive polymer for forming the reactive LbL based coating w is at least about 10,000 daltons, preferably at least about 50,000 daltons, and more preferably from about 100,000 daltons to 5,000,000 daltons.

[0106] The solution of reactive polymer for forming reactive LbL base coating on contact lens can be prepared by dissolving one or more reactive polymers in water, a mixture of water and one or more organic solvents miscible with water, an organic solvent, or a mixture of one or more organic solvents. Preferably, the reactive polymer is dissolved in a mixture of water and one or more organic solvents, an organic solvent, or a mixture of one or more organic solvents. It is believed that the solvent system containing at least one organic solvent can swell the preformed SiHy contact lens, thereby allowing a portion of the reactive polymer to penetrate into the preformed SiHy contact lens and increase the durability of the reactive base coating. Any organic solvent mentioned above can be used to prepare the solution of reactive polymer, as long as it can dissolve the reactive polymer.

[0107] In another preferred embodiment, a pre-formed SiHy contact lens inherently contains amino and / or carboxyl groups on and / or near its surface and is further subjected to a surface treatment to form a reactive LbL base coating having amino and / or carboxyl groups therein.

[0108] In another preferred embodiment (reactive plasma-based coating), the preformed SiHy contact lens is subjected to plasma treatment to form a covalently bonded reactive plasma-based coating on the contact lens. That is, one or more reactive vinyl monomers (any one of those previously described) are polymerized under the action of plasma generated by electrical discharge (so-called plasma-induced polymerization). The term "plasma" refers to an ionized gas, generated for example by glow discharge, which may consist of electrons in any form of ground or higher excited state, ions of any polarity, gas atoms and molecules, and photons. This is also called "low-temperature plasma".For general information on plasma polymerization and its applications, see R. Hartmann, "Plasma polymerisation": Grundlagen, Technik und Anwendung, Jahrb. Oberflachentechnik (1993) 49, pp. 283-296, Battelle-Inst. eV Frankfurt / Main Germany; H. Yasuda, "Glow Discharge Polymerisation", Journal of Polymer Science: Macromolecular Reviews, vol. 16 (1981) , pp. 199-293; H. Yasuda, "Plasma Polymerisation", Academic Press, Inc. (1985); Frank Jansen, "Plasma Deposition Processes", in "Plasma Deposited Thin Films", ed. by T. Mort and F. Jansen, CRC Press Boca Raton (19); O. Auciello et al. (ed.) "Plasma-Surface Interactions and Processing of Materials" See publ. by Kluwer Academic Publishers in NATO ASI Series; Series E: Applied Sciences, vol. 176 (1990), pp. 377-399; and N. Dilsiz and G. Akovali "Plasma Polymerization of Selected Organic Compounds", Polymer, vol. 37 (1996) pp. 333-341. Preferably, the plasma-induced polymerization is a "post-glow" plasma-induced polymerization as described in WO98028026, which is incorporated herein by reference in its entirety.In the case of "post-glow" plasma polymerization, the surface of the contact lens is first treated with a non-polymerizing plasma gas (e.g., H2, He or Ar) and then in a subsequent step, the activated surface is exposed to a vinyl monomer having an amino or carboxyl group (any of the reactive vinyl monomers mentioned above) while the plasma power is turned off. The activation leads to plasma-induced radical generation on the surface, which in a subsequent step initiates the polymerization of the vinyl monomer thereon.

[0109] According to the present invention, the water-soluble and cross-linkable hydrophilic polymeric material for forming the outer hydrogel layer (or cross-linked coating) comprises a cross-linkable group, preferably a thermally cross-linkable group, more preferably an azetidinium group. Preferably, the water-soluble and cross-linkable hydrophilic polymeric material for forming the outer hydrogel layer (or cross-linked coating) is a partially cross-linked polymeric material comprising a three-dimensional network and a cross-linkable (preferably thermally cross-linkable) group within the network, more preferably an azetidinium group. The term "partially cross-linked" means, in relation to the polymeric material, that the cross-linkable group of the starting material for producing the polymeric material is not completely consumed in the cross-linking reaction. Examples of cross-linkable groups include, but are not limited to, azetidinium groups, epoxy groups, isocyanate groups, aziridine groups, azlactone groups, and combinations thereof.

[0110] In a preferred embodiment, the water-soluble and crosslinkable hydrophilic polymeric material for forming the outer hydrogel layer (or crosslinked coating) comprises: (i) about 20% to about 95% (by weight) of a first polymer chain derived from an epichlorohydrin-functionalized polyamine or polyamidoamine; (ii) about 5% to about 80% (by weight) of a hydrophilic portion or second polymer chain derived from at least one hydrophilicity enhancing agent having at least one reactive functional group selected from the group consisting of an amino group, a carboxyl group, a thiol group, and combinations thereof, wherein the hydrophilic portion or second polymer chain is covalently linked to the first polymer chain via one or more covalent bonds formed between one azetitdinium group of the epichlorohydrin-functionalized polyamine or polyamidoamine and one amino, carboxyl, or thiol group of the hydrophilicity enhancing agent, respectively; and (iii) azetidinium groups that are part of the first polymer chain or are pendant or terminal groups covalently linked to the first polymer chain.

[0111] Such water-soluble and crosslinkable hydrophilic polymeric materials can be used to form an outer hydrogel layer (or crosslinked coating) by simply heating a preformed SiHy contact lens (having amino and / or carboxyl groups at and / or near the surface of the contact lens, or a base coating containing amino and / or carboxyl groups) in an aqueous solution in the presence of a hydrophilic polymeric material at a temperature of about 40° C. to about 140° C. for a time sufficient to covalently link the hydrophilic polymeric material to the surface of the contact lens via a covalent bond formed between one azetidinium group of the hydrophilic polymeric material and one amino and / or carboxyl group at and / or near the surface of the contact lens, respectively, thereby forming a crosslinked hydrophilic coating on the contact lens. It should be understood that any water-soluble and crosslinkable hydrophilic polymeric material containing crosslinkable groups (e.g., those described above) can be used in the present invention to form the anterior and posterior outer hydrogel layers of a SiHy contact lens.

[0112] The water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups comprises (i.e., has a composition including) about 20% to about 95%, preferably about 35% to about 90%, more preferably about 50% to about 85% (by weight) of a first polymer chain derived from an epichlorohydrin-functionalized polyamine or polyamidoamine, and about 5% to about 80%, preferably about 10% to about 65%, even more preferably about 15% to about 50% (by weight) of a hydrophilic portion or second polymer chain derived from at least one hydrophilic enhancer having at least one reactive functional group selected from the group consisting of an amino group, a carboxyl group, a thiol group, and combinations thereof. The composition of the hydrophilic polymeric material is determined by the composition of the reaction mixture used to prepare the thermally crosslinkable hydrophilic polymeric material according to the crosslinking reaction shown in Scheme I above (based on the total weight of the reactants). For example, when the reaction mixture comprises about 75% (by weight) of epichlorohydrin-functionalized polyamine or polyamidoamine and about 25% (by weight) of at least one hydrophilic enhancer (based on the total weight of the reactants), the resulting hydrophilic polymeric material comprises about 75% (by weight) of the first polymer chain derived from the epichlorohydrin-functionalized polyamine or polyamidoamine, and about 25% (by weight) of the hydrophilic portion or second polymer chain derived from the at least one hydrophilic enhancer. The azetidinium group of the thermally crosslinkable hydrophilic polymeric material is the azetidinium group (of the epichlorohydrin-functionalized polyamine or polyamidoamine) that does not participate in the crosslinking reaction to prepare the thermally crosslinkable hydrophilic polymeric material.

[0113] Epichlorohydrin-functionalized polyamines or polyamidoamines can be obtained by reacting epichlorohydrin with polyamine polymers or polymers containing primary or secondary amino groups. For example, poly(alkyleneimines) or poly(amidoamines), which are polycondensates derived from polyamines and dicarboxylic acids (e.g., adipic acid-diethylenetriamine copolymers), can be reacted with epichlorohydrin to form epichlorohydrin-functionalized polymers. Similarly, homopolymers or copolymers of aminoalkyl(meth)acrylates, mono-alkylaminoalkyl(meth)acrylates, aminoalkyl(meth)acrylamides or mono-alkylaminoalkyl(meth)acrylamides can also be reacted with epichlorohydrin to form epichlorohydrin-functionalized polyamines. The reaction conditions for epichlorohydrin functionalization of polyamine or polyamidoamine polymers are taught in EP 1465931 (incorporated herein in its entirety by reference). Preferred epichlorohydrin-functionalized polymers are polyaminoamide-epichlorohydrin (PAE) (or polyamide-polyamine-epichlorohydrin or polyamide-epichlorohydrin), such as, for example, Kymene® or Polycup® resins (epichlorohydrin-functionalized adipic acid-diethylenetriamine copolymers) from Hercules, or Polycup® or Servamine® resins from Servo / Delden.

[0114] Any suitable hydrophilicity enhancing agent can be used in the present invention so long as it contains at least one amino group, at least one carboxyl group, and / or at least one thiol group.

[0115] Preferred classes of hydrophilicity enhancers include amino-, carboxyl-, or thiol-containing monosaccharides (e.g., 3-amino-1,2-propanediol, 1-thiolglycerol, 5-keto-D-gluconic acid, galactosamine, glucosamine, galacturonic acid, gluconic acid, glucosamine acid, mannosamine, sugar acid 1,4-lactone, saccharidic acid, ketodeoxynonulosonic acid, acid), N-methyl-D-glucamine, 1-amino-1-deoxy-β-D-galactose, 1-amino-1-deoxysorbitol, 1-methylamino-1-deoxysorbitol, N-aminoethyl gluconamide; amino-, carboxyl- or thiol-containing disaccharides (e.g., chondroitin disaccharide sodium salt, di(β-D-xylopyranosyl)amine, digalacturonic acid, heparin disaccharide, hyaluronic acid disaccharide, lactobionic acid); and amino-, carboxyl- or thiol-containing oligosaccharides (e.g., carboxymethyl-β-cyclodextrin sodium salt, trigalacturonic acid); and combinations thereof.

[0116] Another preferred class of hydrophilic enhancer is a hydrophilic polymer having one or more amino, carboxyl and / or thiol groups.More preferably, the content of monomer units having amino (-NHR', where R' is as defined above), carboxyl (-COOH) and / or thiol (-SH) groups in the hydrophilic polymer as hydrophilic enhancer is less than about 40% (wt), preferably less than about 30% (wt), more preferably less than about 20% (wt), even more preferably less than about 10% (wt) based on the total weight of the hydrophilic polymer.

[0117] One preferred class of hydrophilic polymers as hydrophilic enhancers is, for example, carboxymethylcellulose (having a carboxyl content of about 40% or less, the repeating unit -[CH 10-m O5(CH2CO2H) m]- (where m is 1-3), carboxyethyl cellulose (having a carboxyl content of about 36% or less, 10-m O5(C2H4CO2H) m ]- (where m is 1-3), carboxypropyl cellulose (having a carboxyl content of about 32% or less, 10-m O5(C3H6CO2H) m ]- (where m is 1-3), hyaluronic acid (having a carboxyl content of about 11%, the repeating unit -(C 13 H 20 O9NCO2H)-based on the composition of the repeating unit -(C 12 H 18 O 13 NSCO2H)- (estimated based on the composition of the amino- or carboxyl-containing polysaccharides), or combinations thereof.

[0118] Another preferred class of hydrophilic polymers as hydrophilic enhancers include poly(ethylene glycol)s (PEG) with mono-amino, carboxyl or thiol groups (e.g., PEG-NH2, PEG-SH, PEG-COOH); H2N-PEG-NH2; HOOC-PEG-COOH; HS-PEG-SH; H2N-PEG-COOH; HOOC-PEG-SH; H2N-PEG-SH; branched PEGs with one or more amino, carboxyl or thiol groups; PEG dendrimers with one or more amino, carboxyl or thiol groups; diamino- or diamino-substituted vinyl monomers of non-reactive hydrophilic vinyl monomers. The reactive vinyl monomers include, but are not limited to, dicarboxyl-terminated homo- or copolymers; monoamino- or monocarboxyl-terminated homo- or copolymers of nonreactive hydrophilic vinyl monomers; (1) copolymers that are the polymerization product of a composition comprising up to about 60% (by weight), preferably about 0.1% to about 30%, more preferably about 0.5% to about 20%, and even more preferably about 1% to about 15% (by weight) of one or more reactive vinyl monomers, and (2) at least one nonreactive hydrophilic vinyl monomer and / or at least one phosphorylcholine-containing vinyl monomer; and combinations thereof. The reactive vinyl monomers and nonreactive hydrophilic vinyl monomers are as previously described.

[0119] More preferably, the hydrophilic polymer as hydrophilic enhancer is PEG-NH2; PEG-SH; PEG-COOH; H2N-PEG-NH2; HOOC-PEG-COOH; HS-PEG-SH; H2N-PEG-COOH; HOOC-PEG-SH; H2N-PEG-SH; branched PEG having one or more amino, carboxyl or thiol groups; PEG dendrimers having one or more amino, carboxyl or thiol groups; acrylamide (AAm), N,N-dimethylacrylamide (DMA), N-vinylpyrrolidone (NVP), N-vinyl-N-methylacetamide, glycerol (meth)acrylate, hydroxyethyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, weight average of up to 400 Daltons. (1) about 0.1% to about 30%, preferably about 0.5% to about 20%, more preferably about 1% to about 15% (by weight) of (meth)acrylic acid, C2-C4-alkoxy polyethylene glycol (meth)acrylate, vinyl alcohol, N-methyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, N,N-dimethylaminoethyl (meth)acrylate, N,N-dimethylaminopropyl (meth)acrylamide, (meth)acryloyloxyethyl phosphorylcholine, and combinations thereof; 12and (2) a copolymer that is the polymerization product of a composition comprising at least one non-reactive hydrophilic vinyl monomer selected from the group consisting of alkyl acrylic acid, vinyl amine, allyl amine, and / or amino-C2-C4 alkyl (meth)acrylate and (3) (meth)acryloyloxyethyl phosphorylcholine and / or acrylamide, N,N-dimethylacrylamide, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, glycerol (meth)acrylate, hydroxyethyl (meth)acrylate, N-hydroxyethyl (meth)acrylamide, C1-C4-alkoxy polyethylene glycol (meth)acrylate having a weight average molecular weight of up to 400 Daltons, vinyl alcohol, and combinations thereof.

[0120] Most preferably, the hydrophilicity enhancer is selected from the group consisting of PEG-NH2, PEG-SH, PEG-COOH, monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated polyvinylpyrrolidone, monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated polyacrylamide, monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated poly(DMA), monoamino- or monocarboxyl-, diamino- or dicarboxyl-terminated poly(DMA-co-NVP), monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated poly(NVP-co-N,N-dimethylaminoethyl (meth)acrylate), monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated poly(vinyl alcohol), monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated poly[(meth)acryloyloxyethyl phosphorylcholine] homopolymer or copolymer, monoamino- No-, monocarboxyl-, diamino- or dicarboxyl-terminated poly(NVP-co-vinyl alcohol); monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated poly(DMA-co-vinyl alcohol); poly[(meth)acrylic acid-co-acrylamide] having about 0.1% to about 30%, preferably about 0.5% to about 20%, more preferably about 1% to about 15% (by weight) of (meth)acrylic acid; about 0.1% to about 30%, preferably about 0.5% Poly[(meth)acrylic acid-co-NVP] having from about 0.1% to about 30%, preferably from about 0.5% to about 20%, more preferably from about 1% to about 15% (by weight) of (meth)acrylic acid; (1) (meth)acryloyloxyethyl phosphorylcholine and (2) a copolymer that is the polymerization product of a composition comprising from about 0.1% to about 30%, preferably from about 0.5% to about 20%, more preferably from about 1% to about 15% (by weight) of a carboxylic acid-containing vinyl monomer and / or an amino-containing vinyl monomer, and combinations thereof.

[0121] Functionalized PEGs and functionalized poly(PEGs) can be obtained from a variety of commercial sources, such as Polyscience and Shearwater Polymers, inc.

[0122] Monoamino-, monocarboxyl-, diamino- or dicarboxyl-terminated homo- or copolymers of one or more non-reactive hydrophilic vinyl monomers or phosphorylcholine-containing vinyl monomers can be prepared according to the procedures described in U.S. Patent No. 6,218,508 (incorporated herein in its entirety by reference). For example, to prepare diamino- or dicarboxyl-terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers, a non-reactive vinyl monomer, a chain transfer agent having an amino or carboxyl group (e.g., 2-aminoethanethiol, 2-mercaptopropinic acid, thioglycolic acid, thiolactic acid or other hydroxymercaptans, aminomercaptans or carboxyl-containing mercaptans) and optionally other vinyl monomers are copolymerized (thermally or by actinic radiation) with a reactive vinyl monomer (having an amino or carboxyl group) in the presence of a free radical initiator. Typically, the molar ratio of the chain transfer agent to all vinyl monomers other than the reactive vinyl monomer is about 1:5 to about 1:100, and the molar ratio of the chain transfer agent to the reactive vinyl monomer is 1:1. In such preparations, a chain transfer agent having an amino or carboxyl group is used to control the molecular weight of the resulting hydrophilic polymer, forming a terminal end of the hydrophilic polymer to give the hydrophilic polymer having one terminal amino or carboxyl group, while the reactive vinyl monomer gives the other terminal carboxyl or amino group to the resulting hydrophilic polymer. Similarly, to prepare monoamino- or monocarboxyl-terminated homo- or copolymers of non-reactive hydrophilic vinyl monomers, the non-reactive vinyl monomer, a chain transfer agent having an amino or carboxyl group (e.g., 2-aminoethanethiol, 2-mercaptopropionic acid, thioglycolic acid, thiolactic acid or other hydroxymercaptans, aminomercaptans or carboxyl-containing mercaptans) and optionally other vinyl monomers are copolymerized (by heat or actinic radiation) in the absence of any reactive vinyl monomer.

[0123] As used herein, copolymer of non-reactive hydrophilic vinyl monomer refers to the polymerization product of non-reactive hydrophilic vinyl monomer with one or more additional vinyl monomers. Copolymers containing non-reactive hydrophilic vinyl monomer and reactive vinyl monomer (e.g., carboxyl-containing vinyl monomer) can be prepared according to any well-known radical polymerization method or obtained from a commercial supplier. Copolymers containing methacryloyloxyethyl phosphorylcholine and carboxyl-containing vinyl monomer can be obtained from NOP Corporation (e.g., LIPIDURE®-A and AF).

[0124] The weight average molecular weight M of a hydrophilic polymer (as a hydrophilic enhancer) having at least one amino, carboxyl or thiol group w is preferably about 500 to about 1,000,000, more preferably about 1,000 to about 500,000.

[0125] In accordance with the present invention, the reaction of the hydrophilicity enhancer with the epichlorohydrin-functionalized polyamine or polyamidoamine is carried out at a temperature of about 40° C. to about 100° C. for a time sufficient to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups (about 0.3 hours to about 24 hours, preferably about 1 hour to about 12 hours, and even more preferably about 2 hours to about 8 hours).

[0126] According to the present invention, the concentration of hydrophilicity enhancing agent relative to the epichlorohydrin-functionalized polyamine or polyamidoamine should be selected so as not to render the resulting hydrophilic polymeric material water-insoluble (i.e., solubility of less than 0.005 g per 100 ml of water at room temperature) and so that no more than about 99%, preferably no more than about 98%, more preferably no more than about 97%, and even more preferably no more than about 96% of the azetidinium groups of the epichlorohydrin-functionalized polyamine or polyamidoamine are consumed.

[0127] According to the present invention, heating is preferably carried out by immersing a preformed SiHy contact lens comprising amino and / or carboxyl groups on and / or near the surface of the contact lens, or a base coating comprising amino and / or carboxyl groups, in a packaging solution (i.e., a buffered aqueous solution) comprising a water-soluble thermally crosslinkable hydrophilic polymeric material in a sealed lens package and autoclaving at a temperature of about 118° C. to about 125° C. for about 20 to 90 minutes. According to this embodiment of the present invention, the packaging solution is a buffered aqueous solution that is ophthalmically safe after autoclaving. Alternatively, heating is preferably carried out by immersing a preformed SiHy contact lens comprising a base coating and a layer of water-soluble thermally crosslinkable hydrophilic polymeric material on top of the base coating in a packaging solution (i.e., a buffered aqueous solution) in a sealed lens package and autoclaving at a temperature of about 118° C. to about 125° C. for about 20 to 90 minutes.

[0128] Lens packages (or containers) for autoclaving and storing soft contact lenses are well known to those skilled in the art. Any lens package can be used in the present invention. Preferably, the lens package is a blister package comprising a base and a cover. The cover is removably sealed to the base, and the base comprises a cavity for receiving a sterile packaging solution and a contact lens.

[0129] The lenses are packaged in individual packages, sealed, and sterilized (e.g., by autoclaving at about 120° C. or higher for at least 30 minutes) before being sold to the user. Those skilled in the art will be familiar with how to seal and sterilize lens packages.

[0130] In accordance with the present invention, the packaging solution contains at least one buffer and one or more other ingredients known to those skilled in the art, including, but not limited to, tonicity agents, surfactants, antibacterial agents, preservatives, and lubricants (or water-soluble viscosity enhancers) (e.g., cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone).

[0131] The packaging solution contains a sufficient amount of buffer to maintain the pH of the packaging solution within a desired range, for example, within a physiologically acceptable range, preferably from about 6 to about 8.5. As is known, any physiologically compatible buffer can be used. Suitable buffers as components of the contact lens care compositions of the present invention are known to those skilled in the art. Examples are boric acid, borates such as sodium borate, citric acid, citrates such as potassium citrate, bicarbonates such as sodium bicarbonate, TRIS (2-amino-2-hydroxymethyl-1,3-propanediol), Bis-Tris (bis-(2-hydroxyethyl)-imino-tris-(hydroxymethyl)-methane), bis-aminopolyols, triethanolamine, ACES (N-(2-hydroxyethyl)-2-aminoethanesulfonic acid), BES (N,N-bis(2-hydroxyethyl)-2-aminoethanesulfonic acid), HEPES (4-(2-hydroxyethyl)-1-piperazineethanesulfonic acid), MES (2-(N-morpholino)ethanesulfonic acid), Phosphine acid), MOPS (3-[N-morpholino]-propanesulfonic acid), PIPES (piperazine-N,N'-bis(2-ethanesulfonic acid), TES (N-[tris(hydroxymethyl)methyl]-2-aminoethanesulfonic acid), salts thereof, phosphate buffers such as Na2HPO4, NaH2PO4 and KH2PO4 or mixtures thereof. A preferred bis-aminopolyol is 1,3-bis(tris[hydroxymethyl]-methylamino)propane (bis-TRIS-propane). The amount of each buffer in the packaging solution is preferably 0.001% to 2%, preferably 0.01% to 1%; most preferably about 0.05% to about 0.30% (by weight).

[0132] The packaging solution has an osmolarity of about 200 to about 450 milliosmoles (mOsm), preferably about 250 to about 350 mOsm. The osmolarity of the packaging solution can be adjusted by adding organic or inorganic substances that affect the osmolarity. Suitable ophthalmically acceptable tonicity agents include, but are not limited to, sodium chloride, potassium chloride, glycerol, propylene glycol, polyols, mannitol, sorbitol, xylitol, and mixtures thereof.

[0133] The packaging solution of the present invention has a viscosity at 25°C of about 1 centipoise to about 20 centipoise, preferably about 1.2 centipoise to about 10 centipoise, and more preferably about 1.5 centipoise to about 5 centipoise.

[0134] In a preferred embodiment, the packaging solution preferably contains from about 0.01% to about 2%, more preferably from about 0.05% to about 1.5%, even more preferably from about 0.1% to about 1%, and most preferably from about 0.2% to about 0.5% (by weight) of the water-soluble and thermally crosslinkable hydrophilic polymeric material of the present invention.

[0135] The packaging solution of the present invention can contain a viscosity enhancing polymer. The viscosity enhancing polymer is preferably non-ionic. The increase in viscosity of the solution provides a film on the lens that can promote the wearing comfort of the contact lens. The viscosity enhancing component can also function to cushion the ocular surface during insertion and also helps to reduce irritation to the eye.

[0136] Preferred viscosity enhancing polymers include, but are not limited to, water-soluble cellulose ethers (e.g., methylcellulose (MC), ethylcellulose, hydroxymethylcellulose, hydroxyethylcellulose (HEC), hydroxypropylcellulose (HPC), hydroxypropylmethylcellulose (HPMC) or mixtures thereof), water-soluble polyvinyl alcohols (PVAs), high molecular weight poly(ethylene oxide) having a molecular weight of more than about 2000 (up to 10,000,000 Daltons), polyvinylpyrrolidone having a molecular weight of about 30,000 Daltons to about 1,000,000 Daltons, copolymers of N-vinylpyrrolidone and at least one dialkylaminoalkyl(meth)acrylate having 7 to 20 carbon atoms, and combinations thereof. Water-soluble cellulose ethers and copolymers of vinylpyrrolidone and dimethylaminoethyl methacrylate are the most preferred viscosity enhancing polymers. Copolymers of N-vinylpyrrolidone and dimethylaminoethyl methacrylate are commercially available, such as copolymer 845 and copolymer 937 from ISP.

[0137] The viscosity enhancing polymer is present in the packaging solution in an amount of from about 0.01% to about 5% (by weight) based on the total weight of the packaging solution, preferably from about 0.05% to about 3% (by weight), and even more preferably from about 0.1% to about 1% (by weight).

[0138] The packaging solution can further include polyethylene glycol having a molecular weight of about 1200 daltons or less, more preferably 600 daltons or less, and most preferably from about 100 to about 500 daltons.

[0139] When at least one of the crosslinking coating and packaging solutions contains a polymeric material having a polyethylene glycol segment, the packaging solution preferably contains an α-oxo-multi-acid or a salt thereof in an amount sufficient to reduce the susceptibility of the polyethylene glycol segment to oxidative degradation. A co-owned, co-pending patent application (U.S. Patent Application Publication No. 2004 / 0116564 A1, incorporated herein in its entirety) discloses that an oxo-multi-acid or a salt thereof can reduce the susceptibility of PEG-containing polymeric materials to oxidative degradation.

[0140] Exemplary α-oxo polyacids or biocompatible salts thereof include, but are not limited to, citric acid, 2-ketoglutaric acid, or malic acid or a biocompatible (preferably, ophthalmologically compatible) salt thereof. More preferably, the α-oxo polyacid is citric acid or malic acid or a biocompatible (preferably, ophthalmologically compatible) salt thereof (e.g., sodium, potassium, etc.).

[0141] According to the present invention, the packaging solution may further comprise a mucin-like substance, an ophthalmologically beneficial substance, and / or a surfactant. The exemplary mucin-like substances, the exemplary ophthalmologically beneficial substances, and the exemplary surfactants described above may be used in this embodiment.

[0142] In a preferred embodiment, the SiHy contact lenses of the present invention have a relatively long water break-up time (WBUT). WBUT is the time required for the water film to break down (de-wet) and expose the underlying lens material under visual inspection. SiHy contact lenses with a longer WBUT can maintain a water (tear) film on their surface for a relatively long time when worn on the eye. This will reduce the occurrence of dry spots during eyelid blinking and promote wearing comfort. WBUT can be measured according to the procedure described in the Examples herein below. Preferably, the SiHy contact lenses of the present invention have a surface hydrophilicity characterized by a water break-up time of at least about 10 seconds.

[0143] In a preferred embodiment, the SiHy contact lenses of the present invention have a surface wettability characterized by an average water contact angle of about 90 degrees or less, preferably about 80 degrees or less, more preferably about 70 degrees or less, even more preferably about 60 degrees or less, and most preferably about 50 degrees or less.

[0144] In preferred embodiments, SiHy contact lenses have an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, even more preferably at least about 100, and most preferably at least about 120 barrer / mm.

[0145] In this aspect of the invention, although various embodiments, including preferred embodiments, of the present invention may be described separately above, it should be understood that these may be combined and / or used together in any desired manner to arrive at different embodiments of the silicone hydrogel contact lenses of the present invention.

[0146] In another aspect, the present invention provides a hydrated silicone hydrogel contact lens. The hydrated silicone hydrogel contact lens of the present invention comprises a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface; the contact lens has an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrer / mm, and a cross-sectional surface index profile (including an anterior outer region along the shortest line between the anterior and posterior surfaces of the cross-sectional surface of the contact lens, including and adjacent the anterior surface; an inner region including and surrounding the center of the shortest line; and a posterior outer region including and adjacent the posterior surface, the anterior outer region having an average anterior surface index of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrer / mm).

number

number

number

number

[0147] In a preferred embodiment, the hydrated silicone hydrogel contact lens can have an elastic modulus (or Young's modulus) of about 0.3 MPa to about 1.8 MPa, preferably about 0.4 MPa to about 1.5 MPa, and more preferably about 0.5 MPa to about 1.2 MPa; a water content (by weight) of about 10% to about 75%, preferably about 10% to about 70%, more preferably about 15% to about 65%; even more preferably about 20% to about 60%, and most preferably about 25% to about 55%; a surface wettability characterized by having an average water contact angle of about 90 degrees or less, preferably about 80 degrees or less, more preferably about 70 degrees or less, even more preferably about 60 degrees or less, and most preferably about 50 degrees or less; a surface hydrophilicity characterized by having a WBUT of at least about 10 seconds; or a combination thereof.

[0148] In another preferred embodiment, the front and rear surfaces have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups) characterized by attracting up to about 200, preferably up to about 160, more preferably up to about 120, even more preferably up to about 90, and most preferably up to about 60 positively charged particles in a positively charged particle adhesion test. In order to have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups), the front and rear outer hydrogel layers must have a relatively low carboxylic acid content. Preferably, the front and rear outer hydrogel layers have a carboxylic acid content of about 20% (by weight) or less, preferably about 15% (by weight) or less, even more preferably about 10% (by weight) or less, and most preferably about 5% (by weight) or less.

[0149] In another preferred embodiment, the SiHy contact lenses of the present invention have good surface lubricity, characterized by a critical coefficient of friction (expressed as CCOF) of about 0.046 or less, preferably about 0.043 or less, more preferably about 0.040 or less. Alternatively, the SiHy contact lenses of the present invention preferably have better lubricity than ACUVUE OASYS or ACUVUE TruEye, as measured in a blind test according to the lubricity evaluation procedure described in Example 1.

[0150] In another preferred embodiment, the hydrated SiHy contact lenses have high digital abrasion resistance, preferably characterized by no surface crack lines visible under dark field after rubbing the SiHy contact lenses between fingers. It is believed that surface cracking resulting from digital abrasion may reduce surface lubricity and / or may not prevent silicone migration (exposure) to the surface.

[0151] In another preferred embodiment, the hydrated SiHy contact lens of the present invention comprises an inner layer of silicone hydrogel material, an anterior outer hydrogel layer and a posterior outer hydrogel layer, the anterior and posterior outer hydrogel layers being of substantially uniform thickness and fused at the peripheral edge of the contact lens to completely encapsulate the inner layer of silicone hydrogel material. It should be understood that the first and second outer regions in the cross-sectional surface index profile correspond to the two outer hydrogel layers, and the inner region corresponds to the inner layer of silicone hydrogel material. As described above for other aspects of the present invention, all of the various embodiments of the outer hydrogel layer (crosslinked coating) can be used as the outer hydrogel layer in this aspect of the present invention, either alone or in any combination. As described above for other aspects of the present invention, all of the various embodiments of the inner layer of silicone hydrogel material can be used as the inner layer of silicone hydrogel material in this aspect of the present invention, either alone or in any combination.

[0152] According to this aspect of the invention, the outer hydrogel layer is of substantially uniform thickness and has a thickness of at least about 0.1 μm, preferably about 0.1 μm to about 20 μm, more preferably about 0.25 μm to about 15 μm, even more preferably about 0.5 μm to about 12.5 μm, and most preferably about 1 μm to about 10 μm. The thickness of each outer hydrogel layer of the SiHy contact lens of the invention is determined by AFM analysis of a cross section of the SiHy contact lens in a fully hydrated state, as described above. In a more preferred embodiment, the thickness of each outer hydrogel layer is up to about 30% (i.e., 30% or less), preferably up to about 20% (20% or less), and more preferably up to about 10% (10% or less) of the central thickness of the SiHy contact lens in a fully hydrated state. Also, each of the two outer hydrogel layers is substantially silicone-free (characterized by having an atomic percent silicon of about 5% or less, preferably about 4% or less, and even more preferably about 3% or less of the total elemental percent as measured by XPS analysis of the contact lens in its dry state), and preferably completely silicone-free. It should be understood that a small percentage of silicone can optionally be incorporated (but preferably not) into the polymer network of the outer hydrogel layer, so long as it does not significantly degrade the surface properties (hydrophilicity, wettability and / or lubricity) of the SiHy contact lens.

[0153] In another preferred embodiment, the two outer hydrogel layers of the hydrated SiHy contact lenses of the present invention are hydrated with a water content (WC) of hydrated silicone hydrogel contact lenses. Lens (denoted by WC) and, more specifically, Lens It is believed that the water swelling ratio of each outer hydrogel layer can approximately represent the water content of the outer hydrogel layer, as discussed above. Lens When WC is about 45% or less, the water swelling rate of each outer hydrogel layer is preferably at least about 150%, more preferably at least about 200%, more preferably at least about 250%, and even more preferably at least about 300%. LensWhen the ratio is greater than 45%, the water swelling ratio of each outer hydrogel layer is at least about

number

number

number

number

[0154] Preferably, the SiHy contact lens further comprises a transition layer located between the silicone hydrogel material and the outer hydrogel layer. All of the various embodiments of the transition layer, as described for the previous aspects of the invention, can be used in this aspect of the invention, either alone or in any combination.

[0155] The hydrated SiHy contact lenses of the present invention can be prepared according to the methods described above. All of the various embodiments of the inner layer (i.e., silicone hydrogel material) described above can be used as the silicone hydrogel core in this aspect of the present invention, either alone or in any combination. As described for the previous aspect of the present invention, all of the various embodiments can be used in this aspect of the present invention, either alone or in any combination.

[0156] In this aspect of the invention, the various embodiments, including the preferred embodiments of the invention, may be described above separately, but it should be understood that they may be combined and / or used together in any desired manner to arrive at different embodiments of the silicone hydrogel contact lenses of the invention. As described for the previous aspects of the invention, all of the various embodiments may be used in this aspect of the invention, alone or in any combination, in any desired manner.

[0157] In a further aspect, the present invention provides a hydrated silicone hydrogel contact lens. The hydrated silicone hydrogel contact lens of the present invention comprises a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface; the contact lens has (1) an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, even more preferably at least about 110 barrer / mm, and (2) a surface lubricity characterized by a critical coefficient of friction (referred to as CCOF) of about 0.046 or less, preferably about 0.043 or less, more preferably about 0.040 or less, the anterior and posterior surfaces having a low surface concentration of negatively charged groups, such as carboxylic acid groups, characterized by attracting a maximum of about 200, preferably a maximum of about 160, more preferably a maximum of about 120, even more preferably a maximum of about 90, most preferably a maximum of about 60 positively charged particles in a positively charged particle adhesion test.

[0158] In a preferred embodiment, the hydrated silicone hydrogel contact lens has an elastic modulus (or Young's modulus) of about 0.3 MPa to about 1.8 MPa, preferably about 0.4 MPa to about 1.5 MPa, and more preferably about 0.5 MPa to about 1.2 MPa; a water content (by weight) of about 10% to about 75%, preferably about 10% to about 70%, more preferably about 15% to about 65%; even more preferably about 20% to about 60%, and most preferably about 25% to about 55%; a surface wettability characterized by having an average water contact angle of about 90 degrees or less, preferably about 80 degrees or less, more preferably about 70 degrees or less, even more preferably about 60 degrees or less, and most preferably about 50 degrees or less; a surface hydrophilicity characterized by having a WBUT of at least about 10 seconds; or a combination thereof.

[0159] In another preferred embodiment, the hydrated SiHy contact lenses have high digital abrasion resistance, preferably characterized by no surface crack lines visible under dark field after rubbing the SiHy contact lenses between fingers. It is believed that surface cracking resulting from digital abrasion may reduce surface lubricity and / or may not prevent silicone migration (exposure) to the surface.

[0160] In another preferred embodiment, the hydrated SiHy contact lens of the present invention comprises an inner layer of silicone hydrogel material, an anterior outer hydrogel layer and a posterior outer hydrogel layer, the anterior and posterior outer hydrogel layers being of substantially uniform thickness and fused at the peripheral edge of the contact lens to completely encapsulate the inner layer of silicone hydrogel material. It should be understood that the first and second outer regions in the cross-sectional surface index profile correspond to the two outer hydrogel layers, and the inner region corresponds to the inner layer of silicone hydrogel material. As described above for other aspects of the present invention, all of the various embodiments of the outer hydrogel layer (crosslinked coating) can be used as the outer hydrogel layer in this aspect of the present invention, either alone or in any combination. As described above for other aspects of the present invention, all of the various embodiments of the inner layer of silicone hydrogel material can be used as the inner layer of silicone hydrogel material in this aspect of the present invention, either alone or in any combination.

[0161] According to this aspect of the invention, the outer hydrogel layer is of substantially uniform thickness and has a thickness of at least about 0.1 μm, preferably about 0.1 μm to about 20 μm, more preferably about 0.25 μm to about 15 μm, even more preferably about 0.5 μm to about 12.5 μm, and most preferably about 1 μm to about 10 μm. The thickness of each outer hydrogel layer of the SiHy contact lens of the invention is determined by AFM analysis of a cross section of the SiHy contact lens in a fully hydrated state, as described above. In a more preferred embodiment, the thickness of each outer hydrogel layer is preferably up to about 30% (i.e., 30% or less), preferably up to about 20% (20% or less), more preferably up to about 10% (10% or less) of the central thickness of the SiHy contact lens in a fully hydrated state. Also, each of the two outer hydrogel layers is substantially silicone-free (characterized by having a silicon atomic percentage of about 5% or less, preferably about 4% or less, even more preferably about 3% or less of the total element percentage, as measured by XPS analysis of the contact lens in the dry state), and preferably completely silicone-free. It should be understood that a small percentage of silicone can be optionally incorporated (but preferably not incorporated) into the polymer network of the outer hydrogel layer, so long as it does not significantly reduce the surface properties (hydrophilicity, wettability and / or lubricity) of the SiHy contact lens. In order to have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups), the anterior and posterior outer hydrogel layers should have a relatively low carboxylic acid content. Preferably, the anterior and posterior outer hydrogel layers have a carboxylic acid content of about 20% (by weight) or less, preferably about 15% (by weight) or less, even more preferably about 10% (by weight) or less, and most preferably about 5% (by weight) or less.

[0162] In another preferred embodiment, the two outer hydrogel layers of the hydrated SiHy contact lenses of the present invention are hydrated with a water content (WC) of hydrated silicone hydrogel contact lenses. Lens WC) and more specifically, the water content of hydrated silicone hydrogel contact lenses (WC Lens) (i.e., 120%). It is believed that the water swelling ratio of each outer hydrogel layer can approximately represent the water content of the outer hydrogel layer, as discussed above. WC Lens When WC is about 45% or less, the water swelling rate of each outer hydrogel layer is preferably at least about 150%, more preferably at least about 200%, more preferably at least about 250%, and even more preferably at least about 300%. Lens When the ratio is greater than 45%, the water swelling ratio of each outer hydrogel layer is at least about

number

number

number

number

[0163] In another preferred embodiment, the front and back outer hydrogel layers, independently of each other, have a surface modulus that is reduced relative to the inner layer by at least about 20%, preferably at least about 25%, more preferably at least about 30%, even more preferably at least about 35%, and most preferably at least about 40%.

[0164] Preferably, the SiHy contact lens further comprises a transition layer located between the silicone hydrogel material and the outer hydrogel layer. All of the various embodiments of the transition layer, as described for the previous aspects of the invention, can be used in this aspect of the invention, either alone or in any combination.

[0165] The hydrated SiHy contact lenses of the present invention can be prepared according to the methods described above. All of the various embodiments of the inner layer (i.e., silicone hydrogel material) described above can be used as the silicone hydrogel core in this aspect of the present invention, either alone or in any combination. As described for the previous aspect of the present invention, all of the various embodiments can be used in this aspect of the present invention, either alone or in any combination.

[0166] In this aspect of the invention, the various embodiments, including the preferred embodiments of the invention, may be described above separately, but it should be understood that they may be combined and / or used together in any desired manner to arrive at different embodiments of the silicone hydrogel contact lenses of the invention. As described for the previous aspects of the invention, all of the various embodiments may be used in this aspect of the invention, alone or in any combination, in any desired manner.

[0167] The above disclosure will enable those skilled in the art to carry out the present invention.Various modifications, variations and combinations can be made to the various embodiments described herein.In order to allow the reader to better understand specific embodiments and their advantages, it is suggested to refer to the following examples.The present description and examples are to be considered as illustrative.

[0168] Although the various aspects and various embodiments of the present invention have been described using specific terms, devices and methods, such description is for illustrative purposes only. The words used are words of description rather than of limitation. Those skilled in the art will understand that modifications and variations can be made without departing from the spirit and scope of the present invention as set forth in the following claims. It will also be understood that the aspects of the various embodiments can be interchanged in whole or in part, or combined and / or used together in any manner. Therefore, the spirit and scope of the appended claims should not be construed as limiting the description of the preferred versions contained herein.

[0169] Example 1 Oxygen permeability measurement Apparent lens oxygen permeability and oxygen transmissibility of lens materials are determined according to techniques similar to those described in U.S. Patent No. 5,760,100 and Winterton et al., The Cornea: Transactions of the World Congress on the Cornea 111, H.D. Cavanagh Ed., Raven Press: New York 1988, pp273-280, both of which are incorporated herein by reference in their entireties. Oxygen flux (J) is measured in a humidified cell (i.e., gas flow maintained at approximately 100% relative humidity) at 34° C. using a Dk1000 instrument (available from Applied Design and Development Co., Norcross, GA) or similar analyzer. An airflow of known oxygen % (e.g., 21%) is passed through the lens at approximately 10-20 cm 3 Pass a stream of nitrogen through one side of the lens at a rate of 10-20 cm / min and through the other side of the lens. 3 / min. Equilibrate the sample with the test medium (i.e., saline or distilled water) for at least 30 minutes (but not more than 45 minutes) at the prescribed test temperature prior to measurement. Equilibrate any test medium used as an overlayer for at least 30 minutes (but not more than 45 minutes) at the prescribed test temperature prior to measurement. Set the stir motor speed to 1200 ± 50 rpm, which corresponds to a stepper motor controller display setting of 400 ± 15. Atmospheric pressure P surrounding the system is measured The lens thickness (t) in the area exposed to the test is determined by measuring approximately 10 points with a Mitotoya micrometer VL-50 or similar device and averaging the measurements. The oxygen concentration of the nitrogen stream (i.e., the oxygen that diffuses through the lens) is measured with a DK1000 device. The apparent oxygen permeability Dk of the lens material is app is determined from the following formula: Dk app =Jt / (P oxygen ) [Wherein, J = oxygen flux [O2 μl / cm 2 -min] P oxygen =(P measured -P water vapor) = (O2% in air stream) [mmHg] = partial pressure of oxygen in air stream P measured = atmospheric pressure (mmHg) P water Steam = 0 mmHg (in dry cell) at 34°C (mmHg) P water Steam = 40 mmHg (in a wet cell) at 34°C (mmHg) t = average lens thickness in the exposed test area (mm) Dk app is expressed in barrer units]

[0170] The apparent oxygen transmissibility (Dk / t) of a material is the apparent oxygen permeability (Dk app ) by the average lens thickness (t).

[0171] The above measurements are not corrected for the so-called boundary layer effect, which results from the use of a water or saline bath on top of the contact lens during oxygen flux measurements. Boundary layer effects cause the reported values ​​for the apparent Dk of silicone hydrogel materials to be lower than the actual intrinsic Dk value. Furthermore, the relative impact of boundary layer effects is greater for thin lenses than for thick lenses. The net effect is displayed as a function of lens thickness if the reported Dk needs to be constant.

[0172] The intrinsic Dk value of a lens can be estimated based on the Dk value corrected for surface resistance to oxygen flux caused by boundary layer effects as follows:

[0173] The apparent oxygen permeability values ​​(single point) of reference lotrafilcon A (Focus® N&D® from CIBA VISION CORPORATION) or lotrafilcon B (AirOptix™ from CIBA VISION CORPORATION) lenses are measured using the same device. The reference lenses are of similar power to the test lenses and are measured at the same time as the test lenses.

[0174] Following the procedure for the apparent Dk measurement above, the same device was used to measure oxygen flux through a range of thicknesses of either lotrafilcon A or lotrafilcon B (reference) lenses to obtain the intrinsic Dk value of the reference lens (Dk i The thickness series covers a thickness range of about 100 μm or more. Preferably, the thickness range of the reference lenses brackets the thickness of the test lenses. The Dk of these reference lenses is app is measured with the same equipment as the test lenses, and ideally at the same time as the test lenses. The equipment settings and measurement parameters are kept constant throughout the experiment. If desired, each sample may be measured multiple times.

[0175] In the calculation, the residual oxygen resistance value R is calculated from the result of the reference lens using Equation 1. r Determine.

number

[0176] Using the residual oxygen resistance value determined above, the exact oxygen permeability Dk of the test lens was calculated based on Equation 2. c Calculate (estimated specific Dk).

number

[0177] Using the estimated intrinsic Dk of the test lens, the apparent Dk for a lens of standard thickness under the same test environment (Dk a_std ) can be calculated. std ) = 85 μm. Standard thickness of lotrafilcon B = 60 μm.

number

[0178] Ion permeability measurement The ion permeability of the lenses is measured according to the procedure described in U.S. Patent No. 5,760,100, which is incorporated herein by reference in its entirety. The ion permeability values ​​presented in the examples below are the relative ionoflux diffusion coefficients (D / D) for the lens material Alsacon, a standard material. ref ) Alsacon has an ionoflux diffusion coefficient of 0.314×10 -3 mm 2 / min.

[0179] Lubricity evaluation The lubricity ranking is a qualitative ranking system, where 0 is assigned to the polyacrylic acid coated control lenses, 1 is assigned to the Oasys™ / TruEye™ commercial lenses, and 4 is assigned to the commercial Air Optix™ lenses. The samples are rinsed at least three times with excess DI water and then transferred to PBS for evaluation. Before evaluation, hands are rinsed with soapy water, rinsed thoroughly with DI water, and then dried with a KimWipe® towel. The samples are handled between the fingers and each sample is assigned a numerical value relative to the standard lenses mentioned above. For example, if the lenses are determined to be slightly better than the Air Optix™ lenses, these lenses are assigned the number 3. For consistency, all rankings are collected independently by the same two operators to avoid bias, and the data reveals good qualitative agreement and consistency of ratings.

[0180] Surface Wettability Test The water contact angle on a contact lens is a general measure of the surface wettability of the contact lens. In particular, a smaller water contact angle corresponds to a more wettable surface. The average contact angle (sessile drop method) of a contact lens is measured using a VCA 2500 XE contact angle measuring instrument from AST, Inc., Boston, Massachusetts. This instrument allows for the measurement of advancing or receding contact angles or settled (static) contact angles. Measurements are performed on fully hydrated contact lenses immediately after blot drying as described below. The contact lens is removed from the vial and washed three times in ∼200 ml of fresh DI water to remove any weakly bound packaging additives from the lens surface. The lens is then placed on a soft clean cloth (Alpha Wipe TX1009), wiped thoroughly to remove any surface water, placed on the contact angle measuring platform, and allowed to air dry by blowing dry air through it, and finally the sessile drop contact angle is measured automatically using the software provided by the manufacturer. The DI water used to measure the contact angle has a resistivity >18 MΩcm and the drop volume used is 2 μl. Typically, uncoated silicone hydrogel lenses (after autoclaving) have a liquid drop contact angle of around 120 degrees. Prior to contact with the contact lens, the tweezers and stage are thoroughly washed with isopropanol and rinsed with DI water.

[0181] Water Breakdown Time (WBUT) Test The surface hydrophilicity of lenses (post-autoclaving) is assessed by determining the time required for the water film on the lens surface to begin to break down. Briefly, lenses are removed from the vials and washed 3 times in ~200 ml fresh DI water to remove weakly bound packaging additives from the lens surface. The lenses are removed from the solution, held with tweezers and held up to a strong light source. The time required for the water film to break down (dewet) and expose the underlying lens material is visually determined. Uncoated lenses typically break down immediately upon removal of the DI water, which is designated a WBUT of 0 seconds. Lenses that exhibit a WBUT ≥ 5 seconds are considered to be of good hydrophilicity and are expected to demonstrate the ability to maintain a tear film on the eye.

[0182] Coating intact test The integrity of the coating on the surface of a contact lens can be tested according to the Sudan Black staining test as follows: A contact lens with a coating (LbL coating, plasma coating or any other coating) is immersed in a Sudan Black dye solution (Sudan Black in Vitamin E oil) and then rinsed thoroughly with water. Sudan Black dye is hydrophobic and has a strong tendency to be adsorbed by hydrophobic materials or on hydrophobic spots on the hydrophobic lens surface or on the partially coated surface of a hydrophobic lens (e.g., silicone hydrogel contact lens). If the coating on the hydrophobic lens is intact, no staining spots should be observed on or within the lens. All tested lenses are fully hydrated.

[0183] Coating durability test The lens is rubbed with a finger 30 times using Solo-care® multipurpose lens care solution, and then rinsed with saline. The above procedure is repeated a predetermined number of times, for example, 1 to 30 times (i.e., the number of consecutive digital rub tests that reproduce the washing and soaking cycles). The lens is then subjected to the Sudan Black test (i.e., the coating intact test described above) to test whether the coating is still intact. If it survives the digital rub test, there is no significant increase in the staining spots (e.g., the staining spots cover only about 5% of the total lens surface). The water contact angle is measured to determine the coating durability.

[0184] Determination of Azetidinium Content The azetidinium content in the PAE can be determined according to one of the following assays.

[0185] PPVS assay The PAE charge density (i.e., azetidinium content) can be determined according to the PPVS assay, a colorimetric titration assay, where the titrant is potassium vinyl sulfate (PPVS) and toluidine blue is the indicator. See SK Kam and J. Gregory, "Charge determination of synthetic cationic polyelectrolytes by colloid titration," in Colloid & Surface A: Physicochem. Eng. Aspect, 159: 165-179 (1999). PPVS binds to positively charged species, such as toluidine blue and the azetidinium group of the PAE. The decrease in the absorption intensity of toluidine blue is an indication of the proportional PAE charge density (azetidinium content).

[0186] PES-Na assay The PES-Na assay is another colorimetric titration assay for determining PAE charge density (azetidinium content). In this assay, the titrant is sodium polyethylene sulfonate (PES-Na) instead of PPVS. The assay is the same as the PPVS assay described above.

[0187] PCD assay The PCD assay is a potentiometric titration assay for determining the PAE charge density (azetidinium content). The titrant is sodium polyethylene sulfonate (PES-Na), PPVS or other titrants. The PAE charge is detected by electrodes, for example with a Mutek PCD-04 particle charge detector from BTG. The measurement principle of this detector can be found on the BTG website (http: / / www.btg.com / products.asp?langage=1&appli=5&numProd=357&cat=prod).

[0188] NMR method The active positively charged moiety in PAEs is the azetidinium group (AZR). The NMR ratio method is the ratio of the number of AZR group specific protons to the number of non-AZR associated protons. This ratio is an indication of the charge or AZR density of the PAE.

[0189] Debris adhesion test Contact lenses with highly charged surfaces may be susceptible to increased debris buildup during patient handling. Rub a paper towel with gloved hands, then rub both sides of the lens with fingers to transfer debris to the lens surface. Rinse the lens briefly and then view under a microscope. Rank each lens using a qualitative ranking scale ranging from 0 (no debris buildup) to 4 (debris buildup equivalent to PAA-coated control lenses). Lenses scoring "0" or "1" are considered acceptable.

[0190] Example 2 Preparation of CE-PDMS macromer In the first step, α,ω-bis(2-hydroxyethoxypropyl)-polydimethylsiloxane is capped with IPDI by reacting 49.85 g of α,ω-bis(2-hydroxyethoxypropyl)-polydimethylsiloxane (Mn=2000, Shin-Etsu, KF-6001a) with 11.1 g of isophorone diisocyanate (IPDI) in the presence of 0.063 g of dibutyltin dilaurate (DBTDL) in 150 g of dehydrated methyl ethyl ketone (MEK). The reaction is maintained at 40° C. for 4.5 hours to form IPDI-PDMS-IPDI. In the second step, a mixture of 164.8 g of α,ω-bis(2-hydroxyethoxypropyl)-polydimethylsiloxane (Mn=3000, Shin-Etsu, KF-6002) and 50 g of dehydrated MEK is added dropwise to the IPDI-PDMS-IPDI solution to which an additional 0.063 g of DBTDL has been added. The reactor is kept at about 40° C. for 4.5 hours to form HO-PDMS-IPDI-PDMS-IPDI-PDMS-OH. MEK is then removed under reduced pressure. In the third step, the terminal hydroxyl groups are capped with methacryloyloxyethyl groups by adding 7.77 g of isocyanatoethyl methacrylate (IEM) and an additional 0.063 g of DBTDL to form IEM-PDMS-IPDI-PDMS-IPDI-PDMS-IEM (i.e., CE-PDMS terminated with methacrylate groups).

[0191] Alternative preparation method for CE-PDMS macromers with terminal methacrylate groups 240.43 g of KF-6001 was added to a 1-L reactor equipped with a stirrer, thermometer, cryostat, dropping funnel, and nitrogen / vacuum inlet adapter, then subjected to high vacuum (2×10 -2The reactor is dried by application of 0.235 mBar). Then, under an atmosphere of dry nitrogen, 320 g of distilled MEK is added to the reactor and the mixture is thoroughly stirred. 0.235 g of DBTDL is added to the reactor. After warming the reactor to 45° C., 45.86 g of IPDI is added to the reactor over 10 minutes with moderate stirring via an addition funnel. The reaction is maintained at 60° C. for 2 hours. Then, 630 g of KF-6002 dissolved in 452 g of distilled MEK is added and stirred until a homogenous solution is formed. About 0.235 g of DBTDL is added and the reactor is held overnight at about 55° C. under a blanket of dry nitrogen. The next day, the MEK is removed by flash distillation. The reactor is cooled and then 22.7 g of IEM is charged to the reactor followed by about 0.235 g of DBTDL. After about 3 hours, an additional 3.3 g of IEM is added and the reaction is allowed to proceed overnight. The next day, the reaction mixture is cooled to about 18° C. to yield a CE-PDMS macromer with terminal methacrylate groups.

[0192] Example 3 Preparation of Lens Formulations A lens formulation is prepared by dissolving the ingredients in 1-propanol to have the following composition: 33% (by weight) CE-PDMS macromer prepared in Example 2, 17% (by weight) N-[tris(trimethylsiloxy)-silylpropyl]acrylamide (TRIS-Am), 24% (by weight) N,N-dimethylacrylamide (DMA), 0.5% (by weight) N-(carbonyl-methoxypolyethylene glycol-2000)-1,2-disteaoyl-sn-glycero-3-phosphoethanolamine, sodium salt) (L-PEG), 1.0% (by weight) Darocur 1173 (DC1173), 0.1% (by weight) visitint (5% copper phthalocyanine blue pigment dispersion in tris(trimethylsiloxy)silylpropyl methacrylate (TRIS)), and 24.5% (by weight) 1-propanol.

[0193] 1. Preparation of Lenses Lenses are prepared from the lens formulations prepared above by cast molding in a reusable mold similar to those shown in U.S. Patents 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The mold comprises a female half made of CaF2 and a male half made of PMMA. The UV radiation source is approximately 4 mW / cm2 intensity with a WG335+TM297 cutoff filter. 2 The UV irradiation is performed on the lens formulation in the mold for about 25 seconds. The cast lenses are extracted with isopropanol (or methyl ethyl ketone, MEK), rinsed with water, and coated with polyacrylic acid (PAA) by immersing the lenses in a propanol solution of PAA (0.1% by weight, acidified to a pH of about 2.5 with formic acid) and hydrated with water. The resulting lenses having the reactive PAA-LbL base coating thereon are determined to have the following properties: ion permeability of about 8.0 to about 9.0 relative to Alsacon lens material; apparent Dk (single point) of about 90 to 100; water content of about 30% to about 33%; and bulk surface modulus of about 0.60 MPa to about 0.65 MPa.

[0194] Example 4 The in-package coating (IPC) saline is prepared by adding 0.2% polyamidoamine-epichlorohydrin (PAE) (Ashland's Kymene (in water), used as is, azetidinium content 0.46 by NMR assay) to phosphate buffered saline (hereinafter PBS) (approximately 0.044 w / w% NaH2PO4·H2O, approximately 0.388 w / w% Na2HPO4·2H2O, approximately 0.79 w / w% NaCl) and then adjusting the pH to 7.2-7.4.

[0195] The lenses of Example 3 are placed in polypropylene lens packaging shells with 0.6 mL of IPC saline (half of the IPC saline is added before the lens is inserted), the blisters are then sealed with aluminum foil and autoclaved at 121° C. for about 30 minutes to form a crosslinked coating (PAA-x-PAE coating) on ​​the lenses.

[0196] The lenses are then evaluated for debris adhesion, surface cracking, lubricity, contact angle, and water break-up time (WBUT). The test lenses (packaged / autoclaved in IPC saline, i.e., lenses having a PAA-x-PAE coating thereon) show no debris adhesion after rubbing with a paper towel, whereas the control lenses (packaged / autoclaved in PBS, i.e., lenses having a PAA-LbL base coating thereon) show severe debris adhesion. The water contact angle (WCA) of the test lenses is small (~20 degrees), but the WBUT is less than 2 seconds. Severe cracking lines are visible after handling the lenses (inverting the lenses and rubbing the lenses between fingers) when observed under a dark field microscope. The test lenses are much less smooth than the control lenses as determined by a qualitative finger rub test.

[0197] Example 5 Poly(acrylamide-co-acrylic acid) (or PAAm-PAA or poly(AAm-co-AA) or p(AAm-co-AA)) partial sodium salt (~80% solids content, poly(AAm-co-AA) (80 / 20), Mw 520,000, Mn 150,000) was purchased from Aldrich and used as received.

[0198] IPC saline is prepared by dissolving 0.02% poly(AAm-co-AA) (80 / 20) and 0.2% PAE (Kymene (aqueous) from Ashland, ready to use, azetidinium content 0.46 by NMR assay) in PBS. The pH is adjusted to 7.2-7.4. PBS is prepared by dissolving 0.76% NaCl, 0.044% NaH2PO4·H2O and 0.388% Na2HPO4·2H2O in water.

[0199] The lenses having the PAA-LbL base coating thereon prepared in Example 3 are placed in a polypropylene lens packaging shell with 0.6 mL of IPC saline (half of the saline is added before the lens is inserted). The blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes. It is believed that a crosslinked coating consisting of three layers of PAA-x-PAE-x-poly(AAm-co-AA) is formed on the lenses during autoclaving.

[0200] The test lenses (packaged / autoclaved in IPC saline, i.e., lenses having a PAA-x-PAE-x-poly(AAm-co-AA) crosslinked coating thereon) are free of debris after rubbing with a paper towel. The test lenses have a WBUT of greater than 10 seconds. When viewed under a dark field microscope, cracking lines are visible after rubbing the test lenses. The test lenses are much smoother than the test lenses of Example 4, but still not as smooth as the control lenses packaged in PBS.

[0201] Example 6 The IPC saline solution is prepared by dissolving 0.02% poly(AAm-co-AA) (80 / 20) and 0.2% PAE (Kymene (aqueous solution) from Ashland, used as is, azetidinium content 0.46 by NMR assay) in PBS and adjusting the pH to 7.2-7.4. The saline solution is then heated to approximately 70°C and treated by heating at that temperature for 4 hours (heat pretreatment). During this heat pretreatment, the poly(AAm-co-AA) and PAE are partially crosslinked with each other (i.e., not all azetidinium groups of the PAE are consumed) to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups within a branched polymer network in the IPC saline solution. After heat pretreatment, the final IPC saline solution is filtered using a 0.22 micron polyethersulfone (PES) membrane filter and cooled again to room temperature.

[0202] The lenses having the PAA-LbL base coating thereon prepared in Example 3 are placed into polypropylene lens packaging shells along with 0.6 mL of IPC saline (half of the saline is added prior to lens insertion), the blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes to form a crosslinked coating (PAA-x-hydrophilic polymeric material) on the lenses.

[0203] The test lenses (packaged in heat pretreated IPC saline, i.e., lenses having a PAA-x-hydrophilic polymeric material coating thereon) show no debris adhesion after rubbing with a paper towel, whereas the control lenses (packaged in PBS, i.e., lenses having a non-covalently bonded layer of PAA thereon) show severe debris adhesion. The test lenses have a WBUT of greater than 10 seconds. No cracking lines are visible after rubbing the test lenses when observed under a dark field microscope. The test lenses are very smooth in the finger rub test and are comparable to the control lenses.

[0204] A series of experiments are carried out to study the effect of IPC saline heat pretreatment conditions (duration and / or temperature) on the surface properties of the resulting IPC saline coated lenses. Heat treatment times of about 6 hours or more at about 70°C result in lenses that are susceptible to debris adhesion similar to the control lenses. It is believed that longer heat pretreatments may consume most of the azetidinium groups, so that the number of azetidinium groups remaining in the branched polymer network of the resulting water-soluble polymeric material is insufficient to adhere the polymeric material to the PAA coating. Heat treatment at 50°C for only 4 hours results in lenses that show surface cracking lines under dark field microscope after rubbing between fingers, similar to the test lenses of Example 5 that are not heat pretreated with IPC saline. It is believed that shorter heat pretreatments may consume a small amount of azetidinium groups, so that the number of azetidinium groups remaining in the branched polymer network of the resulting water-soluble polymeric material is high, so that the resulting crosslinked coating (PAA-x-hydrophilic polymeric material) on the lenses may have a very high crosslink density.

[0205] Example 7 Poly(acrylamide-co-acrylic acid) partial sodium salt (~90% solids content, poly(AAm-co-AA) 90 / 10, Mw 200,000) was purchased from Polysciences, Inc. and used as received.

[0206] The IPC saline solution is prepared by dissolving 0.07% PAAm-PAA (90 / 10) and 0.2% PAE (Kymene (aqueous solution) from Ashland, used as is, azetidinium content 0.46 by NMR assay) in PBS and adjusting the pH to 7.2-7.4. The saline solution is then heat pretreated at about 70°C for about 4 hours (heat pretreatment). During this heat pretreatment, poly(AAm-co-AA) and PAE are partially crosslinked with each other (i.e., not all azetidinium groups of PAE are consumed) to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups within a branched polymer network in the IPC saline solution. After heat pretreatment, the IPC saline solution is filtered using a 0.22 micron polyethersulfone [PES] membrane filter and cooled again to room temperature.

[0207] The lenses having the PAA-LbL base coating thereon as prepared in Example 3 and uncoated Lotrafilcon B lenses (CIBA Vision Corporation) immersed in an acidic propanol solution of PAA (about 0.1%, pH ~ 2.5) are placed into polypropylene lens packaging shells with 0.6 mL of heat pretreated IPC saline (half of the IPC saline is added before the lens insertion). The blisters are then sealed with aluminum foil and autoclaved at 121°C for about 30 minutes to form a crosslinked coating (PAA-x-hydrophilic polymeric material) on the lenses.

[0208] The test lenses (both Lotrafilcon B having PAA-x-hydrophilic polymer thereon and the lenses of Example 3) are free of debris after rubbing with a paper towel. The test lenses have a WBUT of greater than 10 seconds. No cracking lines are visible after rubbing the lenses between fingers when viewed under a dark field microscope. The lenses are very smooth in the qualitative finger rub test.

[0209] Example 8 In a design of experiments (DOE), an IPC saline solution is made containing about 0.05% to about 0.09% PAAm-PAA and about 0.075% to about 0.19% PAE (Kymene (aqueous solution) from Ashland, used as is, azetidinium content 0.46 by NMR assay) in PBS. The IPC saline solution is heat treated at 60° C. for 8 hours and the lenses of Example 3 are packaged in the heat pretreated IPC saline solution. No differences in the surface properties of the final lenses are observed, with all lenses exhibiting excellent lubricity, resistance to debris adhesion, excellent wettability, and no surface cracking.

[0210] Example 9 In a design of experiments (DOE), the IPC saline is made to contain approximately 0.07% PAAm-PAA and sufficient PAE to obtain an initial azetidinium content of approximately 8.8 millimole equivalents / liter (~0.15% PAE). Heat pretreatment conditions are varied from 50°C to 70°C in a central composite design, and prereaction times are varied from approximately 4 to approximately 12 hours. A prereaction time of 24 hours at 60°C is also tested. 10 ppm hydrogen peroxide is then added to the saline to prevent bioburden buildup, and the IPC saline is filtered using a 0.22 micron polyethersulfone [PES] membrane filter.

[0211] The lenses of Example 3 are packaged in heat pretreated IPC saline, and then the blisters are autoclaved at 121° C. for 45 minutes. All lenses have excellent lubricity, wettability and surface cracking resistance. As shown in Table 1, some lenses show adhesion of debris from the paper towel.

[0212] [Table 1]

[0213] Example 10 Copolymers of methacryloyloxyethyl phosphorylcholine (MPC) with one carboxyl-containing vinyl monomer (CH2=CH(CH3)C(O)OC2H4OC(O)C2H4COOH (MS), methacrylic acid (MA)) in the absence or presence of butyl methacrylate (BMA) are evaluated in an in-package coating system in combination with PAE.

[0214] Prepare PBS containing NaCl (0.75% (wt)), NaH2PO4·H2O (0.0536% (wt)), Na2HPO4·2H2O (0.3576% (wt)) and DI water (97.59% (wt)) and add 0.2% PAE (polycup 3160). Adjust the PH to approximately 7.3.

[0215] Next, 0.25% of one of several MPC copolymers is added to make IPC saline, and the IPC saline is heat pretreated at 70° C. for 4 hours (heat pretreatment). During this heat pretreatment, MPC and PAE are partially crosslinked with each other (i.e., not all azetidinium groups of PAE are consumed) to form water-soluble and heat crosslinkable hydrophilic polymeric material containing azetidinium groups within the branched polymer network in the IPC saline. After 4 hours, the heat pretreated IPC saline is filtered through a 0.2 micron polyethersulfone [PES] membrane filter (Fisher Scientific catalog#09-741-04, Thermo Scientific nalgene #568-0020) (250 ml).

[0216] The lenses having thereon the PAA-LbL base coating prepared in Example 3 are packaged in heat pretreated IPC saline and autoclaved for about 30 minutes at 121° C. Table 2 shows that all the lenses have excellent surface properties.

[0217] [Table 2]

[0218] Example 11 PAA coated lens Lenses cast from the lens formulation prepared in Example 3 according to the molding process described in Example 3 are extracted and coated by immersion in a series of baths: three MEK baths (22, 78 and 224 seconds); a DI water bath (56 seconds); two PAA coating solution baths (prepared by dissolving 3.6 g of PAA (MW: 450 kDa, Lubrizol) in 975 ml of 1-propanol and 25 ml of formic acid) for 44 and 56 seconds, respectively; and three DI water baths for 56 seconds each.

[0219] PAE / PAA coated lenses The lens having the above prepared PAA-based coating thereon is successively immersed in the following baths: two PAE coating solution baths (prepared by dissolving 0.25 wt% PAE (Polycup 172, Hercules) in DI water, adjusting the pH to about 5.0 using sodium hydroxide, and finally filtering the resulting solution using a 5 μm filter) for 44 and 56 seconds respectively; and three DI water baths for 56 seconds each. After this treatment, the lens has one layer of PAA and one layer of PAE.

[0220] A lens having a PAA-x-PAE-x-CMC coating thereon A batch of lenses with one layer of PAA and one layer of PAE thereon is packaged in 0.2% sodium carboxymethylcellulose (CMC, product number 7H 3SF PH, Ashland Aqualon) in phosphate buffered saline (PBS), then the pH is adjusted to 7.2-7.4. The blisters are then sealed and autoclaved at 121°C for about 30 minutes to form a crosslinked coating (PAA-x-PAE-x-CMC) on the lenses.

[0221] A lens having a PAA-x-PAE-x-HA coating thereon Another batch of lenses with one layer of PAA and one layer of PAE on them is packaged in 0.2% hyaluronic acid (HA, product number 6915004, Novozymes) in phosphate buffered saline (PBS), then the pH is adjusted to 7.2-7.4. The blisters are then sealed and autoclaved at 121°C for approximately 30 minutes to form a crosslinked coating (PAA-x-PAE-x-HA) on the lenses.

[0222] The resulting lenses having either the PAA-x-PAE-x-CMC or PAA-x-PAE-x-HA coatings thereon exhibit no Sudan black staining, no debris adhesion and no cracking under microscopic examination. The lenses having the PAA-x-PAE-x-CMC coatings thereon have an average contact angle of 30±3 degrees and the lenses having the PAA-x-PAE-x-HA coatings thereon have an average contact angle of 20±3 degrees.

[0223] Example 12 Preparation of IPC solutions The reaction mixture is prepared by dissolving 2.86% (wt) mPEG-SH2000 (methoxy-poly(ethylene glycol)-thiol, Avg MW 2000, product number MPEG-SH-2000, Laysan Bio Inc.) with 2% (wt) PAE (Kymene (aqueous solution) from Ashland, used as is, azetidinium content 0.46 by NMR assay) in PBS and adjusting the final pH to 7.5. The solution is heated at 45° C. for about 4 hours (heat pretreatment). During this heat pretreatment, mPEG-SH2000 and PAE react with each other to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups as well as chemically grafted polyethylene glycol polymer chains. After heat treatment, the solution is diluted 10-fold with PBS containing 0.25% sodium citrate, the pH is adjusted to 7.2-7.4, and filtered using a 0.22 micron polyethersulfone (PES) membrane filter. The final IPC saline contains 0.286% (by weight) hydrophilic polymeric material (composed of approximately 59% (by weight) MPEG-SH-2000 chains and approximately 41% (by weight) PAE chains) and 0.25% sodium citrate dihydrate. PBS is prepared by dissolving 0.74% NaCl, 0.053% NaH2PO4·H2O, and 0.353% Na2HPO4·2H2O in water.

[0224] Lens having a crosslinked coating thereon - Patent application The PAA coated lenses of Example 11 are packaged in the above IPC saline in polypropylene lens packaging shells, then autoclaved at about 121°C for about 30 minutes to form a crosslinked coating on the lenses. The final lenses show no debris adhesion, no cracking lines after rubbing the lenses. The lenses are very smooth in finger rub tests, similar to the control PAA coated lenses.

[0225] A series of experiments are carried out to study the effect of conditions (reaction time and mPEG-SH2000 solution concentration (with a constant PAE concentration of 2%)) on the surface properties of the resulting IPC saline coated lenses. The results are shown in Table 3.

[0226] [Table 3]

[0227] As the solution concentration of mPEGSH2000 increases, the lubricity of the lens increases. The increase in the surface contact angle may be due to the increasing density of terminal methyl groups on the surface with increasing grafting density. At high grafting densities, corresponding to a solution concentration of 0.6%, the contact angle is comparable to measurements obtained on polyethylene glycol (PEG) monolayer grafted flat substrates (reference: Langmuir 2008, 24, 10646-10653).

[0228] Example 13 A series of experiments are carried out to study the effect of the molecular weight of mPEG-SH. IPC saline is prepared similarly to the procedure described in Example 12. However, the following mPEG-SH are used to prepare the saline: mPEG-SH1000, mPEG-SH2000, mPEG-SH5000 and mPEG-SH20000. All saline is subjected to heat treatment at 45°C for 4 hours and 10-fold dilution. The results and reaction conditions are shown below:

[0229] [Table 4]

[0230] Example 14 The reaction mixture is prepared by dissolving 2.5% mPEG-SH2000, 10% PAE (Ashland's Kymene (aqueous), used as is, azetidinium content 0.46 by NMR assay) and 0.25% sodium citrate dihydrate in PBS. The pH of the solution is then adjusted to 7.5 and further degassed by bubbling nitrogen gas through the vessel for 2 hours. The solution is then heat treated at 45°C for approximately 6 hours to react with the azetidinium groups in the PAE to form a thermally crosslinkable hydrophilic polymeric material containing mPEG-SH-2000 groups chemically grafted onto the polymer. After heat treatment, the solution is diluted 50 times using PBS containing 0.25% sodium citrate, the pH is adjusted to 7.2-7.4, and filtered using a 0.22 micron polyethersulfone (PES) membrane filter. The final IPC saline solution contains about 0.30% (by weight) polymeric material (composed of about 17% wt. mPEG-SH-2000 and about 83% wt. PAE) and 0.25% sodium citrate dihydrate.

[0231] The PAA coated lenses of Example 11 are packaged in the above IPC saline in polypropylene lens packaging shells and then autoclaved at about 121° C. for about 30 minutes to form a crosslinked coating on the lenses.

[0232] The final lenses show no debris buildup, cracking lines after rubbing the lenses. The test lenses are very smooth in finger rub tests, similar to the control PAA coated lenses.

[0233] Example 15 The reaction mixture is prepared by dissolving 3.62% mPEG-NH2-550 (Methoxy-poly(ethylene glycol)-amine, MW ~550 (product no. MPEG-NH2-550, Laysan Bio Inc.) in PBS with 2% PAE (Kymene (in water) from Ashland, used as is, azetidinium ratio 0.46 as assayed by NMR) and adjusting the final pH to 10. The solution is heated at 45 °C for approximately 4 hours to form a thermally crosslinkable hydrophilic polymeric material containing MPEG-NH2-550 groups chemically grafted onto the polymer by reacting with the azetidinium groups in the PAE. After heating, the solution is diluted 10x with PBS containing 0.25% sodium citrate. The solution is diluted, the pH adjusted to 7.2-7.4, and filtered using a 0.22 micron polyethersulfone (PES) membrane filter. The final IPC saline solution contains approximately 0.562% wt. of polymeric material (composed of 64% wt. MPEG-SH-2000 and approximately 36% wt. PAE) and 0.25% sodium citrate dihydrate. PBS is prepared by dissolving 0.74% NaCl, 0.053% NaH2PO4·H2O, and 0.353% Na2HPO4·2H2O in water.

[0234] The PAA coated lenses of Example 11 are packaged in the above IPC saline in polypropylene lens packaging shells and then autoclaved at about 121° C. for about 30 minutes to form a crosslinked coating on the lenses.

[0235] The final lenses show no debris build-up and no cracking lines after digital (finger) rubbing of the lenses.

[0236] Example 16 Poloxamer 108 (sample) and Nelfilcon A (CIBA VISION) are used as is. Nelfilcon A is a polymerizable polyvinyl alcohol obtained by modifying polyvinyl alcohol (e.g., Gohsenol KL-03 from Nippon Gohsei Co., Ltd.) with N-(2,2-dimethoxyethyl)acrylamide under cyclic acetal forming reaction conditions (Buhler et al., CHIMIA, 53 (1999), 269-274, the entirety of which is incorporated herein by reference). Approximately 2.5% of the vinyl alcohol units in Nelfilcon A are modified with N-(2,2-dimethoxyethyl)acrylamide.

[0237] IPC saline is prepared by dissolving 0.004% poloxamer 108, 0.8% Nelfilcon A, 0.2% PAE (Kymene, Polycup 3160), 0.45% NaCl, and 1.1% disodium hydrogen phosphate (dihydrate) in DI water. The saline is heat pretreated by stirring at approximately 65-70 °C for 2 h. After heat pretreatment, the saline is cooled to room temperature and then filtered using a 0.2 μm PES filter.

[0238] The lenses prepared in Example 3 are placed into polypropylene lens packaging shells along with 0.6 mL of IPC saline (half of the saline is added prior to lens insertion.) The blisters are then sealed with aluminum foil and autoclaved at 121° C. for approximately 30 minutes.

[0239] The test lenses show no debris adhesion after rubbing with a paper towel. The lenses have a WBUT of more than 10 seconds. When observed under a dark field microscope, no cracking lines are visible after rubbing the lenses between fingers. The lenses are much smoother than the lenses of Example 4, but still not as smooth as the PAA-coated control lenses packaged in PBS.

[0240] Example 17 A. Synthesis of 80% Ethylenically Functionalized Chain-Extended Polysiloxane KF-6001A (α,ω-bis(2-hydroxyethoxypropyl)-polydimethylsiloxane, Mn=2000, Shin-Etsu) and KF-6002A (α,ω-bis(2-hydroxyethoxypropyl)-polydimethylsiloxane, Mn=3400, Shin-Etsu) are dried separately in a one-neck flask under high vacuum at about 60° C. for 12 hours (or overnight). The OH molar equivalents of KF-6001A and KF-6002A are determined by titration of the hydroxyl groups and used to calculate the millimolar equivalents used in the synthesis.

[0241] A 1 liter reaction vessel is evacuated overnight to remove moisture, the vacuum is broken and replaced with dry nitrogen. 75.00 g (75 meq) of dry KF6001A is charged to the reactor, then 16.68 g (150 meq) of freshly distilled IPDI is added to the reactor. The reactor is purged with nitrogen and heated to 45° C. with stirring, then 0.30 g of DBTDL is added. The reactor is sealed and a positive flow of nitrogen is maintained. An exotherm occurs, after which the reaction mixture is cooled and stirred at 55° C. for 2 hours. After the exotherm is reached, 248.00 g (150 meq) of dry KF6002A is added to the reactor at 55° C., then 100 μL of DBTDL is added. The reactor is stirred for 4 hours. Heating is discontinued and the reactor is allowed to cool overnight. Nitrogen bubbling is discontinued and the reactor is opened to the atmosphere and allowed to stir moderately for 30 minutes. The hydroxyl-terminated chain extended polysiloxane HO-PDMS-IPDI-PDMS-IPDI-PDMS-OH (or HO-CE-PDMS-OH) with three polysiloxane segments is produced.

[0242] For 80% ethylenically functionalized polysiloxane, add 18.64 g (120 meq) of IEM to the reactor along with 100 μL of DBTDL. The reactor is stirred for 24 h, then the product (80% IEM capped CE-PDMS) is decanted and stored under refrigeration.

[0243] B: Synthesis of non-UV absorbing amphiphilic branched polysiloxane prepolymers A 1 L jacketed reactor is equipped with a 500 mL addition funnel, overhead stirrer, reflux condenser with nitrogen / vacuum inlet adapter, thermometer, and sampling adapter. The reactor is charged with 45.6 g of 80% IEM capped CE-PDMS prepared above and sealed. A solution of 0.65 g hydroxyethyl methacrylate (HEMA), 25.80 g DMA, 27.80 g (tris(trimethylsilyl))-siloxypropyl) methacrylate (TRIS) in 279 g ethyl acetate is charged to the addition funnel. The reactor is degassed with a high vacuum pump at <1 mbar for 30 minutes at room temperature. The monomer solution is degassed for 3 cycles at 100 mbar for 10 minutes at room temperature, replacing the vacuum with nitrogen during the degassing cycles. The monomer solution is then charged to the reactor, followed by stirring and heating the reaction mixture to 67°C. While heating, a solution of 1.50 g mercaptoethanol (chain transfer agent, CTA) and 0.26 g azoisobutyronitrile dissolved in 39 g ethyl acetate is charged to the addition funnel and deoxygenated at 100 mbar and room temperature for 10 minutes three times. When the reactor temperature reaches 67° C., the initiator / CTA solution is added to the PDMS / monomer solution in the reactor. The reaction is allowed to proceed for 8 hours, then heating is discontinued and the reactor temperature is allowed to reach room temperature within 15 minutes.

[0244] The resulting reaction mixture is then siphoned into a dry one-neck flask with an airtight lid and 4.452 g of IEM is added along with 0.21 g of DBTDL. The mixture is stirred at room temperature for 24 h to produce a non-UV absorbing amphiphilic branched polysiloxane prepolymer. To this mixed solution, 100 μL of hydroxy-tetramethylenepiperonyloxy solution in ethyl acetate (2 g / 20 mL) is added. The solution is then concentrated to 200 g (~50%) using a rotary evaporator (rota-vap) at 30 °C and filtered through a 1 μm pore size filter paper. After solvent exchange to 1-propanol, the solution is further concentrated to the desired concentration.

[0245] C. Synthesis of UV-absorbing amphiphilic branched polysiloxane prepolymers A 1 L jacketed reactor is equipped with a 500 mL addition funnel, overhead stirrer, reflux condenser with nitrogen / vacuum inlet adapter, thermometer, and sampling adapter. The reactor is then charged with 45.98 g of the 80% IEM capped CE-PDMS prepared above and the reactor is sealed. A solution of 0.512 g HEMA, 25.354 g DMA, 1.38 g Norbloc methacrylate, 26.034 g TRIS in 263 g ethyl acetate is charged to the addition funnel. The reactor is degassed with a high vacuum pump at <1 mbar for 30 minutes at room temperature. The monomer solution is degassed for 3 cycles at 100 mbar for 10 minutes at room temperature, replacing the vacuum with nitrogen during the degassing cycles. The monomer solution is then charged to the reactor, after which the reaction mixture is stirred and heated to 67°C. While heating, a solution of 1.480 g mercaptoethanol (chain transfer agent, CTA) and 0.260 g azoisobutyronitrile dissolved in 38 g ethyl acetate is charged to the addition funnel and deoxygenated at 100 mbar and room temperature for 10 minutes three times. When the reactor temperature reaches 67° C., the initiator / CTA solution is added to the PDMS / monomer solution in the reactor. The reaction is allowed to proceed for 8 hours, then heating is discontinued and the reactor temperature is allowed to reach room temperature within 15 minutes.

[0246] The resulting reaction mixture is then siphoned into a dry one-neck flask with an airtight lid and 3.841 g of isocyanatoethyl acrylate is added along with 0.15 g of DBTDL. The mixture is stirred at room temperature for 24 h to produce a UV-absorbing amphiphilic branched polysiloxane prepolymer. To this mixed solution is added 100 μL of hydroxy-tetramethylenepiperonyloxy solution in ethyl acetate (2 g / 20 mL). The solution is then concentrated to 200 g (~50%) using a rotary evaporator at 30 °C and filtered through a 1 μm pore size filter paper.

[0247] D-1: Lens formulation with non-UV absorbing polysiloxane prepolymer In a 100 mL amber flask, add 4.31 g of the synthetic macromer solution (82.39% in 1-propanol) prepared above. In a 20 mL vial, 0.081 g of TPO and 0.045 g of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) are dissolved in 10 g of 1-propanol and then transferred to the macromer solution. After concentrating the mixture to 5.64 g at 30° C. using a rotary evaporator, 0.36 g of DMA is added and the formulation is homogenized at room temperature. 6 g of transparent lens formulation D-1 is obtained.

[0248] D-2: Lens formulation with UV absorbing polysiloxane prepolymer (4% DMA) In a 100 mL amber flask, add 24.250 g of the macromer solution (43.92% in ethyl acetate) prepared above. In a 50 mL vial, 0.15 g of TPO and 0.75 g of DMPC are dissolved in 20 g of 1-propanol and then transferred to the macromer solution. Using a rotary evaporator, remove 20 g of solvent at 30° C., then add 20 g of 1-propanol. After two cycles, the mixture is concentrated to 14.40 g. 0.6 g of DMA is added to the mixture and the formulation is homogenized at room temperature. 15 g of clear lens formulation D-2 is obtained.

[0249] D-3: Lens formulation with UV absorbing polysiloxane prepolymer (2% DMA / 2% HEA) In a 100 mL amber flask, add 24.250 g of the macromer solution (43.92% in ethyl acetate) prepared above. In a 50 mL vial, 0.15 g of TPO and 0.75 g of DMPC are dissolved in 20 g of 1-propanol and then transferred to the macromer solution. Using a rotary evaporator, remove 20 g of solvent at 30° C., then add 20 g of 1-propanol. After two cycles, the mixture is concentrated to 14.40 g. 0.3 g of DMA and 0.3 g of HEA are added to the mixture and the formulation is homogenized at room temperature. 15 g of transparent lens formulation D-3 is obtained.

[0250] Example 18 Example E: Covalent attachment of modified PAE coating polymer Monomers containing amine groups, N-(3-aminopropyl) methacrylamide hydrochloride (APMAA-HCl) or N-(2-aminoethyl) methacrylamide hydrochloride (AEMAA-HCl), are purchased from Polysciences and used as received. Poly(amidoamine epichlorohydrin) (PAE) in water is obtained from Ashland and used as received. Poly(acrylamide-co-acrylic acid) (poly(AAm-co-AA) (90 / 10) from Polysciences, mPEG-SH from Laysan Bio, and poly(MPC-co-AeMA) (i.e., a copolymer of methacryloyloxyethyl phosphorylcholine (MPC) and aminoethyl methacrylate (AeMA)) from NOF are used as received.

[0251] The APMAA-HCl monomer is dissolved in methanol and added to lens formulations D-1, D-2 and D-3 (prepared in Example 17) to achieve a concentration of 1 wt %.

[0252] Prepare reactive packaging saline by dissolving the ingredients listed in Table 4 in DI water along with the appropriate buffer salts. Heat pre-treat the saline by stirring at approximately 60° C. for 8 hours. After heat pre-treatment, allow the saline to cool to room temperature and then filter using a 0.2 μm PES filter.

[0253] [Table 5]

[0254] Lens formulation D-1 prepared in Example 17 was modified by adding APMAA-HCl monomer (APMMA-HCL stock solution in 1:1 methanol:propanol) to obtain a luminance of 16 mW / cm 2 Lens formulations D-2 and D-3 prepared in Example 17 were modified by adding APMAA-HCl monomer and cured at 4.6 mW / cm 2 and harden with a 380 nm filter.

[0255] DSM Lenses The female part of a polypropylene lens mold is filled with approximately 75 μl of the lens formulation prepared above and the mold is closed with the male part (base curve mold) of the polypropylene lens mold. The closed mold is exposed to a UV irradiation source (intensity approximately 16 mW / cm with a 330 nm cutoff filter). 2 The contact lenses are obtained by curing for about 5 minutes using a 1000W Hamamatsu lamp.

[0256] LS Lens LS lenses are prepared from the lens formulations prepared above by cast molding in a reusable mold similar to those shown in U.S. Patents 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The mold includes a female half made of quartz and a male half made of PMMA. The UV radiation source is approximately 4.6 mW / cm2 intensity with a 380 nm cutoff filter. 2 The lens formulation in the mold is exposed to UV radiation for approximately 30 seconds.

[0257] Lens formulation D-1 modified with APMAA-HCl is cured according to the DSM and LS methods described above, and lens formulations D-2 or D-3 are cured according to the LS method described above.

[0258] The molded lenses are extracted with methyl ethyl ketone, hydrated, and packaged in one of the saline solutions listed in Table 4. The lenses are placed into polypropylene lens packaging shells with 0.6 mL of IPC saline (half of the saline is added before inserting the lens). The blisters are then sealed with aluminum foil and autoclaved at 121° C. for 30 minutes.

[0259] Evaluation of the lens surface shows that all test lenses are free of debris after rubbing with a paper towel, and no cracking lines are visible after rubbing the lenses between fingers when viewed under a dark field microscope.

[0260] The wettability (WBUT), lubricity and contact angle of the lens surface were measured and the results are summarized in Table 5. Unless otherwise specified, the lenses are manufactured according to DSM method. Lubricity is rated on a qualitative scale of 0 to 5, with lower numbers indicating greater lubricity. In general, all properties are shown to improve after application of the in-package coating.

[0261] [Table 6]

[0262] Example 19 Preparation of Lens Formulations A lens formulation is prepared by dissolving the components in 1-propanol to have the following composition: about 32% (by weight) CE-PDMS macromer prepared in Example 2, about 21% (by weight) TRIS-Am, about 23% (by weight) DMA, about 0.6% (by weight) L-PEG, about 1% (by weight) DC1173, about 0.1% (by weight) visitint (5% copper phthalocyanine blue dye dispersion in TRIS), about 0.8% (by weight) DMPC, about 200 ppm H-tempo, and about 22% (by weight) 1-propanol.

[0263] 1. Preparation of Lenses Lenses are prepared from the lens formulation prepared above by cast molding in a reusable mold (quartz female half and glass male half) similar to the molds shown in U.S. Patent Nos. 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The lens formulation in the mold is exposed to UV irradiation (13.0 mW / cm 2 ) and irradiate for approximately 24 seconds.

[0264] PAA Coating Solution A PAA coating solution is prepared by dissolving an amount of PAA (MW: 450 kDa, Lubrizol) in a given amount of 1-propanol to have a concentration of about 0.36% (by weight), and the pH is adjusted to about 2.0 with formic acid.

[0265] PAA coated lens Contact lenses cast as described above are extracted and coated by immersion in a series of baths: a DI water bath (approximately 56 seconds); six MEK baths (approximately 44, 56, 56, 56, 56, and 56 seconds, respectively); a DI water bath (approximately 56 seconds); one bath of PAA coating solution in 100% 1-propanol (approximately 0.36% by weight, acidified to pH approximately 2.0 with formic acid) (approximately 44 seconds); one bath of a 50% / 50% water / 1-propanol mixture (approximately 56 seconds); four DI water baths each for approximately 56 seconds; one PBS bath for approximately 56 seconds; and one DI water bath for approximately 56 seconds.

[0266] IPC Saline Poly(AAm-co-AA) (90 / 10) partial sodium salt (~90% solids content, poly(AAm-co-AA) 90 / 10, Mw 200,000) is purchased from Polysciences, Inc. and used as received. PAE (Kymene, azetidinium content 0.46 by NMR assay) is purchased as an aqueous solution from Ashland and used as received. IPC saline is prepared by dissolving approximately 0.07% w / w poly(AAm-co-AA) (90 / 10) and approximately 0.15% PAE (approximately 8.8 mmol initial azetidinium millimole equivalents) in PBS (approximately 0.044 w / w% NaH2PO4·H2O, approximately 0.388 w / w / % Na2HPO4·2H2O, approximately 0.79 w / w / % NaCl) and adjusting the pH to 7.2-7.4. The IPC saline solution is then heat pretreated at about 70° C. for about 4 hours (heat pretreatment). During this heat pretreatment, the poly(AAm-co-AA) and PAE are partially crosslinked with each other (i.e., not all azetidinium groups of the PAE are consumed) to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups within a branched polymer network in the IPC saline solution. After heat pretreatment, the IPC saline solution is filtered using a 0.22 micron PES membrane filter and cooled back to room temperature. Next, 10 ppm hydrogen peroxide is added to the final IPC saline solution to prevent bioburden buildup, and the IPC saline solution is filtered using a 0.22 micron PES membrane filter.

[0267] Application of cross-linked coatings The lenses having the PAA-LbL base coating thereon prepared above are placed into polypropylene lens packaging shells (one lens per shell) with 0.6 mL of IPC saline (half of the saline is added before lens insertion). The blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes to produce SiHy contact lenses having a crosslinked coating (PAA-x-hydrophilic polymeric material) thereon.

[0268] Characterization of SiHy lenses The SiHy contact lenses having the resulting crosslinked coating (PAA-x-hydrophilic polymeric material) thereon are free of debris after rubbing with a paper towel, whereas the control lenses (packaged in PBS, i.e., lenses having a non-covalently bonded layer of PAA thereon) show severe debris adhesion. The lenses have an oxygen permeability (Dk) of 146 barrer. c or estimated inherent Dk), a bulk surface modulus of 0.76 MPa, a water content of about 32% (by weight), a relative ion permeability of about 6 (relative to Alsacon lenses), a contact angle of about 34-47 degrees, and a WBUT of greater than 10 seconds. No cracking lines are visible after rubbing the test lenses when observed under a dark field microscope. The lenses are very smooth in finger rub tests comparable to the control lenses.

[0269] Example 20 The SiHy lenses and IPC saline in the post-autoclaved lens packages prepared in Examples 6, 14 and 19 are subjected to the biocompatibility studies described below.

[0270] In-vitro cytotoxicity assessment The SiHy lenses are evaluated by the USP Direct Contact Material Assay. Lens extractables are evaluated by the USP MEM elution and ISO CEN cell growth inhibition assays, and IPC saline in the package after autoclaving is evaluated by a modified elution method. All lenses and lens extractables evaluated were well within the acceptance criteria for each test, with no unacceptable cytotoxicity observed.

[0271] In-vivo testing ISO systemic toxicity in mice indicates that no systemic toxicity in mice is observed with lens extracts. ISO intraocular irritation studies in rabbits indicate that lens extracts are not considered irritants to rabbit ocular tissues. ISO intraocular irritation studies in rabbits indicate that IPC saline in packaging after autoclaving is not considered irritant to rabbit ocular tissues. Lenses worn continuously for 22 days in a daily disposable wear format are less irritating to the rabbit model, with eyes treated with test lenses being similar to eyes treated with control lenses. ISO sensitization studies (guinea pig maximization studies of packaging solutions) indicate that IPC saline after autoclaving does not cause delayed skin contact sensitization in guinea pigs. ISO sensitization studies (guinea pig maximization studies of lens extracts) indicate that sodium chloride and sesame oil extracts of lenses do not cause delayed skin contact sensitization in guinea pigs.

[0272] Genotoxicity Testing When IPC saline and SiHy lens extract from the lens package are tested in a microbial reverse mutation assay (Ames test), it is found that the lens extract and IPC saline appear to be non-mutagenic to Salmonella typhimurium tester strains TA98, TA100, TA1535 and TA1537 and Escherichia coli WPuvrA. When SiHy lens extracts are tested in a mammalian erythrocyte micronucleus assay, they have no clastogenic activity and are negative in a mouse bone marrow micronucleus test. When IPC saline from the lens package is tested according to the chromosomal aberration test in Chinese hamsters, the IPC saline is negative for the induction of structural and numerical chromosomal aberrations in an assay using CHO cells, in both the non-activated and S9 activated test systems. When SiHy lens extract is tested according to the cellular gene mutation test (mouse lymphoma mutagenesis assay), it is shown that the lens extract is negative in the mouse lymphoma mutagenesis assay.

[0273] Example 21 The surface compositions of pre-formed SiHy contact lenses (i.e., SiHy contact lenses without any coating and before the application of the PAA-based coating), SiHy contact lenses with PAA coatings (i.e., lenses before sealing in a lens package with IPC saline and autoclaving), and SiHy contact lenses with crosslinked coatings thereon, all of which were prepared according to the procedure described in Example 19, are determined by characterizing the vacuum-dried contact lenses with X-ray photoelectron spectroscopy (XPS). XPS is a method for measuring the surface composition of lenses at a sampling depth of about 10 nm. The surface compositions of the three types of lenses are reported in Table 6.

[0274] [Table 7]

[0275] Table 6 shows that when the PAA coating is applied onto the SiHy lens (preformed without coating), the silicon atomic composition is significantly reduced (from 12.1% to 4.5%) and the nitrogen atomic composition is also reduced (from 6.2% to 1.6%). When the crosslinked coating is further applied onto the PAA coating, the surface composition is dominated by three atomic compositions: carbon, nitrogen and oxygen (excluding hydrogen, since XPS does not count hydrogen in the surface composition). These results indicate that the outermost layer of the SiHy contact lens with crosslinked coating is likely to be composed essentially of a hydrophilic polymeric material that is the reaction product of poly(AAm-co-AA) (90 / 10) (60% C, 22% O and 18% N) and PAE.

[0276] The following commercially available SiHy lenses were also subjected to XPS analysis after being vacuum dried. The surface compositions of these commercially available SiHy contact lenses are reported in Table 7.

[0277] [Table 8]

[0278] The SiHy contact lens of the present invention is found to have a nominal silicon content of about 1.4% in the surface layer, which is significantly lower than commercial SiHy lenses without plasma coating (Acuvue® Advance®, Acuvue® Oasys®, TruEye™, Biofinity®, Avira™) and PureVision® (with plasma oxidation) and Premio™ (with unknown plasma treatment), and even lower than SiHy lenses with plasma deposition coating with a thickness of about 25 nm (N&D® Aqua™ and Air Optix® Aqua™). This extremely low Si% value is comparable to the silicon atomic% of the control sample Goodfellow's polyethylene (LDPE, d=0.015mm; LS356526SDS; ET31111512; 3004622910). These results indicate that the extremely low XPS analysis of the vacuum dried SiHy contact lenses of the present invention may be due to contaminants introduced during the preparation process, including the vacuum drying process and XPS analysis, as observed inclusion of fluorine in non-fluorine containing lenses. In the SiHy contact lenses of the present invention, the silicone is successfully shielded from XPS analysis.

[0279] XPS analysis is also performed on the SiHy contact lenses of the present invention (prepared according to the procedure described in Example 19), commercially available SiHy contact lenses (CLARITI™ 1 Day, ACUVUE® TruEye™ (narafilcon A and narafilcon B)), Goodfellow polyethylene sheet (LDPE, d=0.015 mm; LS356526 SDS; ET31111512; 3004622910), DAILIES® (polyvinyl alcohol hydrogel lenses, i.e., non-silicone hydrogel lenses), and ACUVUE® Moist (polyhydroxyethyl methacrylate hydrogel lenses, i.e., non-silicone hydrogel lenses). All lenses are vacuum dried. The polyethylene sheet, DAILIES®, and ACUVUE® Moist are used as controls since they do not contain silicon. The silicon atomic compositions in the surface layers of the test samples are as follows: 1.3±0.2 (polyethylene sheet); 1.7±0.9 (DAILIES®); 2.8±0.9 (ACUVUE® Moist); 3.7±1.2 (three SiHy lenses prepared according to the procedure described in Example 19); 5.8±1.5 (CLARITI™ 1 Day); 7.8±0.1 (ACUVUE® TruEye™ (narafilcon A); and 6.5±0.1 (ACUVUE® TruEye™ (narafilcon B)). The results of the SiHy contact lenses of the present invention are closer to conventional hydrogels than to silicone hydrogels.

[0280] Example 22 Fluorescein-labeled PAA (PAA-F) PAA-F is synthesized in-house by covalently attaching 5-aminofluorescein to PAA (Mw 450k). The degree of labeling with fluorescein is a few percent, e.g., about 2 mol % (or n / (m+n)=2% in the formula shown below). [ka]

[0281] 1. Preparation of Lenses Lenses are prepared by casting from the lens formulation prepared in Example 19 above in a reusable mold (quartz female half and glass male half) similar to the molds shown in U.S. Patent Nos. 7,384,590 (FIGS. 1-6) and 7,387,759 (FIGS. 1-6). The lens formulation in the mold is exposed to UV irradiation (13.0 mW / cm 2 ) and irradiate for approximately 24 seconds.

[0282] PAA-F coating solution A PAA-F coating solution is prepared by dissolving an amount of the above prepared PAA-F in a predetermined amount of 1-PrOH / water (95 / 5) solvent mixture to have a concentration of about 0.36% (by weight), and the pH is adjusted to about 2.0 with formic acid. About 5% water is used to dissolve the PAA-F.

[0283] PAA coated lens The cast contact lenses are extracted and coated by immersion in a series of baths: a DI water bath (~56 s); six MEK baths (~44, 56, 56, 56, 56, and 56 s, respectively); a DI water bath (~56 s); one PAA-F coating solution bath (~0.36% (by weight), acidified to pH ~2.0 with formic acid) in 1-PrOH / water (95 / 5) solvent mixture (~44 s); one water / 1-propanol 50% / 50% mixture bath (~56 s); four DI water baths for ~56 s each; one PBS bath for ~56 s; and one DI water bath for ~56 s.

[0284] Application of cross-linked coatings The lenses having the PAA-LbL base coating thereon prepared above are placed into polypropylene lens packaging shells (one lens per shell) with 0.6 mL of IPC saline (half of the saline is added prior to lens insertion) prepared according to the procedure described in Example 19. The blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes to produce SiHy contact lenses having a crosslinked coating (PAA-x-hydrophilic polymeric material) thereon.

[0285] Confocal laser scanning fluorescence microscopy A cross-section of a hydrated SiHy lens (prepared above) with a cross-linked coating is cut, placed between two glass cover slips, and imaged with a confocal laser fluorescence microscope (model #Zeiss LSM 510 Vis). The lens is scanned from the front curve side to the base curve side of the lens (and vice versa). The presence of PAA-F is indicated by green fluorescence and a confocal laser fluorescence microscope image can be obtained. Examination of the confocal laser fluorescence microscope image reveals that PAA-F rich layers are present on both lens surfaces (anterior and posterior) and at the peripheral edge, while no PAA-F is observed in the bulk material of the hydrated lens.

[0286] The fluorescence intensity profile is examined across the cross section of the lens along a line that traverses both the posterior and anterior surfaces and perpendicular to the posterior surface. Figure 3 shows two representative fluorescence intensity profiles along two lines traversing the lens cross section, one at a point where the lens is approximately 100 μm thick (Panel A) and the other at a point where the lens is approximately 200 μm thick (Panel B). The origin in Figure 3 is the midpoint between the anterior and posterior surfaces along that line. It can be noted in Figure 3 that there is a PAA-F rich layer near the outermost surface of the SiHy lens with the crosslinked coating, there is no PAA-F in the bulk of the lens, and the thickness of the coating is similar in these two cross sections regardless of the thickness of the cross section.

[0287] The thickness of the PAA-F rich layer (i.e., the sum of the injection depth into the outer hydrogel layer and the penetration depth of PAA-F into the bulk material (i.e., the inner layer)) or the transition layer (see FIG. 2 for a schematic diagram, transition layer 115) can be estimated from the fluorescence intensity profile shown in FIG. 3. The possible thickness of the transition layer (PAA-F rich layer) is estimated by the distance from zero intensity to zero intensity again after crossing the peak intensity. Considering possible contributions from unknown factors (such as scattering) to the fluorescence intensity, the minimum thickness of the layer is the thickness at which the fluorescence intensity of at least 10% of the maximum peak intensity is retained. Based on such predictions, the minimum thickness of the PAA-F rich layer would be at least about 5 microns. It should be noted that the thicker thickness of the SiHy lenses with PAA coating of the previous examples would be expected if the PAA concentration used was 10 times higher than the PAA-F concentration used in this example. Lenses with thicker coatings could also be prepared using a dip coating time longer than 44 seconds, which was the dip coating time of PAA-F used in this example. Lenses with thicker coatings can also be prepared using different molecular weight PAAs.

[0288] Example 23 This example illustrates a method for determining the water content of the crosslinked coating (two outer hydrogel layers) on the SiHy of the present invention. In an effort to determine the potential water content of the crosslinked coating of the SiHy lens of Example 19, a sample of the polymer composed of the coating components is prepared for evaluation. The resulting gel is then hydrated and tested to determine the water content.

[0289] A solution is prepared using the two polymeric components of the crosslinked coating formed in Example 19: poly(AAm-co-AA) (90 / 10) and PAE to have the following composition: 12.55% w / w PAE, 6.45% w / w poly(AAm-co-AA) (90 / 10) and 81% w / w water. The ratio of PAE / poly(AAm-co-AA) is the same as that of the IPC saline of Example 19, but the individual concentrations of the components are higher to ensure that a gel is formed during autoclaving.

[0290] The solution is then autoclaved at 121°C for approximately 45 minutes, after which the samples gel. Gel samples are then prepared for determining water content by testing the samples after hydration (n=3). Hydrated samples are prepared by soaking the gel samples in SoftWear saline for at least approximately 6 hours (i.e., hydrate overnight).

[0291] The hydrated samples are blotted dry and the hydrated mass is recorded according to mass balance. After the hydrated mass is recorded, all samples are placed in a vacuum oven set at approximately 50° C. and dried overnight under a vacuum of <1 inch Hg.

[0292] After drying overnight, the dried sample is removed from the vacuum oven and the dry mass is then measured and recorded. The moisture content is calculated using the following relationship: Moisture content = (wet mass - dry mass) / wet mass x 100% The moisture content of the sample is determined to be 84.6±0.4 w / w / %.

[0293] This water content of the PAE / poly(AAm-co-AA) hydrogel is believed to represent the outer hydrogel layer (crosslinked coating) of the SiHy contact lens of Example 19 for the following reasons: First, it is assumed to some extent that the hydrophobic bulk lens polymer (silicone hydrogel) is not present in the outer surface layer. This is believed to be a very good assumption based on the XPS data. According to the XPS data of Example 21, the surface of the SiHy lens with the crosslinked coating has zero or very low silicon content, which indicates that the outer surface layer is composed almost entirely of the coating polymers (PAE and PAAm-PAA). Second, the polyacrylic acid (PAA)-based coating (transition layer) probably has the least effect on the water content of the surface layer. This assumption may not be conclusive. However, if any charged PAA is present in the outer surface layer, the water content will increase further beyond 84.6%. Third, much higher concentrations of PAE and PAAm-PAA are required to produce the PAE / poly(AAm-co-AA) hydrogel than those used in the IPC saline solution of Example 19. This may result in a higher crosslink density of the PAE / poly(AAm-co-AA) hydrogel, giving an artificially low water content result. It is believed that both the presence of PAA in the outer hydrogel layer and the lower crosslink density may result in a surface layer (outer hydrogel layer) with a higher water content than that measured in the test of this example due to the lower concentration of polymeric material during crosslinking (in Example 19). It can be speculated that the outer coating layer of the SiHy contact lens of Example 19 contains at least 80% water, and may be even higher when fully hydrated.

[0294] Example 24 The Abbe refractometer is commonly used to measure the refractive index of contact lenses. The difference in refractive index between the test lens and the prism of the instrument creates a characteristic angle of total internal reflectance that produces a dark visible shadow line. The angle at which this shadow line appears is directly related to the refractive index of the test lens. Most contact lenses (including the uncoated SiHy contact lenses prepared in Example 19) produce a clear shadow line in the Abbe refractometer, but the SiHy with crosslinked coating (i.e., outer hydrogel layer) of Example 19 does not produce a clear shadow line. This phenomenon is believed to be due to the decrease in the refractive index of the lens at the surface compared to the bulk and the fact that the transition from bulk to surface is not abrupt. Furthermore, it is believed that the water content begins to increase near the surface of the lens, locally decreasing the refractive index of the lens. This would actually result in multiple angles of shadow lines simultaneously, resulting in a blurred image of the shadow line.

[0295] The Abbe data demonstrate that the outer surface layer is characterized by an increase in water content near the surface of the lens, consistent with the results described in Example 23.

[0296] Example 25 SiHy contact lenses with crosslinked coating (i.e., outer hydrogel layer) prepared in Example 19 are demineralized in ultrapure water and frozen by placing them individually in 50 mL disposable beakers with 50 mL of ultrapure water and placing the beaker in a bath containing dry ice and isopropyl alcohol. The beaker is wrapped in aluminum foil and placed on a VirTis Freezemobile 35EL with a vacuum pressure of 30 μbar and a condenser temperature of -70°C. After 24 hours, the aluminum foil is removed to increase heat transfer and the flask is left for another 24-48 hours to remove residual moisture. The flask is sealed to prevent the ingress of moisture from the air until analysis. The lens sample is cut in half, and then two sections are cut from the center of each and their edges are fixed to image the cross section. The sample is then sputter coated with Au / Pd for about 1 minute and examined by SEM using a Bruker Quantax Microanalysis System (JEOL JSM-800LV SEM). Tilt the sample stage approximately 0-60° at the analyst's discretion to obtain the desired sample orientation.

[0297] It is believed that when the SiHy contact lens is freeze-dried, the hydrated surface structure of the lens may be preserved or fixed to some extent. Panel A of FIG. 4 shows a top view of an SEM image of the surface of the freeze-dried SiHy contact lens prepared in Example 19. It is clear from FIG. 4 that the freeze-dried SiHy contact lens has a sponge-like surface structure that is expected for a high water content hydrogel. Furthermore, the results confirm that the SiHy contact lens of the present invention comprises two outer hydrogel layers of high water content hydrogel. Panels B and C of FIG. 4 show side views at two different angles of the cross section of the freeze-dried SiHy contact lens shown in Panel A. Panels B and C show a thick inner layer with a smooth surface, a lighter colored transition layer (PAA layer) on top of the inner layer, and an outer hydrogel layer with a sponge-like structure on top of the transition layer. From the data shown in Panels B and C, the thickness of the freeze-dried outer hydrogel layer is estimated to be about 2 μm to 2.5 μm.

[0298] Example 26 Fluorescein-labeled poly(AAm-co-AA) (90 / 10) (referred to as PAAm-PAA-F) PAAm-PAA-F is synthesized in-house by covalently attaching 5-aminofluorescein to PAAm-PAA (90 / 10) through a procedure similar to the preparation of PAA-F. Poly(AAm-co-AA) (90 / 10) partial sodium salt (~90% solids content, poly(AAm-co-AA) 90 / 10, Mw 200,000) is purchased from Polysciences, Inc. and used as received. The degree of labeling of fluorescein is approximately 0.04 mol%.

[0299] IPC saline modified with PAAm-PAA-F This saline solution is prepared by the same IPC preparation procedure as described in Example 19, except that PAAm-PAA is replaced with PAAm-PAA-F.

[0300] PAA coated lens Lenses are prepared by casting from the lens formulation prepared in Example 19 above into reusable molds (quartz female half and glass male half) similar to those shown in U.S. Patent Nos. 7,384,590 (FIGS. 1-6) and 7,387,759 (FIGS. 1-6). The lens formulation in the mold is exposed to UV irradiation (13.0 mW / cm 2 ) for about 24 seconds. The cast contact lenses are extracted and coated by immersion in a series of baths: a DI water bath (about 56 seconds); six MEK baths (about 44, 56, 56, 56, 56, and 56 seconds, respectively); a DI water bath (about 56 seconds); one PAA coating solution in 1-PrOH solvent (about 0.36% by weight, acidified to pH about 2.0 with formic acid) bath (about 44 seconds); one water / 1-propanol 50% / 50% mixture bath (about 56 seconds); four DI water baths for about 56 seconds each; one PBS bath for about 56 seconds; and one DI water bath for about 56 seconds.

[0301] Application of cross-linked coatings The lenses having the PAA-based coating thereon prepared above are placed into polypropylene lens packaging shells (one lens per shell) with 0.6 mL of modified IPC saline (half of the saline is added prior to lens insertion) prepared above with PAAm-PAA-F. The blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes to produce SiHy contact lenses having a crosslinked coating (PAA-x-hydrophilic polymeric material) thereon.

[0302] Confocal laser scanning fluorescence microscopy One hydrated SiHy lens with crosslinked coating (prepared above) is placed between two glass cover slips and imaged with a confocal laser fluorescence microscope (model # Zeiss LSM 510 Vis). The lens is scanned from the front curve side to the base curve side of the lens (and vice versa). The presence of PAAm-PAA-F is indicated by green fluorescence and a confocal laser fluorescence microscope image can be obtained. Examination of the confocal laser fluorescence microscope image reveals that a PAAm-PAA-F rich layer (i.e., outer hydrogel layer) is present on both lens surfaces (anterior and posterior) and at the peripheral edge, while no PAAm-PAA-F is observed in the bulk material of the lens.

[0303] The fluorescence intensity profile is examined across the cross section of the lens, across both the posterior and anterior surfaces, and along a line perpendicular to the posterior surface. The thickness of the PAAm-PAA-F rich layer can be estimated from the fluorescence intensity profile across the lens. The possible thickness of the outer hydrogel layer (PAAm-PAA-F rich layer) is estimated by the distance from zero intensity, across the peak intensity, and back to zero intensity again. Taking into account possible contributions from unknown factors (such as scattering) to the fluorescence intensity, the minimum thickness of the layer is the thickness at which a fluorescence intensity of at least 10% of the maximum peak intensity is retained. Based on such predictions, the minimum thickness of the PAAm-PAA-F rich layer (hydrated outer hydrogel layer) would be at least about 5 microns.

[0304] Example 27 Lenses are made using lens formulation D-2 (Example 17) with APMAA monomer added to a concentration of 1%. LS lenses are prepared from the lens formulation prepared above by cast molding in a reusable mold similar to those shown in U.S. Patent Nos. 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The mold includes a female half made of glass and a male half made of quartz. The UV radiation source is at an intensity of approximately 4.6 mW / cm with a 380 nm cutoff filter. 2 The lens formulation in the mold is exposed to UV radiation for approximately 30 seconds.

[0305] The cast lenses are extracted with methyl ethyl ketone (MEK), rinsed with water, and coated with polyacrylic acid (PAA) by immersing the lenses in a propanolic solution of PAA (0.0044% by weight, acidified to pH approx. 2.5 with formic acid) and hydrated with water.

[0306] IPC saline is prepared according to the composition described in Example 9 with pre-reaction conditions at about 60° C. for 8 hours. The lenses are placed in polypropylene lens packaging shells with 0.6 mL of IPC saline (half of the saline is added before the lens is inserted). The blisters are then sealed with aluminum foil and autoclaved at 121° C. for 30 minutes.

[0307] Evaluation of the lens surface shows that all test lenses are free of debris adhesion. No cracking lines are visible after rubbing the lenses between fingers when observed under a dark field microscope. The wettability (WBUT) of the lens surface is greater than 10 seconds, the lubricity is rated as "1", and the contact angle is about 20°.

[0308] Example 28 Cast molded SiHy contact lenses (without any coating) prepared from Example 19 are used. All lenses are extracted overnight in MEK to ensure that all residual monomers are removed. The first group of lenses (lenses having a hydrated crosslinked coating thereon) are soaked overnight in a PAA coating solution (0.36% (by weight) PAA in 1-propanol, adjusted to pH 1.7-2.3 with formic acid) and the second group of lenses (control) are soaked in 1-propanol for the same period of time. Both groups of lenses are packaged in IPC saline prepared in Example 19 and autoclaved. The lenses are tested (in five groups) after autoclaving using gravimetric techniques to determine the weights of the dry and wet contact lenses (for the first group of contact lenses, N=14; for the second group of contact lenses, N=18). The results are shown in Table 8.

[0309] [Table 9]

[0310] There is a statistically significant difference (7 mg) in wet weight between the first and second contact lens groups due to the presence of the hydrated cross-linked coating in the contact lenses versus the control lenses (no coating). However, the difference in dry weight between the first and second contact lens groups is approximately 0.3 mg, which is not statistically significant. The lens water content of the coated lenses can be estimated to be ~96% according to the following calculation:

number

[0311] Example 29 This example describes how to quantify the lubricity of SiHy contact lenses according to the inclined plate method ("Derby friction test"). The inclined plate method is a simple test with the setup shown in Figure 5. The inclined plate setup consists of a plastic reservoir or tank 501 filled with phosphate buffered saline (PBS, pH ~ 7.3) 502, a borosilicate glass plate 503, and a shim 506 with an adjustable height between 5mm and 20mm high. Both the borosilicate glass plate 503 and the shim 506 are immersed in the phosphate buffered saline 502 in the plastic reservoir or tank 501. For the test, a contact lens 504 is placed on the borosilicate glass plate, which in turn is topped with a stainless steel ferrule 505 (to provide physiologically relevant pressure). The critical coefficient of friction = F t / F N = tan θ (where θ is the critical angle and F N is the normal force, F t is the tangential force). The highest angle at which the lens continues to slide after being pushed but takes more than 10 seconds before stopping or reaching an edge is defined as the "critical angle θ". The critical coefficient of friction (CCOF) is the tangent of the critical angle θ. A lens that does not move does not exceed the CCOF, and a lens that does not stop between travel distances exceeds the CCOF. Angles that do or do not exceed the CCOF are excluded from the analysis. The Derby friction test can provide a direct method of measuring the kinetic coefficient of friction.

[0312] For tilted plate testing, store all lenses in PBS solution at least overnight (>6 hours) prior to testing to remove any residual packaging solution. Clean glass plates (6” x 4” borosilicate glass) with soapy water (1% Micro-90) and wipe (AlphaWipe TX1009). Rinse each plate thoroughly with DI water for approximately 2 minutes. Check the resistance of the plate cross section by rubbing with a finger to ensure all soapy water is removed. Wipe off the water with a paper towel (KimTech Kimwipe #34705) and inspect under a light for any foreign material remaining on the glass. Place the glass plate on shims of various heights in a plastic reservoir or tank and measure and record the height of this surface with a micrometer. Fill the reservoir with phosphate buffered saline (PBS) so that the lenses are completely immersed (28mm deep).

[0313] Place each lens on the "start line" and place a 0.79 g ferrule (1 / 4" stainless steel, to provide physiologically appropriate pressure) on the lens surface. Allow the lens to slide down the plate and record the time it takes for the lens to travel 96 mm.

[0314] Before retesting, the weight is removed and the lens is allowed to move to the starting position. This "preload" effect should be minimized for best reproducibility. Lenses can be tested at multiple angles to obtain the ideal CCOF.

[0315] Sixteen commercially available contact lenses and the silicone hydrogel contact lenses prepared in Example 19 were tested for CCOF and the results are reported in Table 9. The results show that the SiHy contact lenses of the present invention (prepared in Example 19 to have a crosslinked coating thereon) have the lowest CCOF and therefore the best lubricity among the commercially available and all classes of silicone hydrogel lenses tested.

[0316] [Table 10]

[0317] Example 30 This example describes how to characterize the negatively charged surface of a SiHy contact lens according to a positively charged particle adhesion test.

[0318] The surface charge of the lens surface can be detected indirectly through interaction with charged particles or beads. A negatively charged surface will attract positively charged particles. A surface with no or substantially no negative charge will not attract positively charged particles or will attract only small amounts of positively charged particles.

[0319] Uncoated SiHy contact lenses (i.e., cast and MEK extracted as described in Example 19), PAA-coated SiHy contact lenses (as prepared in Example 19), and SiHy contact lenses having crosslinked coatings thereon (as prepared in Examples 14 and 19) are tested as follows. The PAA coating of the PAA-coated contact lenses has a surface concentration of carboxylic acid groups of about 62.5% (by weight) (M COOH / M AA )(where M COOH is the mass of the carboxylic acid group, and M AA (wherein m is the mass of acrylic acid). The crosslinked coating of the contact lens of Example 14 theoretically does not contain carboxylic acid groups, whereas the crosslinked coating of the contact lens of Example 19 theoretically contains a low surface concentration of carboxylic acid groups.

number

[0320] DOWEX™ 1×4 20-50 mesh resin is purchased from Sigma-Aldrich and used as received. DOWEX™ 1×4 20-50 mesh resin is a spherical type I strong base anion resin, N + (CH3)3Cl -It is a styrene / divinylbenzene copolymer containing functional groups and 4% divinylbenzene. 5% 1x4 20-50 mesh resin is dispersed in PBS and mixed thoroughly by stirring or vortexing at about 1000 rpm for 10 seconds. The lens is immersed in this dispersion and vortexed at 1000-1100 rpm for 1 minute, then rinsed with DI water and vortexed for 1 minute. The lens is then placed in water in a glass Petri dish and images of the lens are taken using bottom illumination with a Nikon optical microscope. As shown in Figure 6, almost the entire surface of the PAA coated lens is covered with attached positively charged particles (Figure 6a), whereas on the lens with the crosslinked coating prepared in Example 19, a total of about 50 positively charged particles are attached (Figure 6B), and on the lens with the crosslinked coating prepared in Example 14, no positively charged particles are attached (Figure 6C). Some weakly attached particles fall off the lens surface and can be found in the water surrounding the lens.

[0321] It should be understood that the number of particles attached on the particles may be reduced if positively charged particles with larger size (i.e., DOWEX™ monosphere ion exchange resin, cross-linked polystyrene beads, chloride form, ∼590 micron size, Sigma-Aldrich) are used in the test. Approximately 30% of these DOWEX monosphere resins are dispersed in PBS. The lenses are immersed in this dispersion for about 1 minute and then rinsed with DI water. The lenses are then placed in water in a glass Petri dish and images of the lenses are taken using bottom illumination with a Nikon optical microscope. It is found that many particles (approximately 200 particles) are attached on the PAA coated lenses and no particles are attached on the lenses with cross-linked coating. Some commercially available contact lenses are also tested. No particles are observed on the following lenses: Acuvue® TruEye™, Acuvue® Advance®, Acuvue® Oasys®, Avira™, Biofinity®, Air Optix®, and Focus® Night&Day®. Particles are observed on four lenses (in order of increasing particle count): PureVision®, 1 Day Acuvue® Moist®, Proclear 1 day, and Acuvue® (Etafilcon A) lenses. Almost the entire surface of the Acuvue® (Etafilcon A) lens is covered with attached positively charged particles.

[0322] Negatively charged resin (Amberlite CG50) is purchased from Sigma and used as is. 5% of the Amberlite CG50 beads are dispersed in PBS and vortexed at approximately 1000 rpm for 10 seconds. A PAA-coated lens is immersed in this dispersion and vortexed at 1000-1100 rpm for 1 minute, then rinsed with DI water and vortexed for 1 minute. The lens is then placed in water in a glass Petri dish and an image of the lens is taken using bottom illumination with a Nikon optical microscope. No Amberlite particles (negatively charged) are found on the PAA-coated lens.

[0323] Negatively charged beads (Amberlite CG50) coated with polyethyleneimine (PEI, a positively charged electrolyte) are used in this experiment. The PEI coating procedure is performed as follows: PEI (Lupasol SK, 24% aqueous solution, Mw~2000000) is purchased from BASF and used as received. An aqueous dispersion of 1% Amberlite particles and 5% PEI is prepared. The pH is adjusted to 7 and the solution is mixed thoroughly (e.g., stirred for 30 min). The dispersion is then suspended in large amounts of water 2-3 times and filtered 2-3 times to collect the particles (PEI-coated Amberlite). 5% of the PEI-coated Amberlite CG50 particles are dispersed in PBS and vortexed at approximately 1000 rpm for 10 seconds. Lenses are immersed in this dispersion and vortexed at 1000-1100 rpm for 1 minute, then rinsed with DI water and vortexed for 1 minute. The lens is then placed in water in a glass Petri dish and images of the lens are taken using bottom illumination with a Nikon optical microscope. A large amount of PEI-coated Amberlite particles (positively charged particles, due to the presence of PEI) are observed to be attached on the PAA-coated lens (Example 19). However, substantially no PEI-coated Amberlite particles are attached on the uncoated SiHy contact lens (Example 19), the SiHy contact lens with a crosslinked coating (Example 19), or the PAExPAA-coated lens (Example 4).

[0324] Example 31 Sample preparation: AFM studies were performed on hydrated and dry SiHy contact lenses (prepared in Example 19). The lens is removed from its blister pack (sealed and autoclaved) and a cross section is cut (e.g., using a razor blade). The cross section of the lens is placed vertically in a metal clamp as shown in Figure 7. A small piece of the lens protrudes from the top of the holder and the lens is scanned with the AFM tip (on the lens cross section in Figure 7).

[0325] AFM Experiments: Two separate AFM instruments are used to characterize the lens cross-sections: In both cases (other than the dry samples), AFM scans are performed in phosphate buffer (PBS with or without NaCl, but with substantially the same osmolarity as physiological saline) in order to keep the hydrogel samples fully hydrated.

[0326] The first AFM instrument is a Veeco BioScope AFM with a Nanoscope IV controller. Data are collected using triangular silicon cantilevers with a spring constant of 0.58 N / m and a nominal tip radius of curvature of 20-60 nm. Scanning is performed in continuous contact (force-volume) mode with a probe speed of 30 microns / sec and a force-volume scanning frequency of 0.19 Hz. Topographic and force-volume data are collected simultaneously. Each force curve consists of approximately 30 data points. During the AFM scan, the lens is fully immersed in PBS. To achieve a sufficiently high resolution to obtain force-volume images, a maximum scan size of 20 microns is typically used. 128 x 128 pixel force plots are collected over approximately 3 hours per image.

[0327] An AFM image of a cross-section of a SiHy contact lens (Example 19) with a cross-linked coating in a fully hydrated state was obtained by force-volume techniques and is shown in Figure 8. In the image, the darker areas 420 represent the coating and the lighter areas 410 represent the bulk material of the lens. The average thickness of the cross-linked coating (i.e., the anterior and posterior outer layers) of the SiHy contact lens (Example 19) is determined to be about 5.9 μm (standard deviation 0.8 μm) as obtained from seven images of four lenses.

[0328] AFM techniques allow the determination of the surface modulus (surface flexibility) of a particular location on the cross-section of the lens. Figure 9 shows the cross-sectional surface modulus profile of a SiHy contact lens (prepared in Example 19) with a cross-linked coating in a fully hydrated state. Since the surface modulus of a material is proportional to the cantilever deflection, the cross-sectional surface modulus profile of the contact lens can be approximately obtained by plotting the cantilever deflection value (as a measure of the surface modulus of a material at a particular location on the cross-section of the lens) as a function of distance from the side of the cross-section (front or back) along two lines that cross the cross-section shown in Figure 8. As shown in Figure 9, the cross-linked coating (front and back outer layers of the contact lens of Example 19) is softer than the bulk (inner layer) silicone hydrogel lens material. Moving along the two lines, the surface modulus initially remains nearly constant over the area from 0 to about 5.9 microns with an average cantilever deflection (i.e., average surface modulus) of about 52 nm, then gradually increases until it reaches a maximum further inside the lens, and then remains nearly constant (plateau) over an area of ​​more than about 7 microns with an average cantilever deflection (i.e., average surface modulus) of about 91. The transition from the softer crosslinked coating to the stiffer bulk SiHy material occurs gradually over a range of several microns, indicating that a morphology or composition (water content) gradient may exist between the surface of the coating and the bulk of the lens. The surface modulus of the area from 5.9 microns to about 7 microns, i.e., the area near the boundary between the outer hydrogel layer and the inner layer of silicone hydrogel material, is not used in the calculation of the average surface modulus. The anterior and posterior outer hydrogel layers (crosslinked coatings) of the SiHy contact lens (Example 19) exhibited a surface modulus that was reduced by about 43%.

number

number

number

[0329] SiHy contact lenses (prepared in Example 19) are studied with a second AFM instrument. Scans are performed with a Bruker Icon AFM in quantitative nanomechanical measurement (PeakForce QNM) mode using lenses either fully hydrated (PBS without NaCl but containing glycerol to achieve similar osmolality) or dry. Lens cross sections are placed in metal clamps as described above. Test conditions include a spring constant of 1.3 N / m, a tip radius of 33.3 nm, a sensitivity of 31 nm / V, a scan frequency of 0.4 Hz, and a scan resolution of 512 x 512.

[0330] AFM images of the cross-sections of the SiHy contact lens (Example 19) in the fully hydrated and dry states are obtained according to the PeakForce QNM method. By analyzing the obtained images, the thickness of the cross-linked coating in the fully hydrated state is determined to be about 4.4 microns, while the thickness of the cross-linked coating in the dry state is determined to be about 1.2 microns for the vacuum dried sample and about 1.6 microns for the oven dried sample. The water swelling coefficient L of the cross-linked coating of the SiHy contact lens (prepared in Example 19) is about 1.2 microns for the vacuum dried sample and about 1.6 microns for the oven dried sample. wet / L Dry ×100% (in the formula, L Wet is the average thickness of the outer hydrogel layer of a SiHy contact lens in a fully hydrated state, and L Dry is the average thickness of the outer hydrogel layer of the SiHy contact lenses in the dry state, is calculated to be about 277% (oven dried samples) or about 369% (vacuum dried samples).

[0331] Example 32 Preparation of Lens Formulations Formulation I is prepared by dissolving the components in 1-propanol to have the following composition: 33% (wt) CE-PDMS macromer prepared in Example 2, 17% (wt) N-[tris(trimethylsiloxy)-silylpropyl]acrylamide (TRIS-Am), 24% (wt) N,N-dimethylacrylamide (DMA), 0.5% (wt) N-(carbonyl-methoxypolyethylene glycol-2000)-1,2-distearoyl-sn-glycero-3-phosphoethanolamine, sodium salt) (L-PEG), 1.0% (wt) Darocur 1173 (DC1173), 0.1% (wt) visitint (5% copper phthalocyanine blue pigment dispersion in tris(trimethylsiloxy)silylpropyl methacrylate (TRIS)), and 24.5% (wt) 1-propanol.

[0332] Formulation II is prepared by dissolving the components in 1-propanol to have the following composition: about 32% (wt) CE-PDMS macromer prepared in Example 2, about 21% (wt) TRIS-Am, about 23% (wt) DMA, about 0.6% (wt) L-PEG, about 1% (wt) DC1173, about 0.1% (wt) visitint (5% copper phthalocyanine blue dye dispersion in TRIS), about 0.8% (wt) DMPC, about 200 ppm H-tempo, and about 22% (wt) 1-propanol.

[0333] 1. Preparation of Lenses Lenses are prepared from the lens formulations prepared above by casting in reusable molds (quartz female half and glass male half) similar to those shown in U.S. Patents 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The UV radiation source is an intensity of approximately 4 mW / cm with a WG335+TM297 cutoff filter. 2 The lens formulation in the mold is exposed to UV radiation for approximately 25 seconds. The cast lenses are extracted with methyl ethyl ketone (MEK) (or propanol or isopropanol).

[0334] Application of PAA prime coating on SiHy contact lenses A polyacrylic acid coating solution (PAA-1) was prepared by dissolving an amount of PAA (MW: 450 kDa, Lubrizol) in a given amount of 1-propanol to have a concentration of about 0.36% (by weight), and the pH was adjusted to about 2.0 with formic acid.

[0335] Another PAA coating solution (PAA-2) was prepared by dissolving an amount of PAA (MW: 450 kDa, Lubrizol) in a volume of organic solvent (50 / 50 1-propanol / HO) to have a concentration of about 0.39% (by weight) and adjusting the pH to about 2.0 with formic acid.

[0336] The SiHy contact lenses obtained above are subjected to one of the immersion processes shown in Tables 10 and 11.

[0337] [Table 11]

[0338] [Table 12]

[0339] Application of cross-linked hydrophilic coating Poly(acrylamide-co-acrylic acid) partial sodium salt, poly(AAm-co-AA)(90 / 10) (~90% solids content, poly(AAm-co-AA) 90 / 10, Mw 200,000) was purchased from Polysciences, Inc. and used as received. PAE (Kymene, azetidinium content 0.46 by NMR assay) was purchased from Ashland as an aqueous solution and used as received. In-package crosslinking (IPC) saline is prepared by dissolving about 0.07% w / w poly(AAm-co-AA) (90 / 10) and about 0.15% PAE (about 8.8 mmol initial azetidinium millimole equivalents) in phosphate buffered saline (PBS) (about 0.044 w / w% NaH2PO4·H2O, about 0.388 w / w / % Na2HPO4·2H2O, about 0.79 w / w% NaCl) and adjusting the pH to 7.2-7.4. The IPC saline is then heat pretreated at about 70 °C for about 4 h (heat pretreatment). During this heat pretreatment, poly(AAm-co-AA) and PAE are partially crosslinked with each other (i.e., not all azetidinium groups of PAE are consumed) to form a water-soluble and thermally crosslinkable hydrophilic polymeric material containing azetidinium groups within a branched polymer network in the IPC saline. After heat pretreatment, the IPC saline is filtered using a 0.22 micron polyethersulfone [PES] membrane filter and cooled back to room temperature. Next, 10 ppm hydrogen peroxide is added to the final IPC saline to prevent bioburden buildup, and the IPC saline is filtered using a 0.22 micron polyethersulfone [PES] membrane filter.

[0340] The lenses having the PAA prime coating thereon prepared above are placed into polypropylene lens packaging shells (one lens per shell) with 0.6 mL of IPC saline (half of the saline is added prior to lens insertion). The blisters are then sealed with aluminum foil and autoclaved at about 121° C. for about 30 minutes to produce SiHy contact lenses having a crosslinked hydrophilic coating thereon.

[0341] Characterization of SiHy lenses The resulting SiHy contact lens having a center thickness of about 0.95 microns and having a crosslinked hydrophilic coating thereon has an oxygen permeability (Dk) of about 142 to about 150 barrer. c or estimated specific Dk), a bulk surface modulus of about 0.72 to about 0.79 MPa, a water content of about 30% to about 33% (by weight), a relative ion permeability of about 6 (relative to Alsacon lenses), and a contact angle of about 34 to about 47 degrees.

[0342] Characterization of nanotextured surfaces of contact lenses Transmission Differential Interference Contrast (TDIC) The contact lens is placed on a glass slide and flattened by compressing the lens between the slide and a glass cover slip. The surface of the contact lens is placed and examined using a Nikon ME600 microscope with transmitted differential interference contrast optics by focusing through the lens using a 40x objective. The resulting TDIC image is then evaluated to determine the presence of winkled surface patterns (e.g., random and / or ordered worm patterns, etc.).

[0343] Reflective Differential Interference Contrast (RDIC) The lens is placed on a glass slide and flattened to create four squares approximately every 90 degrees. Excess saline is blown off the surface using compressed air. The lens surface is examined using 10x, 20x and 50x objectives using a Nikon Optiphot-2 reflective differential interference contrast optical system, if wrinkled surface patterns are present on the contact lens surface. A representative image of each slide is taken using the 50x objective. The contact lens is then turned over, excess saline is removed and the other side of the contact lens is similarly examined. The resulting RDIC images are then evaluated to determine the presence of wrinkled surface patterns (e.g., random and / or ordered worm-like patterns, etc.).

[0344] Dark-field optical microscopy (DFLM) DFLM is generally based on dark-field illumination and is a method to enhance the contrast of the observed sample. This technique consists of a light source outside or obscured from the observer's field of view to illuminate the sample at an angle relative to the normally transmitted light. Since the unscattered light from the light source is not collected by the objective lens, it is not part of the image and the image background appears dark. When the light source illuminates the sample at an angle, the light observed in the sample image is that which is scattered by the sample towards the observer, and then a contrast is created between this scattered light from the sample and the dark background of the image. This contrast effect results in dark illumination, which is particularly useful for observing scattering phenomena such as haze.

[0345] DFLM is used to evaluate the haze of contact lenses as follows. It is believed that dark field data can provide the worst assessment of haze because the dark field setup includes scattered light. In an 8-bit grayscale digital image, each image pixel is assigned a grayscale intensity (GSI) value ranging from 0 to 255. Zero represents a pixel that is completely black and 255 represents a pixel that is completely white. An increase in scattered light captured in the image will produce a pixel with a higher GSI value. This GSI value can then be used as a function to quantify the amount of scattered light observed in the dark field image. Haze is represented by averaging the GSI values ​​of all pixels in an area of ​​interest (AOI) (e.g., the entire lens or a lenticular zone or optic of the lens). The experimental setup consists of a microscope or equivalent optics, an attached digital camera, and a dark field stand with a ring light and a variable intensity light source. The optics are designed / positioned such that the entire contact lens being observed falls within the field of view (typically a field of view of ~15mm x 20mm). Illumination is set to an appropriate level to observe the desired changes in the relevant sample. Light intensity is adjusted / calibrated to the same level for each set of samples using density / light scattering standards as known to those skilled in the art. For example, a standard consists of two overlapping plastic cover glasses (homogeneous and slightly or moderately hazy). Such a standard is composed of areas with three different average GSIs, including two areas with intermediate grayscale levels and saturated white (edges). The black area represents the empty dark field. The black and saturated white areas can be used to verify the gain and offset (contrast and brightness) settings of the camera. The intermediate gray levels can provide three points to verify the linear response of the camera. Light intensity is adjusted so that the average GSI of the empty dark field reaches 0 and the average GSI of the defined AOI in the digital image of the standard is the same every time within ±5 GSI units. After calibrating the light intensity, the contact lens is immersed in 0.2 μm filtered phosphate buffered saline in a quartz Petri dish or a dish of similar transparency placed on the DFLM stand.An 8-bit grayscale digital image of the lens is then visually acquired using calibrated lighting, and the average GSI of a defined AOI within the portion of the image containing the lens is determined. This is repeated for each sample set of contact lenses. Light intensity calibration is periodically re-evaluated throughout the test to ensure consistency. The level of haze under DFLM testing refers to the DFLM haze GSI / 255×100%.

[0346] PAA prime coated SiHy contact lenses obtained according to either of the immersion processes 20-0 and 80-0 were determined to have an average DFLM haze of about 73% and exhibit a wrinkled surface pattern (random worm-like pattern) that can be visually observed by examining the contact lenses in a hydrated state according to either the RDIC or TDIC method as described above. However, the wrinkled surface pattern has no actual detrimental effect on the light transmission of the contact lenses.

[0347] PAA prime coated SiHy contact lenses obtained according to any of immersion processes 20-1 through 20-4 were determined to have a low average DFLM haze of about 26% (probably due to the presence of visitint pigment particles) and did not exhibit a noticeable wrinkled surface pattern (random worm-like pattern) when tested in either the RDIC or TDIC as described above.

[0348] SiHy contact lenses with a high percentage of PAA prime coating obtained according to any of the immersion processes 20-5 were determined to have a moderate average DFLM haze of about 45% and exhibit a slightly noticeable wrinkled surface pattern when tested in either the RDIC or TDIC as described above, however, the wrinkled surface pattern has no actual detrimental effect on the light transmission of the contact lenses.

[0349] PAA primed SiHy contact lenses obtained according to any of the immersion processes 80-1, 80-2, 80-3, 80-5 and 80-6 do not exhibit a noticeable wrinkled surface pattern when tested in either RDIC or TDIC as described above. However, PAA primed SiHy contact lenses obtained according to any of the immersion processes 80-0 and 80-4 exhibit a noticeable wrinkled surface pattern when tested in either RDIC or TDIC as described above. However, the wrinkled surface pattern does not have any practical detrimental effect on the light transmission of the contact lenses.

[0350] Example 33 Synthesis of UV-absorbing amphiphilic branched-chain copolymers A 1 L jacketed reactor is equipped with a 500 mL addition funnel, overhead stirrer, reflux condenser with nitrogen / vacuum inlet adapter, thermometer and sampling adapter. 89.95 g of 80% partially ethylenically functionalized polysiloxane prepared in Example 17-A is charged to the reactor, then degassed at room temperature for about 30 minutes under a vacuum of less than 1 mbar. A monomer solution prepared by mixing 1.03 g of HEMA, 50.73 g of DMA, 2.76 g of Norbloc methacrylate, 52.07 g of TRIS and 526.05 g of ethyl acetate is charged to the 500 mL addition funnel, then degassed at room temperature for 10 minutes under a vacuum of 100 mbar and then backfilled with nitrogen gas. The monomer solution is degassed for two more cycles under the same conditions. The monomer solution is then charged to the reactor. The reaction mixture is heated to 67° C. with moderate stirring. With heating, a solution consisting of 2.96 g mercaptoethanol (chain transfer agent, CTA) and 0.72 g dimethyl 2,2'-azobis(methyl 2-propionate) (V-601-initiator) and 76.90 g ethyl acetate is charged to the addition funnel, followed by the same degassing process as the monomer solution. When the reactor temperature reaches 67°C, the initiator / CTA solution is also added to the reactor. The reaction is carried out at 67°C for 8 hours. After the copolymerization is complete, the reactor temperature is cooled to room temperature.

[0351] Synthesis of UV-absorbing amphiphilic branched-chain prepolymers The copolymer solution prepared above is ethylenically functionalized by adding 8.44 g of IEM (or the desired molar equivalent of 2-isocyanatoethyl methacrylate) in the presence of 0.50 g of DBTDL to form an amphiphilic branched prepolymer. The mixture is stirred at room temperature for 24 hours under sealed conditions. The prepared prepolymer is then stabilized with 100 ppm of hydroxy-tetramethylenepiperonyloxy, after which the solution is concentrated to 200 g (~50%) and filtered through a 1 μm pore size filter paper. After exchanging the reaction solvent with 1-propanol through repeated cycles of evaporation and dilution, the solution is ready for use in formulations. The solids content is measured by removing the solvent in a vacuum oven at 80 °C.

[0352] Preparation of Lens Formulations A lens formulation is prepared having the following composition: 71% (by weight) of the prepolymer prepared above; 4% (by weight) DMA; 1% (by weight) TPO; 1% (by weight) DMPC; 1% (by weight) Brij 52 (Sigma-Aldrich) and 22% (by weight) 1-PrOH.

[0353] 1. Preparation of Lenses Lenses are made by cast molding of the lens formulation prepared above using spatially restricted UV irradiation in a reusable mold similar to those shown in U.S. Patents 7,384,590 (Figures 1-6) and 7,387,759 (Figures 1-6). The mold includes a female half made of glass and a male half made of quartz. The UV irradiation source has an intensity of about 4.6 mW / cm with a 380 nm cutoff filter. 2 The lens formulation in the mold is exposed to UV radiation for approximately 30 seconds.

[0354] The cast lenses are extracted with methyl ethyl ketone (MEK), rinsed with water, and coated with polyacrylic acid (PAA) by immersing the lenses in a solution of PAA in propanol (0.004% by weight, acidified to pH approx. 2.0 with formic acid) and hydrated with water.

[0355] The IPC saline is prepared under pre-reaction conditions at about 60° C. for 6 hours from a composition containing about 0.07% PAAm-PAA and sufficient PAE (~0.15% PAE) to provide an initial azetidinium content of about 8.8 millimole equivalents / liter. 5 ppm hydrogen peroxide is then added to the IPC saline to prevent bioburden buildup, and the IPC saline is filtered using a 0.22 micron polyethersulfone [PES] membrane filter. The lens is placed in a polypropylene lens packaging shell with 0.6 mL of IPC saline (half of the saline is added prior to lens insertion). The blister is then sealed with aluminum foil and autoclaved at 121° C. for 30 minutes.

[0356] Lens characterization The resulting lens has the following properties: E'~0.82MPa; DK c ~159.4 (mean central thickness of 80 μm and specific Dk110, using lotrafilcon B as the reference lens); IP~2.3; Water%~26.9; and UVA / UVB %T~4.6 / 0.1. No cracking lines are visible after rubbing the test lenses when viewed under a dark field microscope. The lenses are very smooth, comparable to the control lenses in the finger rub test.

Claims

1. a front surface and an opposite rear surface; and 1. A hydrated silicone hydrogel contact lens comprising a layered structure shape from anterior to posterior surface, the layered configuration includes a front outer hydrogel layer, an inner layer of silicone hydrogel material, and a rear outer hydrogel layer; The silicone hydrogel material has an oxygen permeability of at least about 50, preferably at least about 60, more preferably at least about 70, even more preferably at least about 90, and most preferably at least about 110 barrers, and a first water content (WC) of about 10% to about 70%, preferably about 10% to about 65%, more preferably about 10% to about 60%, even more preferably about 15% to about 55%, and most preferably about 15% to about 50% (by weight). SiHy ) The anterior and posterior outer hydrogel layers are of substantially uniform thickness and are fused at the peripheral edges of the contact lens to completely encapsulate the inner layer of silicone hydrogel material, and the anterior and posterior outer hydrogel layers are, independently of one another, SiHy ≦45%, having a water swelling percentage of at least about 100% (preferably at least about 150%, more preferably at least about 200%, even more preferably at least about 250%, and most preferably at least about 300%); or (b) having a water swelling percentage of at least about 100% (preferably at least about 150%, more preferably at least about 200%, even more preferably at least about 250%, and most preferably at least about 300%) if WC SiHy If >45%, then at least about [0031] WC having a water expansion coefficient of SiHy having a higher secondary moisture content, A hydrated silicone hydrogel contact lens, wherein the anterior and posterior outer hydrogel layers each have a thickness of from about 0.1 μm to about 20 μm, preferably from about 0.25 μm to about 15 μm, more preferably from about 0.5 μm to about 15 μm, and even more preferably from about 1 μm to about 10 μm (as measured by atomic force microscopy across a cross section from the posterior to the anterior surface of the silicone hydrogel contact lens in a fully hydrated state).

2. The front and rear outer hydrogel layers are independently SiHy 10. The hydrated silicone hydrogel contact lens of claim 1 having a water swelling ratio of at least about 150%, if < 55%.

3. The front and rear outer hydrogel layers are independently SiHy 10. The hydrated silicone hydrogel contact lens of claim 1 having a water swelling ratio of at least about 200%, if < 60%.

4. The front and rear outer hydrogel layers are independently SiHy 10. The hydrated silicone hydrogel contact lens of claim 1 having a water swelling ratio of at least about 250%, if < 65%.

5. 10. The hydrated silicone hydrogel contact lens of claim 1, wherein the anterior and posterior outer hydrogel layers, independently of one another, have a water swelling rate of at least about 300%.

6. The silicone hydrogel material has an oxygen permeability of at least about 70 and a first water content (WC) of about 15% to about 55% (by weight). SiHy 6. The hydrated silicone hydrogel contact lens of claim 1, wherein the anterior and posterior outer hydrogel layers each have a thickness of from about 0.25 μm to about 15 μm.

7. 7. The hydrated silicone hydrogel contact lens of any one of claims 1 to 6, wherein the anterior and posterior outer hydrogel layers, independently of each other, have a reduced surface modulus relative to the inner layer by at least about 20%, preferably at least about 25%, more preferably at least about 30%, even more preferably at least about 35%, and most preferably at least about 40%.

8. The hydrated silicone hydrogel contact lens of any one of claims 1 to 7, wherein the anterior and posterior outer hydrogel layers each have a thickness of from about 0.5 μm to about 12.5 μm.

9. The hydrated silicone hydrogel contact lens of any one of claims 1 to 8, wherein the silicone hydrogel material has an elastic modulus of about 0.4 MPa to about 1.5 MPa.

10. 10. A hydrated silicone hydrogel contact lens according to any one of claims 1 to 9, wherein the anterior and posterior surfaces have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups) characterized by attracting up to about 200, preferably up to about 160, more preferably up to about 120, even more preferably up to about 90, and most preferably up to about 60 positively charged particles in a positively charged particle adhesion test.

11. 1. A hydrated silicone hydrogel contact lens comprising a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface, the contact lens having an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrers / mm, and a cross-sectional surface modulus profile, the cross-sectional surface modulus profile being along a shortest line between the anterior and posterior surfaces of a cross-sectional surface of the contact lens, the cross-sectional surface modulus profile including an anterior outer region including and adjacent the anterior surface; an inner region including a center and periphery of the shortest line; and a posterior outer region including and adjacent the posterior surface, the anterior outer region having an average anterior surface modulus of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrers / mm. [0032] and the posterior outer region has an average posterior coefficient [Equation 33] and the inner region has an average inner surface coefficient [0034] having [Equation 35] is at least about 20%, preferably at least about 25%, more preferably at least about 30%, even more preferably at least about 35%, and most preferably at least about 40%, and the anterior and posterior outer areas independently range from at least about 0.1 μm, preferably from about 0.1 μm to about 20 μm, more preferably from about 0.25 μm to about 15 μm, even more preferably from about 0.5 μm to about 12.5 μm, and most preferably from about 1 μm to about 10 μm.

12. 12. The hydrated silicone hydrogel contact lens of claim 11, wherein the anterior and posterior surfaces have a low surface concentration of negatively charged groups (e.g., carboxylic acid groups) characterized by attracting up to about 200, preferably up to about 160, more preferably up to about 120, even more preferably up to about 90, and most preferably up to about 60 positively charged particles in a positively charged particle adhesion test.

13. 1. A hydrated silicone hydrogel contact lens comprising a silicone hydrogel material as a bulk material, an anterior surface and an opposite posterior surface, the hydrated silicone hydrogel contact lens having (1) an oxygen transmissibility of at least about 40, preferably at least about 60, more preferably at least about 80, and even more preferably at least about 110 barrers / mm, and (2) good surface lubricity characterized by a critical coefficient of friction of about 0.046 or less, preferably about 0.043 or less, and more preferably about 0.040 or less, the anterior and posterior surfaces having a low surface concentration of negatively charged groups (e.g., carboxylic acid groups) characterized by attracting a maximum of about 200, preferably a maximum of about 160, more preferably a maximum of about 120, and even more preferably a maximum of about 90, and most preferably a maximum of about 60 positively charged particles in a positively charged particle adhesion test.

14. A hydrated silicone hydrogel contact lens comprising an inner layer of silicone hydrogel material, a front outer hydrogel layer and a rear outer hydrogel layer, the front and rear outer hydrogel layers being of substantially uniform thickness and fused at the peripheral edges of the contact lens to completely encapsulate the inner layer of silicone hydrogel material, the front outer region, the rear outer region and the inner region in a cross-sectional surface index profile representing the front outer hydrogel, the rear outer hydrogel and the inner layer, respectively, the hydrated silicone hydrogel contact lens having a water content (WC) of about 10% to about 70%, preferably about 10% to about 65%, more preferably about 10% to about 60%, even more preferably about 15% to about 55%, and most preferably about 15% to about 50% by weight. Lens ), the front and rear outer hydrogel layers having a thickness of about 0.1 μm to about 20 μm, more preferably about 0.25 μm to about 15 μm, even more preferably about 0.5 μm to about 12.5 μm, and most preferably about 1 μm to about 10 μm, and the front and rear outer hydrogel layers each having, independently of one another, a WC Lens is 45% or less, a water swelling ratio of at least about 100% (preferably at least about 150%, more preferably at least about 200%, even more preferably at least about 250%, and most preferably at least about 300%), or WC Lens If more than 45%, then at least about [0036] The hydrated silicone hydrogel contact lens of any one of claims 11 to 13, having a water swelling coefficient of

15. The front and rear outer hydrogel layers are independently Lens 15. The hydrated silicone hydrogel contact lens of claim 14 having a water swelling ratio of at least about 150%, if < 55%.

16. The front and rear outer hydrogel layers are independently Lens 15. The hydrated silicone hydrogel contact lens of claim 14 having a water swelling ratio of at least about 200%, if < 60%.

17. The front and rear outer hydrogel layers are independently Lens 15. The hydrated silicone hydrogel contact lens of claim 14 having a water swelling ratio of at least about 250%, if < 65%.

18. 15. The hydrated silicone hydrogel contact lens of claim 14, wherein the anterior and posterior outer hydrogel layers, independently of one another, have a water swelling rate of at least about 300%.

19. The hydrated silicone hydrogel contact lens of any one of claims 1-7, 9, 10, and 14-18, wherein the anterior and posterior outer hydrogel layers independently have a thickness of from about 0.25 μm to about 15 μm.

20. The hydrated silicone hydrogel contact lens of any one of claims 1-10 and 14-18, wherein the anterior and posterior outer hydrogel layers independently have a thickness of from about 0.5 μm to about 12.5 μm.

21. The hydrated silicone hydrogel contact lens of any one of claims 1-10 and 14-18, wherein the anterior and posterior outer hydrogel layers independently have a thickness of from about 1 μm to about 10 μm.

22. 22. A hydrated silicone hydrogel contact lens according to any one of claims 1 to 10 and 14 to 21, further comprising two transition layers of polymeric material in its layered configuration, each of the two transition layers being located between the inner layer and one of the anterior and posterior outer hydrogel layers and being of substantially uniform thickness, each transition layer having a thickness of at least about 0.05 μm, preferably from about 0.05 μm to about 10 μm, more preferably from about 0.1 μm to about 7.5 μm, and even more preferably from about 0.15 μm to about 5 μm.

23. 23. The hydrated silicone hydrogel contact lens of any one of claims 1 to 22, having high digital rub resistance characterized by no visible surface cracking lines under dark field after rubbing the SiHy contact lens between fingers.

24. 24. The hydrated silicone hydrogel contact lens of any one of claims 1 to 23, having good surface lubricity characterized by a critical coefficient of friction of about 0.043 or less, more preferably about 0.040 or less.

25. 24. The hydrated silicone hydrogel contact lens of any one of claims 1 to 23, having a surface hydrophilicity characterized by having a water disintegration time of at least about 10 seconds; a surface wettability characterized by having an average water contact angle of about 90 degrees or less, preferably about 80 degrees or less, more preferably about 70 degrees or less, even more preferably about 60 degrees or less, and most preferably about 50 degrees or less; or a combination thereof.

26. 23. The hydrated silicone hydrogel contact lens of claim 22, wherein the transition layer comprises a carboxyl (COOH) containing polymer, preferably a homo- or copolymer of acrylic acid or methacrylic acid, more preferably polyacrylic acid or polymethacrylic acid.

27. 27. A hydrated silicone hydrogel contact lens according to any one of claims 1 to 10, 14 to 22 and 26, wherein the anterior and posterior outer hydrogel layers are formed by applying and crosslinking a water soluble and crosslinkable hydrophilic polymeric material onto a preformed silicone hydrogel contact lens, the preformed silicone hydrogel contact lens comprising amino and / or carboxyl groups or a base coating comprising amino and / or carboxyl groups at and / or near the surface of the contact lens; and the preformed silicone hydrogel contact lens becomes the inner layer after crosslinking.

28. 28. The hydrated silicone hydrogel contact lens of claim 27, wherein the water-soluble and crosslinkable hydrophilic polymeric material is a partially crosslinked polymeric material comprising a three-dimensional network structure and crosslinkable groups, preferably azetidinium groups, within the network structure.

29. 28. The hydrated silicone hydrogel contact lens of claim 27, wherein the water-soluble and crosslinkable hydrophilic polymeric material comprises: (i) about 20% to about 95% (by weight) of a first polymer chain derived from an epichlorohydrin-functionalized polyamine or polyamidoamine; (ii) about 5% to about 80% (by weight) of a hydrophilic portion or second polymer chain derived from at least one hydrophilicity enhancing agent having at least one reactive functional group selected from the group consisting of an amino group, a carboxyl group, a thiol group, and combinations thereof, wherein the hydrophilic portion or second polymer chain is covalently linked to the first polymer chain through one or more covalent bonds formed between an azetitdinium group of the epichlorohydrin-functionalized polyamine or polyamidoamine and an amino, carboxyl, or thiol group of the hydrophilicity enhancing agent, respectively; and (iii) azetidinium groups that are part of the first polymer chain or pendant or terminal groups covalently linked to the first polymer chain.

30. The hydrophilic polymer used as the hydrophilic enhancer is PEG-NH 2 ;PEG-SH;PEG-COOH;H 2 N-PEG-NH 2 ;HOOC-PEG-COOH;HS-PEG-SH;H 2 N-PEG-COOH;HOOC-PEG-SH;H 2 N-PEG-SH; a branched PEG having one or more amino, carboxyl or thiol groups; a PEG dendrimer having one or more amino, carboxyl or thiol groups; a diamino-, dicarboxyl-, monoamino- or monocarboxyl-terminated homo- or copolymer of a non-reactive hydrophilic vinyl monomer; a copolymer that is the polymerization product of a composition comprising (1) up to about 60% (by weight), preferably about 0.1% to about 30%, more preferably about 0.5% to about 20%, and even more preferably about 1% to about 15% (by weight) of at least one reactive vinyl monomer and (2) at least one non-reactive hydrophilic vinyl monomer; or a combination thereof, wherein the PEG is a polyethylene glycol segment and the reactive vinyl monomer is amino-C 1 -C 6 Alkyl (meth)acrylate, C 1 -C 6 Alkylamino-C 1 -C 6 Alkyl (meth)acrylate, allylamine, vinylamine, amino-C 1 -C 6 Alkyl (meth)acrylamide, C 1 -C 6 Alkylamino-C 1 -C 6 Alkyl (meth)acrylamide, acrylic acid, C 1 -C 4 and the non-reactive vinyl monomer is selected from the group consisting of acrylamide, methacrylamide, N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-vinylpyrrolidone, N,N-dimethylaminoethyl methacrylate, N,N-dimethylaminoethyl acrylate, N,N-dimethylaminopropyl ... methacrylamide, N,N-dimethylaminopropylacrylamide, glycerol methacrylate, 3-acryloylamino-1-propanol, N-hydroxyethylacrylamide, N-[tris(hydroxymethyl)methyl]-acrylamide, N-methyl-3-methylene-2-pyrrolidone, 1-ethyl-3-methylene-2-pyrrolidone, 1-methyl-5-methylene-2-pyrrolidone, 1-ethyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, 5-ethyl-3-methylene-2-pyrrolidone, 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, phosphorylcholine-containing vinyl monomers, C having a weight average molecular weight of up to 1500 Daltons 1 -C 4 30. The hydrated silicone hydrogel contact lens of claim 29, wherein the hydroxyl group is selected from the group consisting of N-alkoxypolyethylene glycol (meth)acrylates, N-vinylformamide, N-vinylacetamide, N-vinylisopropylamide, N-vinyl-N-methylacetamide, allyl alcohol, vinyl alcohol (hydrolyzed form of vinyl acetate in the copolymer), and combinations thereof.

31. The hydrated silicone hydrogel contact lens of any one of claims 1-10, 14-22, and 26-30, wherein the anterior and posterior outer hydrogel layers contain crosslinks derived from azetidinium groups in a thermally induced coupling reaction.

32. 32. The hydrated silicone hydrogel contact lens of any one of claims 1 to 31, wherein the silicone hydrogel material is obtained from a silicone hydrogel lens formulation comprising at least one component selected from the group consisting of silicone-containing vinyl monomers, silicone-containing vinyl macromers, silicone-containing prepolymers, hydrophilic vinyl monomers, hydrophobic vinyl monomers, crosslinkers, free radical initiators, hydrophilic vinyl macromers / prepolymers, and combinations thereof.

33. 33. The hydrated silicone hydrogel contact lens of claim 32, wherein the silicone hydrogel lens formulation comprises: (1) a hydrophilic vinyl monomer selected from the group consisting of N,N-dimethylacrylamide, N,N-dimethylmethacrylamide, N-vinylpyrrolidone, N-vinyl-N-methylacetamide, 1-methyl-5-methylene-2-pyrrolidone, 5-methyl-3-methylene-2-pyrrolidone, hydroxyethyl methacrylate, hydroxyethyl acrylate, and combinations thereof; and (2) a silicone-containing vinyl monomer, polysiloxane-containing vinyl monomer or macromer, and / or a silicone-containing prepolymer.

Citation Information

Patent Citations

  • Intraocular lens, and method for suppressing secondary cataract

    JP2005185776A

  • Wettable silicone hydrogel contact lenses, and related compositions and methods

    JP2008020918A

  • Method for manufacturing silicone hydrogel contact lenses with good coating durability

    JP2009540369A

  • Crosslinkable polyion coating for contact lenses

    JP2010518436A

  • Azetidinium modified polymers and fabric treatment composition

    US20050060812A1